A high-resolution α-glucosidase inhibition profiling for targeted identification of natural antidiabetic products from Lycopodiella cernua (L.) Pic. Serm and their inhibitory mechanism study - Bing-Rui Liu; Xu-Liu Shi; Jian-Kun Yan; Rui Zhao (Natural Product Research, 2023)

Assessment of wellbore integrity failure risk and hazardous zones in depleted reservoirs underground gas storage during the operation processes - Rui Wang; Ergun Kuru; Chaojie Zhao; Minggang Liu; Yanxin Jin (Environmental Science and Pollution Research, 2023)

Roxarsone biotransformation by a nitroreductase and an acetyltransferase in Pseudomonas chlororaphis, a bacterium isolated from soil - Jie-wen Ma; Gui-wen Liu; Jia-Yu Zhai; Ke-qian Zhao; Ya-qing Wu; Rui-lian Yu; Gong-ren Hu; Yu Yan (Chemosphere, 2023)

Effects of single and combined contamination of total petroleum hydrocarbons and heavy metals on soil microecosystems: Insights into bacterial diversity, assembly, and ecological function - Du Zhang; Qi Hu; Bing Wang; Junwen Wang; Can Li; Ping You; Rui Zhou; Weimin Zeng; Xueduan Liu; Qian Li (Chemosphere, 2023)

Induced mechanism of phosphatase hormesis by Cd ions and rhizosphere metabolites of Trifolium repens L. - Chenxi Zhang; Haibo Li; Yue Yang; Xulun Zhou; Damiao Zhuang; Wengang Liu; Kaixuan Wang; Pengkai Wang; Wenxin Zhang; Yaran Bai; Haotian Ma; Bingqian Gao; et al. (Chemosphere, 2023)

O2 plasma-modified carbon nanotube for sulfamethoxazole degradation via peroxymonosulfate activation: Synergism of radical and non-radical pathways boosting water decontamination and detoxification - Shiqi Liu; Zichen Zhang; Rui Lu; Yuankun Mao; Huiru Ge; Can Liu; Chenxi Tian; Siyuan Yin; Li Feng; Yongze Liu; Chao Chen; Liqiu Zhang (Chemosphere, 2023)

Simulating droplet distribution characteristics for sprinkler irrigation with a modified ballistic model - Rui Zhang; Yichuan Liu; Delan Zhu; Pute Wu; Changjuan Zheng; Xiaomin Zhang; Nazarov Khudayberdi; Changxin Liu (Computers and Electronics in Agriculture, 2023)

Automatic detection of crop lodging from multitemporal satellite data based on the isolation forest algorithm - Rui Guo; Xiufang Zhu; Tingting Liu (Computers and Electronics in Agriculture, 2023)

A robust rice yield estimation framework developed by grading modeling and normalized weight decision-making strategy using UAV imaging technology - Rui Yang; Jun Zhou; Xiangyu Lu; Jianxun Shen; Huizhe Chen; Mengyuan Chen; Yong He; Fei Liu (Computers and Electronics in Agriculture, 2023)

First report of Fusarium sacchari causing root rot of tobacco (Nicotiana tabacum L.) in China - Rui Qiu; Caihong Li; Xiaojie Li; Yingying Zhang; Chang Liu; Chenjun Li; Yuguo Chen; Jingke Bai; Min Xu; Ruifang Song; Shujun Li (Crop Protection, 2023)

Improvement of flesh quality, muscle growth and protein deposition in adult grass carp (Ctenopharyngodon idella): The role of tryptophan - Lu-Qiao Xiao; Wei-Dan Jiang; Pei Wu; Yang Liu; Hong-Mei Ren; Ling Tang; Shu-Wei Li; Cheng-Bo Zhong; Rui-Nan Zhang; Lin Feng; Xiao-Qiu Zhou (Aquaculture, 2023)

Dietary supplementation with polysaccharides from Rhizoma dioscoreae resulting in the enhanced immunity and the structural modulation of the intestinal microbiota in Luciobarbus capito - Yuan Sun; Xiaowei Hu; Xianwei Meng; Rui Liu; Zhigang Zhao; Shihui Wang; Rui Zhang; Kun Guo; Liang Luo (Aquaculture, 2023)

Growth patterns and feeding characteristics in early developmental stages of Takifugu rubripes cultured in a recirculating aquaculture system - Xiaoqiang Gao; Shuquan Cao; Xianhong Zhang; Zhiwen Zhu; Chen Hai-Bin; Xing Rui; Kui-Feng Zhao; Chuan-Xin Zhang; Bao-Liang Liu (Aquaculture, 2023)

Unexpected shifts of dissolved carbon biogeochemistry caused by anthropogenic disturbances in karst rivers - Maofei Ni; Rui Liu; Weijun Luo; Junbing Pu; Jing Zhang; Xiaodan Wang (Water Research, 2023)

Antiviral effects of duck type I and type III interferons against Duck Tembusu virus in vitro and in vivo - Peng Zhou; Dejian Liu; Qingxiang Zhang; Wanrong Wu; Dong Chen; Rui Luo (Veterinary Microbiology, 2023)

The co-regulation of the gut microbiome and host genes might play essential roles in metformin gastrointestinal intolerance - Huixiang Zhang; Jiao Lai; Lihuan Zhang; Wei Zhang; Xun Liu; Qilin Gong; Hongxi Tian; Mingzhi Yang; Tao Yang; Rui Zhao; Dongqing Li; Hehua Huang; et al. (Toxicology and Applied Pharmacology, 2023)

Geophysical constraints on the deep structure beneath the Xiong'an New Area geothermal field, North China - Hongqiang Li; Ramon Carbonell; Rui Gao; Xingfu Huang; Jie Zhang; Xiaofan Deng; Lei Gao; Hongkai Liu; Hesheng Hou (Tectonophysics, 2023)

Iron isotope fractionation of redox and geochemical cycling in the typical Gleysols in Mun River Basin, Northeast Thailand - Qian Zhang; Guilin Han; Jie Zeng; Lingqing Wang; Guangyou Zhu; Man Liu; Bin Liang; Rui Qu; Xiaoqiang Li; Shitong Zhang (Science of The Total Environment, 2023)

Migration and adsorption of naphthalene in road-deposited sediments from stormwater runoff: Impact of the particle size - Hongze Liu; Fuguo Qiu; Mingchen Gao; Yongjian Che; Chaohong Tan; Ziyang Zhang; Rui Yan; Haiyan Li; Meipeng Jian (Science of The Total Environment, 2023)

Nano- and micro-plastic transport in soil and groundwater environments: Sources, behaviors, theories, and models - Jun Xu; Rui Zuo; Jinhua Shang; Guanlan Wu; Yanan Dong; Shida Zheng; Zuorong Xu; Jingchao Liu; Yunxiang Xu; Ziyi Wu; Chenxi Huang (Science of The Total Environment, 2023)

Historical peak situation of building carbon emissions in different climate regions in China: Causes of differences and peak challenges - Rui Li; Liu Chen; Weiguang Cai; Kairui You; Zhaoji Li; Lina Ran (Science of The Total Environment, 2023)

Nitrite stimulates HONO and NOx but not N2O emissions in Chinese agricultural soils during nitrification - Yaqi Song; Dianming Wu; Xiaotang Ju; Peter Dörsch; Mengdi Wang; Ruhai Wang; Xiaotong Song; Lingling Deng; Rui Wang; Zhiwei Gao; Haroon Haider; Lijun Hou; et al. (Science of The Total Environment, 2023)

The suitability of isotopic methods in identifying water sources of a shallow-rooted herbaceous plant in a desert steppe - Yifan Song; Denghua Yan; Tiejun Liu; Yajing Lu; Rui Jiao; Yunhao Wen; Tianling Qin; Baisha Weng; Wei Shi (Science of The Total Environment, 2023)

Seroprevalence and potential risk factors of brucellosis in sheep from America, Africa and Asia regions: A systematic review and meta-analysis - Lian-Min Li; Qi Wang; Jun-Feng Shi; Ting Li; Bo Zhao; Qing-Xia Ma; Hong-Ying Liu; Nuo Su; Ruo-Peng Cai; Fan-Li Zeng; Qing-Long Gong; Kun Shi; et al. (Research in Veterinary Science, 2023)

Westerly aridity in the western Tarim Basin driven by global cooling since the mid-Pleistocene transition - Hongye Liu; Rui Zhang; Yansheng Gu; Gaowen Dai; Lin Li; Shuo Guan; Zhongbiao Fu (Quaternary Science Reviews, 2023)

Fabrication of high permeability and antifouling composite membrane loaded with Fe3O4 nanoparticles via a magnetic field induced phase separation - Meng Zhang; Shu Jiang; Xishou Guo; Xiaobin Tang; Langming Bai; Jinlong Wang; Han Zhang; Daliang Xu; Rui Wu; Luming Liu; Heng Liang (Journal of Water Process Engineering, 2023)

The roles of Methylobacterium organophilum and Sphingomonas melonis for accelerating N-methyl pyrrolidone (NMP) biodegradation - Yongyi Gao; Ting Chen; Yifan Hou; Ruiyun Xue; Rui Liu; Fu Chen; Yongming Zhang; Bruce E. Rittmann (Journal of Water Process Engineering, 2023)

Protective and immunomodulatory effects of mesenchymal stem cells on multiorgan injury in male rats with heatstroke - Yuyan Liu; Yun Li; Zihui Deng; Yan Zhao; Rui Yuan; Mengmeng Yang; Lu Wang; Yuan Fang; Dengfeng Ding; Feihu Zhou; Hongjun Kang (Journal of Thermal Biology, 2023)

Characterization of aquifer heterogeneity by tomographic slug test responses considering wellbore effects - Quan Liu; Linwei Hu; Rui Hu; Ralf Brauchler; Yixuan Xing; Junjie Qi; Thomas Ptak (Journal of Hydrology, 2023)

Evaluation of GPM IMERG and error sources for tropical cyclone precipitation over eastern China - Fengjiao Chen; Rui Wang; Peng Liu; Lu Yu; Yan Feng; Xiaoyi Zheng; Jinlan Gao (Journal of Hydrology, 2023)

Auto encoder generative adversarial networks - based mineral prospectivity mapping in Lhasa area, Tibet - Miao Xie; Bingli Liu; Lu Wang; Cheng Li; Yunhui Kong; Rui Tang (Journal of Geochemical Exploration, 2023)

Nexus between water-energy-carbon footprint network: Multiregional input-output and coupling coordination degree analysis - Xiuli Liu; Duc Vu; Sandun C. Perera; Guofeng Wang; Rui Xiong (Journal of Cleaner Production, 2023)

Quantitative flood disaster loss-resilience with the multilevel hybrid evaluation model - Rui Yan; Lulu Liu; Wanlu Liu; Shaohong Wu (Journal of Environmental Management, 2023)

Enhanced biological wastewater treatment supplemented with anaerobic fermentation liquid of primary sludge - Lin Li; Qiqi Liao; Caihong Liu; Tanglong Zhang; Chang Liu; Ziwei Chen; Rui Gao; Qiang He (Journal of Environmental Management, 2023)

CeO2 nanorods with bifunctional oxygen vacancies for promoting low-pressure photothermocatalytic CO2 conversion with CH3OH to dimethyl carbonate - Shanbiao Jin; Xiushuai Guan; Xiaochao Zhang; Changming Zhang; Jianxin Liu; Yawen Wang; Yunfang Wang; Rui Li; Zhong Li; Caimei Fan (Journal of Environmental Chemical Engineering, 2023)

Parental exposure to environmental cadmium causes developmental defects in the rare minnow (Gobiocypris rarus) embryos: The association between ROS-mediated oxidative stress and developmental dysfunction - Liangxia Su; Huanhuan Li; Yinrui Wu; Anni Tao; Ning Qiu; Rui Wang; Liu Jun; Jianwei Wang (Journal of Environmental Chemical Engineering, 2023)

Microwave assisted synthesis of PQ-GDY@NH2-UIO-66(Zr) for improved photocatalytic removal of NO under visible light - Qingyu Yang; Shuangjun Li; Rui Liang; Lei Gao; Shao Zhang; Junfen Jia; Yiran Liu; Rundong Lyv; Guisheng Li; Shengxiong Xiao; Dieqing Zhang (Journal of Environmental Sciences, 2023)

Low-carbon economic analysis of a virtual power plant with wind and solar power considering the integrated flexible operation mode of a carbon capture thermoelectric unit - Chunming Zhu; Gang Bao; Rui Xu; Zhenyan Song; Yikai Liu (International Journal of Greenhouse Gas Control, 2023)

New insight into the pyrophoricity and mechanism of ironic sulfide from synergistic effect of FeS and FeS2 - Kai Pan; Hui Liu; Zhihui Lang; Rui Huang; Ze Wei; Wenjing Ji; Jianhai Wang; Dong Ye; Haining Wang (Fuel, 2023)

CaO hydrated with ethanol solution for flue gas HCl immobilization. Part II: Influences of gas components - Rui Wang; Xiaoshuo Liu; Cong Chen; Yuqing Wang; Zhen Shen; Lei Meng; Xiaobing Gu; Changdong Sheng; Yufeng Duan (Fuel, 2023)

Highly-efficient hydrogen production from ammonia decomposition over Co-doped graphdiyne under moderate temperature - Lishan Liu; Feng Gong; Yunlong Xie; Sijun Wang; Yu Qiu; Zhihua Wang; Rui Xiao (Fuel, 2023)

Unraveling symbiotic microbial communities, metabolomics and volatilomics profiles of kombucha from diverse regions in China - Shiqi Li; Saiqun Wang; Leran Wang; Xiaoshuang Liu; Xingnan Wang; Rui Cai; Yahong Yuan; Tianli Yue; Zhouli Wang (Food Research International, 2023)

An electrochemical sensor derived from Cu-BTB MOF for the efficient detection of diflubenzuron in food and environmental samples - Xian-Xian Ji; Yu-Long Liu; Xin-Yue Chang; Rui-Long Li; Fei Ye; Liu Yang; Ying Fu (Food Chemistry, 2023)

Cyanidin-3-O-glucoside from blueberry anthocyanin extracts protects ARPE-19 cells against high glucose damage via REDD1/GSK3β pathway - Rui Li; Zhan Ye; Yong-jiang Xu; Yuanfa Liu (Food Bioscience, 2023)

Novel herbal beverage ameliorates exercise-induced fatigue in mice by modulating oxidative stress and reshaping the gut microbiota - Xiangchang Yin; Juan Song; Rui Xue; Xiaojuan Chen; Wei Zheng; Yue Liu; Jie Zhang; Beilei Dong; Youzhi Zhang; Baiping Ma (Food Bioscience, 2023)

Combining vegetation, color, and texture indices with hyperspectral parameters using machine-learning methods to estimate nitrogen concentration in rice stems and leaves - Dunliang Wang; Rui Li; Tao Liu; Shengping Liu; Chengming Sun; Wenshan Guo (Field Crops Research, 2023)

An interval water demand prediction method to reduce uncertainty: A case study of Sichuan Province, China - Xinyu Xia; Bin Liu; Rui Tian; Zuli He; Suyue Han; Ke Pan; Jingjing Yang; Yiting Zhang (Environmental Research, 2023)

Mitigating abortion risk of synthetic musk-contained body wash in pregnant women: Risk assessment and mechanism analysis - Xixi Li; Rui Li; Yong Niu; Meijin Du; Hao Yang; Di Liu (Environmental Pollution, 2023)

Developing energy flexibility in clusters of buildings: A critical analysis of barriers from planning to operation - Jérôme Le Dréau; Rui Amaral Lopes; Sarah O'Connell; Donal Finn; Maomao Hu; Humberto Queiroz; Dani Alexander; Andrew Satchwell; Doris Österreicher; Ben Polly; Alessia Arteconi; Flavia de Andrade Pereira; et al. (Energy and Buildings, 2023)

Conversion of highly polymerized lignin into monophenolic products via pyrolysis: A comparative study of acidic and alkaline depolymerization pretreatments using deep eutectic solvents - Xin Yue; Jinxin Lin; Terhi Suopajärvi; Otto Mankinen; Atte Mikkelson; Rui Liu; Harri Huttunen; Liheng Chen; Chunlin Xu; Ville-Veikko Telkki; Shirong Sun; Henrikki Liimatainen (Chemical Engineering Journal, 2023)

Anti-freezing hydrogel thermocells with confined microcrystallization for enhanced low-grade heat harvest - Ping-Fan Li; Ting-Yuan Hu; Tao Luo; Zhuang Liu; Xiao-Jie Ju; Rui Xie; Da-Wei Pan; Wei Wang; Liang-Yin Chu (Chemical Engineering Journal, 2023)

Design of corrosion-resistant absorbers with a core @ compact film structure based on the “dissolution-redeposition” theory - Jiaxin Qian; Yu Cui; Shucheng Ren; Rui Liu; Song Ma; Pengfei Ju; Li Liu (Chemical Engineering Journal, 2023)

Oxalic acid-enhanced sulfamethoxazole degradation by V2O3/percarbonate process: Insights into the reactive oxygen species generation and conversion - Rui Liu; Mu-cheng Xu; Jin-yan Yang (Chemical Engineering Journal, 2023)

Rare earth regulatory defect engineering: A multifunctional nanoplatform for breast cancer therapy through PANoptosis - Rui Zhang; Guobo Chen; Jun Du; Qian Wang; Qingwen Qi; Xueyu Li; Lejin Zhu; Xingzhou Chen; Baolin Liu; Yuqing Miao; Yuhao Li (Chemical Engineering Journal, 2023)

Preparation of microstructure controllable Al/WO3/F2603 MICs by droplet microfluidic technology to improve combustion performance - Jinqiang Zhou; Qi Pan; Xueyong Guo; Jianxin Nie; Rui Liu (Chemical Engineering Journal, 2023)

A review of starch swelling behavior: Its mechanism, determination methods, influencing factors, and influence on food quality - Ruoyu Jia; Congli Cui; Lin Gao; Yang Qin; Na Ji; Lei Dai; Yanfei Wang; Liu Xiong; Rui Shi; Qingjie Sun (Carbohydrate Polymers, 2023)

Remediation of Pb- and, Cd-contaminated soil through magnetic-modified eluent synergetic freeze-thaw and washing - Yuru Wang; Dahu Rui; Wenjun Nie; Mintae Kim; Daoning Hu; Jun Zhang; Jianfei Liu (Cold Regions Science and Technology, 2023)

Assessing indoor PM2.5 microbial activity in a university campus environments in Beijing - Hua Zhao; Rui Du; Yinhang Liu; Du Wang; Yuanyuan Li (Building and Environment, 2023)

Stable precipitation isotope records of cold wave events in Eurasia - Xinrui Lin; Guofeng Zhu; Dongdong Qiu; Linlin Ye; Yuwei Liu; Longhu Chen; Jiawei Liu; Siyu Lu; Lei Wang; Kailiang Zhao; Wenhao Zhang; Rui Li; et al. (Atmospheric Research, 2023)

Research Progress on TRPA1 in Diseases - Jiajing Li; Hongfei Zhang; Qian Du; Junyu Gu; Jiangbo Wu; Qi Liu; Zhuo Li; Ting Zhang; Jingyu Xu; Rui Xie (The Journal of Membrane Biology, 2023)
For a long time, the physiological activity of TRP ion channels and the response to various stimuli have been the focus of attention, and the physiological functions mediated by ion channels have subtle links with the occurrence of various diseases. Our group has been engaged in the study of ion channels. In recent years, the report rate of TRPA1 , the only member of the TRPA subfamily in the newly described TRP channel, has been very high. TRPA1 channels are not only abundantly expressed in peptidergic nociceptors but are also found in many nonneuronal cell types and tissues, and through the regulation of Ca 2+ influx, various neuropeptides and signaling pathways are involved in the regulation of nerves, respiration, circulation, and various diseases and inflammation throughout the body. In this review, we mainly summarize the effects of TRPA1 on various systems in the body, which not only allows us to have a more systematic and comprehensive understanding of TRPA1 but also facilitates more in-depth research on it in the future. Graphical Abstract

Peripheral BDNF Regulates Somatosensory–Sympathetic Coupling in Brachial Plexus Avulsion-Induced Neuropathic Pain - Hang Xian; Huan Guo; Yuan-Ying Liu; Jian-Lei Zhang; Wen-Chao Hu; Ming-Jun Yu; Rui Zhao; Rou-Gang Xie; Hang Zhang; Rui Cong (Neuroscience Bulletin, 2023)

A multi-view assisted registration network for MRI registration pre- and post-therapy - Yanxia Liu; Xiaozhen Li; Rui Li; SiJuan Huang; Xin Yang (Medical & Biological Engineering & Computing, 2023)

Improvement of Soil Structure and Bacterial Composition by Long-Term Application of Seaweed Fertilizer - Liu Qiqin; Zhou Huaguang; Sun Minxiu; Li Qian; Fan Haijun; Chen Haimin; Yang Rui (Journal of Soil Science and Plant Nutrition, 2023)

The Role of Cystathionine-β-Synthase, H2S, and miRNA-377 in Hypoxic-Ischemic Encephalopathy: Insights from Human and Animal Studies - Chun-Yang Liu; Hisham Al-Ward; Ning Liu; Francine Ngaffo Mekontso; Wei Chen; Wenxia Gao; Chunxue Zhang; Abduh Murshed; Zi-Rui Yu; Orion Fan; Yi Eve Sun; Hui Xu (Journal of Molecular Neuroscience, 2023)

Mitochondrial dysfunction: a new molecular mechanism of intervertebral disc degeneration - Chao Song; Yulin Xu; Qinghua Peng; Rui Chen; Daqian Zhou; Kang Cheng; Weiye Cai; Tao Liu; Chenyi Huang; Zhijiang Fu; Cong Wei; Zongchao Liu (Inflammation Research, 2023)

Associations of 10 trace element levels in the whole blood with risk of three types of obesity in the elderly - Rui Zhan; Lin Liu; Maoyuan Yang; Yating Ren; Zhihao Ge; Jun Shi; Ke Zhou; Jiebao Zhang; Hongjuan Cao; Linsheng Yang; Kaiyong Liu; Jie Sheng; et al. (Environmental Geochemistry and Health, 2023)

Nano-composite system of traditional Chinese medicine for ocular applications: molecular docking and three-dimensional modeling insight for intelligent drug evaluation - Xinyi Jiao; Xingru Peng; Xin Jin; Ning Liu; Yang Yu; Rui Liu; Zheng Li (Drug Delivery and Translational Research, 2023)

17β-Estradiol Mediates Staphylococcus aureus Adhesion in Vaginal Epithelial Cells via Estrogen Receptor α-Associated Signaling Pathway - Lina Yan; Can Rui; Bin Zhuang; Xia Liu; Ting Luan; Lisha Jiang; Zhiyong Dong; Qing Wang; Aiwen Wu; Ping Li; Xinyan Wang; Xin Zeng (Current Microbiology, 2023)

Tracing nitrate pollution sources of karst groundwater in water resources using environmental isotopes - Yunfeng Zhang; Dalu Yu; Di Wu; Yuhui Zhao; Zhe Zhang; Bo Li; Baohui Huang; Mingguo Wang; Junru Gao; Yuxiao Kang; Rui Liu (Carbonates and Evaporites, 2023)

Soil microbial communities as potential regulators of N2O sources in highly acidic soils - Junhui Yin; Huaihai Chen; Pengpeng Duan; Kun Zhu; Naihui Li; Yan Ma; Yumeng Xu; Jingheng Guo; Rui Liu; Qing Chen (Soil Ecology Letters, 2023)

Development characteristics and failure modes of reactivated ancient landslides in the Sichuan–Tibet transportation corridor, China - Rui-an Wu; Yong-shuang Zhang; Chang-bao Guo; San-shao Ren; Xin Yao; Xiao-yi Liu; Zhi-hua Yang; Guo-liang Du (Journal of Mountain Science, 2023)

Ecosystem responses dominate the trends of annual gross primary productivity over terrestrial ecosystems of China during 2000–2020 - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Hua Qi; Meng Yang; Zhao-Gang Liu; Xiao-Jun Dou; Le-Xin Ma; Shi-Ping Chen; et al. (Agricultural and Forest Meteorology, 2023)

Hypermethylation of the ADIRF promoter regulates its expression level and is involved in NNK-induced malignant transformation of lung bronchial epithelial cells - Rui Xiong; Yiheng Du; Sili Chen; Tao Liu; Xiangyu Ding; Jiaxin Zhou; Zhi Wang; Qiaoyuan Yang (Archives of Toxicology, 2023)

The development of ecological civilization in China based on the economic–social–natural complex system - Rui Xiao; Haiguang Hao; Huiyuan Zhang; Yujie Liu; Mengxiao Liu (Ambio, 2023)

Reversing seasonality of Southern Hemisphere Annular Mode trend in the 21st century - Fei Zheng; Xiaoning Liu; Hao Wang; Yuxun Li; Rui Wang; Shuailei Yao; Wenjie Dong (International Journal of Climatology, 2023)
The Southern Hemisphere Annular Mode (SAM) is the dominant mode of atmospheric circulation in the Southern Hemisphere extratropical region. In the late 20th century, the SAM underwent a remarkable positive trend, with the strongest trend occurring in austral summer because of Antarctic ozone depletion. In this study, we quantitatively explore changes in the seasonality of the SAM trend under the background of ozone recovery. As expected, accompanied by ozone recovery since 2001, the summer SAM trend has decreased, thus reducing the seasonal difference in the SAM trend between summer and winter. However, what was not expected and found in this study is that the winter SAM has meanwhile shown an increasing positive trend in the early 21st century, which further reverses the seasonality of the SAM trend, leading to a stronger trend in winter rather than summer, which is different from the seasonality in the late 20th century. The reason underlying the winter SAM changes is explored from the perspective of natural variability. Winter SAM exhibits clear multidecadal variability, and the recent increasing trend is a part of multidecadal oscillation. The multidecadal variability of winter SAM may partly originate from the Atlantic Multidecadal Oscillation. The seasonality of linear trend in extratropical surface climate also exhibits reversing characteristics since 2001. In the early 21st century, the acceleration of westerlies and the strengthening of Amundsen Sea Low are stronger in winter, reversing the previous seasonality in the late 20th century, in which the acceleration of westerlies and the strengthening of Amundsen Sea Low is stronger in summer.

A Pre-Procession Module for Point-Based Deep Learning in Dense Point Clouds in the Ship Engineering Field - Shilin Huo; Yujun Liu; Ji Wang; Rui Li; Xiao Liu; Jiawei Shi (Journal of Marine Science and Engineering, 2023)
Recently, point cloud technology has been applied in the ship engineering field. However, the dense point cloud acquired by terrestrial laser scanning (TLS) technology in ship engineering applications brings an obstacle to some powerful and advanced point-based deep learning point cloud processing methods. This paper presents a deep learning pre-procession module to ensure the feasibility of processing dense point clouds on commonly available computer devices. The pre-procession module is designed according to the traditional point cloud processing methods and the PointNet++ paradigm, and is evaluated on two ship structure datasets and two popular point cloud datasets. Experimental results illustrate that (i) the proposed module improves the performance of point-based deep learning semantic segmentation networks, and (ii) the proposed module empowers the existing point-based deep learning networks with the capability to process dense input point clouds. The proposed module may provide a useful semantic segmentation tool for realistic dense point clouds in various industrial applications.

High-quality development efficiency in Yangtze River Delta urban agglomeration: analysis of spatiotemporal evaluation and influencing factors - Xiaoxue Wei; Rui Zhao; Ranran Li; Ke Liu (Environment, Development and Sustainability, 2023)

Toward the development of smart capabilities for understanding seafloor stretching morphology and biogeographic patterns via DenseNet from high-resolution multibeam bathymetric surveys for underwater vehicles - Rui Nian; Shasha Liu; Zongcan Lu; Xiaoyu Li; Shidong Ren; Yuqi Qian; Qiuying Li; Guotong He; Kexin Shi; Guoyao Zhang; Lina Zang; Luyao Li; et al. (Frontiers in Marine Science, 2023)
The increasing use of underwater vehicles facilitates deep-sea exploration at a wide range of depths and spatial scales. In this paper, we make an initial attempt to develop online computing strategies to identify seafloor categories and predict biogeographic patterns with a deep learning-based architecture, DenseNet, integrated with joint morphological cues, with the expectation of potentially developing its embedded smart capacities. We utilized high-resolution multibeam bathymetric measurements derived from MBES and denoted a collection of joint morphological cues to help with semantic mapping and localization. We systematically strengthened dominant feature propagation and promoted feature reuse via DenseNet by applying the channel attention module and spatial pyramid pooling. From our experiment results, the seafloor classification accuracy reached up to 89.87%, 82.01%, and 73.52% on average in terms of PA, MPA, and MIoU metrics, achieving comparable performances with the state-of-the-art deep learning frameworks. We made a preliminary study on potential biogeographic distribution statistics, which allowed us to delicately distinguish the functionality of probable submarine benthic habitats. This study demonstrates the premise of using underwater vehicles through unbiased means or pre-programmed path planning to quantify and estimate seafloor categories and the exhibited fine-scale biogeographic patterns.

Monitoring the evolution process of karst desertification and quantifying its drivers in the karst area of Southwest China - Wenli Liu; Liangliang Jiang; Bing Liu; Rui Liu; Zuolin Xiao (Environmental Science and Pollution Research, 2023)

The predictive, preventive, and personalized medicine of insomnia: gut microbiota and inflammation - Hao-Wen Chen; Rui Zhou; Bi-Fei Cao; Kuan Liu; Qi Zhong; Yi-Ning Huang; Hua-Min Liu; Jin-Qing Zhao; Xian-Bo Wu (EPMA Journal, 2023)

Evolution of tidal flats in the Yellow River Qingshuigou sub-delta: spatiotemporal analysis and mechanistic changes (1996-2021) - Yin Cao; Qing Wang; Chao Zhan; Rui Li; Zhangfan Qian; Longsheng Wang; Xianbin Liu; Jun Zhu; Hongyuan Shi; Yan Li (Frontiers in Marine Science, 2023)
The Yellow River Delta has undergone significant changes, developing a temperate chalk-sand silty coast with expansive and level tidal flats. However, the area is currently facing the threat of erosion due to coastal area construction, decreased river sediment discharge into the sea, and intensified marine hydrodynamic forces. Remote sensing technology has important applications in spatial and temporal monitoring of tidal flats. This study employs tidal data to establish the threshold range for the extraction of tidal flats in the Yellow River Qingshuigou sub-delta, using the water frequency method based on the image element proposed by previous authors. The study successfully identifies and analyzes the range of tidal flats, and further delves into their evolutionary process and underlying mechanisms. The study concludes that the area of tidal flats has shown a decreasing trend and was divided into a “rapid decline phase” and an “overall stabilization phase” with 2006 as the boundary. The spatial and temporal evolution of tidal flats is primarily influenced by three main factors: river sediment discharges, marine hydrodynamic forces, and anthropogenic reclamation activities. Specifically, the river sediment discharges and marine hydrodynamic forces impact the extent of tidal flats by modifying the boundary conditions, primarily at the sea boundary. Reclamation activities have a direct and rapid effect on the extent of tidal flats, primarily at the land boundary. In this study, we determined the contribution of three factors to the spatial and temporal evolution of tidal flats in different periods. During the two phases of the tidal flats’ spatial and temporal evolution in the Yellow River Qingshuigou sub-delta, the driving mechanisms were identified as “reclamation - marine hydrodynamic forces - river sediment discharges” and “marine hydrodynamic forces - river sediment discharges - reclamation”.

Two truxinate derivatives and a phenyldilactone from the leaves of Castanopsis eyrei - Ya-feng Wang; Nao Pang; Zhen-hua Liang; Yong-lin Huang; Rui-jie He; Bing-yuan Yang; Zhang-bin Liu (Natural Product Research, 2023)

Enhanced As extraction from paddy soils with high As contamination risk by rice plant upon Si fertilization - Rui Huang; Xin Wang; Wei Wei; Yunhe Xie; Saihua Liu; Haoyu Chen; Renjie Zhang; Xionghui Ji (Chemosphere, 2023)

Insights of microalgal municipal wastewater treatment at low temperatures: Performance, microbiota patterns, and cold-adaptation of tubular and aeration column photobioreactors - Jiansong Tian; Pan Li; Yajun Luo; Heng Yan; Jian Liu; Zhicheng Pan; Yangwu Chen; Rui Wang; Yiwei Cheng; Houzhen Zhou; Junjie Li; Xin Li; et al. (Chemosphere, 2023)

Aluminum soap nanoparticles-lignin powder form phase-selective gelator as an efficient sorbent for oils/water separation - Suwan Cui; Bohao Qi; Hao Liu; Xiaojun Sun; Rui He; Junshuai Lian; Yiming Li; Jinren Lu; Mutai Bao (Chemosphere, 2023)

Heavy metal pollution alters reproductive performance and mate choice in an anuran, Strauchbufo raddei - Rui Su; Rui Guo; Zhenyu Liu; Yongna Yuan; Wenya Zhang (Marine Pollution Bulletin, 2023)

New perspective into possible mechanism in growth promotion of potassium diformate (KDF) on the juvenile grass carp (Ctenopharyngodon idella) - Xue Xue; Xiao-Qiu Zhou; Pei Wu; Wei-Dan Jiang; Yang Liu; Rui-Nan Zhang; Lin Feng (Aquaculture, 2023)

Dynamic assessment of population exposure to traffic-originated PM2.5 based on multisource geo-spatial data - Hui Zhong; Rui Xu; Hongliang Lu; Yonghong Liu; Meixin Zhu (Transportation Research Part D: Transport and Environment, 2023)

Subchronic exposure to di-(2-ethylhexyl) phthalate (DEHP) elicits blood–brain barrier dysfunction and neuroinflammation in male C57BL/6J mice - Wen-qiang Ren; Nuo Liu; Yan Shen; Xian-yan Wang; Qiong Zhou; Chen Rui; Xiao-han Yang; Sheng-long Cao; Ling-yu Li; Yán Wāng; Qu-nan Wang (Toxicology, 2023)

Efficient numerical implementation for nonlinear analysis of pile-supported structures during soil liquefaction through adaptive pile element formulations - Weihang Ouyang; An-Rui Liang; Si-Wei Liu (Soil Dynamics and Earthquake Engineering, 2023)

Thermokarst lake susceptibility assessment using machine learning models in permafrost landscapes of the Arctic - Rui Wang; Lanlan Guo; Yuting Yang; Hao Zheng; Hong Jia; Baijian Diao; Hang Li; Jifu Liu (Science of The Total Environment, 2023)

Distribution, sources, and potential health risks of fluoride, total iodine, and nitrate in rural drinking water sources of North and East China - Shier Huang; Jiaxun Guo; Yu Xie; Rui Bian; Nan Wang; Weixiao Qi; Huijuan Liu (Science of The Total Environment, 2023)

Releasing mechanism of ammonium during clayey sediments compaction and its impact on groundwater environment - Rui Liu; Juan Chen; Teng Ma (Science of The Total Environment, 2023)

Glyphosate-based herbicide (GBH) challenged thermoregulation in lizards (Eremias argus), compensatory warming could mitigate this effect - Simin Yu; Yufan Nie; Zikang Wang; Luyao Zhang; Rui Liu; Yuping Liu; Hongjun Zhang; Wentao Zhu; Mingqi Zheng; Jinling Diao (Science of The Total Environment, 2023)

PM1 exposure and spatial transmission of nicotine from the simulated second-hand vapor of pod-based electronic cigarettes - Tong Cui; Rui Lu; Qianyun Liu; Xingtao Jiang; Yanpeng Li; Song Pan (Science of The Total Environment, 2023)

Cleanable natural-sugar-alcohol-based polyester membrane for highly efficient molecular separation - Xiongwei Luo; Yue Wang; Yaoli Guo; Qieyuan Gao; Rui Zhao; Yanyan Liu; Riri Liu; Lei Jiang; Zhaohuan Mai; Hideto Matsuyama; Pengrui Jin (Resources, Conservation and Recycling, 2023)

A novel 1T-2H MoS2/NaBi(MoO4)2 alternating-phase piezoelectric composites for high-efficient ultrasound-drived piezoelectric catalytic removal of Sildenafil - Qing-rui Zeng; Zi-ang Jia; Xu Liu; Jin-ping Cheng (Process Safety and Environmental Protection, 2023)

Experimental and numerical research on the viscous flow field induced by a swing plate - Rui Deng; Hailong Liu; Xiaoyue Mo; Xiang Yu; Tiecheng Wu; Yulong Li (Ocean Engineering, 2023)

Carboniferous-Permian high-resolution conodont biostratigraphy and paleoclimate change in North China - Yuan Wang; Jianghai Yang; Charles M. Henderson; Dongxun Yuan; Rui Ma; Jia Liu (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

TBtools-II: A “one for all, all for one” bioinformatics platform for biological big-data mining - Chengjie Chen; Ya Wu; Jiawei Li; Xiao Wang; Zaohai Zeng; Jing Xu; Yuanlong Liu; Junting Feng; Hao Chen; Yehua He; Rui Xia (Molecular Plant, 2023)

Dietary oregano essential oil supplementation alters meat quality, oxidative stability, and fatty acid profiles of beef cattle - Pengjia He; Yu Lei; Ke Zhang; Rui Zhang; Yunpeng Bai; Zeming Li; Li Jia; Jinping Shi; Qiang Cheng; Yannan Ma; Xiaoqiang Zhang; Lishan Liu; et al. (Meat Science, 2023)

Microscopic mechanism of the combined effects of confining pressure and fines content on suffusion in gap-graded underfilled soils - Leilei Liu; Rui Chen; Chao Zhou; Xiaojiao Li; Bate Bate (Journal of Hydrology, 2023)

Unveiling the pollution and risk of atmospheric (gaseous and particulate) polycyclic aromatic hydrocarbons (PAHs) in a heavily polluted Chinese city: A multi-site observation research - Tao Wang; Luyao Zhang; Pei Zhang; Guangyuan Yu; Chong Chen; Xiaofei Qin; Guochen Wang; Xiansheng Liu; Rui Li; Liwu Zhang; Zhonghuan Xia (Journal of Cleaner Production, 2023)

Surface reconstruction of copper foil via electrochemical etching to proliferate CH4 production from CO2 electroreduction - Weicong Xu; Chao Liu; Peijun Li; Hongyun Zeng; Xianjun Lu; Xinyu Li; Tao Li; Rui Xiao (Journal of Cleaner Production, 2023)

Influence of urban extent discrepancy on the estimation of surface urban heat island intensity: A global-scale assessment in 892 cities - Qiquan Yang; Yi Xu; Xiaohua Tong; Ting Hu; Yue Liu; T.C. Chakraborty; Rui Yao; Changjiang Xiao; Shurui Chen; Zonghan Ma (Journal of Cleaner Production, 2023)

Mechanistic insight into the hydrogen transfer pathway for selective upcycling of PET to arenes - Huiyu Liu; Jun Zhang; Jing Gu; Rui Shan; Haoran Yuan; Yong Chen (Journal of Cleaner Production, 2023)

Assessment of cruise ship decarbonization potential with alternative fuels based on MILP model and cabin space limitation - Wenxian Zhang; Yuan He; Nianyuan Wu; Fuzheng Zhang; Danni Lu; Zekun Liu; Rui Jing; Yingru Zhao (Journal of Cleaner Production, 2023)

Widely targeted metabolomics provides insights into the effect of parboiling treatment on the nutritional quality of black rice based on its improved cooking characteristics - Xin Wu; Xingxing Zhang; Min Liu; Tang Tang; Yanhua Li; Hao Chen; Qun Lu; Rui Liu (Journal of Cereal Science, 2023)

Speciation and gas-liquid equilibrium study of CO2 absorption in aqueous MEA-DEEA blends - Rui Zhang; Haonan Liu; Ruixi Liu; Yingjie Niu; Luning Yang; Francesco Barzagli; Chao'en Li; Min Xiao (Gas Science and Engineering, 2023)

Pyrolysis of different types of waste cooking oil in the presence/absence HZSM-5 catalyst: Influence of feedstock characteristics on aromatic formation - Yuanyuan Wang; Yuan Zeng; Liangliang Fan; Qiuhao Wu; Letian Zhang; Jianyun Xiong; Jiahui Zhang; Rui Liao; Kirk Cobb; Yuhuan Liu; Roger Ruan; Yunpu Wang (Fuel, 2023)

Peanut skin procyanidins reduce intestinal glucose transport protein expression, regulate serum metabolites and ameliorate hyperglycemia in diabetic mice - Min Liu; Jinxin Shen; Xiaoling Zhu; Tingting Ju; Benjamin P. Willing; Xin Wu; Qun Lu; Rui Liu (Food Research International, 2023)

Sensory-directed isolation and identification of an intense salicin-like bitter compound in infected teas with bird’s eye spot disease - Jingna Yan; Yiwen Miao; Jingyun Zhou; Rui Huang; Hongwei Dai; Ming Liu; Yunzhi Lin; Yingjuan Chen; Chi-Tang Ho; Huarong Tong; Qing Meng (Food Research International, 2023)

Selenium speciation and volatile flavor compound profiles in the edible flowers, stems, and leaves of selenium-hyperaccumulating vegetable Cardamine violifolia - Yan Ma; Jinjing Yin; Jingyi Wang; Xin Liu; Jingren He; Rui Zhang; Shen Rao; Xin Cong; Yin Xiong; Muci Wu (Food Chemistry, 2023)

Quantitative proteomics analysis on the meat quality of processed pale, soft, and exudative (PSE)-like broiler pectoralis major by different heating methods - Tianyi Yang; Yamin Yang; Peng Zhang; Weitao Li; Qingfeng Ge; Hai Yu; Mangang Wu; Lidong Xing; Zhiyu Qian; Fan Gao; Rui Liu (Food Chemistry, 2023)

Hydrophobic aggregation via partial Gal removal affects solution characteristics and fine structure of tamarind kernel polysaccharides - Rui Guo; Xianbao Sun; Yuxing Kou; Hong Song; Xujiao Li; Lihua Song; Taolei Zhao; Hui Zhang; Deshun Li; Yanfang Liu; Zibo Song; Jieli Wu; et al. (Food Hydrocolloids, 2023)

Inactivation of Alicyclobacillus spp. in apple juice by pulsed light and the analysis of its mechanisms - Yali Ma; Qi Wang; Wanyu Shen; Yingying Liu; Lige Qi; Jiandong Xiao; Rui Cai; Tianli Yue; Zhouli Wang (Food Control, 2023)

Synergetic effect on fouling alleviating of membrane distillation in urine resource recovery by thermally activated peroxydisulfate pretreatment - Yaping Lyu; Xiuwei Ao; Zongsu Wei; Shikun Cheng; Xiaoqin Zhou; Nana Liu; Xuemei Wang; Rui Feng; Zifu Li (Environmental Research, 2023)

Reducing airborne transmission of SARS-CoV-2 by an upper-room ultraviolet germicidal irradiation system in a hospital isolation environment - Haiyang Liu; Zhijian Liu; Junzhou He; Chenxing Hu; Rui Rong; Hao Han; Lingyun Wang; Desheng Wang (Environmental Research, 2023)

A review of the toxic effects of ammonia on invertebrates in aquatic environments - Tian-Xu Zhang; Ming-Rui Li; Chen Liu; Shu-Ping Wang; Zhen-Guang Yan (Environmental Pollution, 2023)

Early clues and molecular mechanism involved in neurodegenerative diseases induced in immature mice by combined exposure to polypropylene microplastics and DEHP - Ge Yang; Cunyi Gong; Xinyue Zheng; Fei Hu; Jie Liu; Tian Wang; Xinyue Chen; Min Li; Zhihong Zhu; Ling Zhang; Rui Li (Environmental Pollution, 2023)

Occurrences of typical PPCPs during wastewater treatment and the composting of sewage sludge with micron-sized and nano-sized Fe3O4 - Jishao Jiang; Rui Hou; Huilin Cui; Dong Liu; Guangxuan Yan; Yujuan Fan; Ke Cheng; Zhiguo Cao (Environmental Pollution, 2023)

Corrigendum to “Combining functional physiological phenotyping and simulation model to estimate dynamic water use efficiency and infer transpiration sensitivity traits” [Eur. J. Agron. 150 (2023) 126955] - Ting Sun; Rui Cheng; Rujia Jiang; Yunxiu Liu; Yudong Sun; Zhuoyi Wang; Pingping Fang; Xinyang Wu; Kang Ning; Pei Xu (European Journal of Agronomy, 2023)

Contrasting riverine K and Li isotope signatures during silicate weathering in the southeastern Tibetan Plateau - Xiaoqiang Li; Guilin Han; Qian Zhang; Jinke Liu; Rui Qu (Earth and Planetary Science Letters, 2023)

Epithelial lining inspired protective shield for prolonged endotracheal intubation - Baisong Zhao; Meng-Han Bai; Luxi Zhang; Qingning Wang; Yongying Pan; Yan-Pu Li; Rui Hong; Juxiang Gou; Dongjie Zhang; Yuwei Liu; Gan-Ji Zhong; Ka Li; et al. (Chemical Engineering Journal, 2023)

New insight into opposite oxidation behavior in acetone and propane catalytic oxidation over CoMn based spinel oxides - Cangpeng Shan; Yan Zhang; Qian Zhao; Jianbo Li; Yunchong Wang; Rui Han; Caixia Liu; Qingling Liu (Chemical Engineering Journal, 2023)

Bio-inspired microvascular patches with MSC encapsulation for wound healing - Rui Liu; Bin Kong; Jingjing Gan; Yuanjin Zhao; Lingyun Sun (Chemical Engineering Journal, 2023)

ZIF-derived Fe,Co coordinated N/O-codoped three-dimensional tungsten–carbon matrix for the performance-enhanced zinc-air flow battery and water splitting - Jinling Xue; Zhipeng Liu; Yibin Fan; Rui Wang; Yinshi Li (Chemical Engineering Journal, 2023)

Surface engineered long-lasting antibacterial Janus cotton fabrics with excellent moisture/thermal management properties - Lujie Wang; Maoshuang Chen; Rui Cai; Jingjing Jiang; Shuangfei Xiang; Xiangdong Liu; Hongyan Diao (Chemical Engineering Journal, 2023)

Demethylation-Driven ligase chain reaction for simultaneously sensitive detection of m6A demethylase FTO and m1A demethylase ALKBH3 in breast cancer at Single-Molecule level - Ming-hao Liu; Qian Zhang; Wan-tong Yu; Jian-Ge Qiu; Hui-min Yuan; Chuan-rui Wang; Bing-Hua Jiang; Yan Zhang; Chun-yang Zhang (Chemical Engineering Journal, 2023)

Efficient antibiotic wastewater treatment via interfacial water evaporation based soot-coated conjugated microporous polymer hollow microspheres - Wenwen Luo; Meichen Liu; Rui Jiao; Yunjia Wang; Jiyan Li; Zhaoqi Zhu; Weidong Liang; Hanxue Sun; An Li (Chemical Engineering Journal, 2023)

Enhancing biomass oxidation with carbon nitride nanosheets ring inserted on C. I. Pigment Yellow 53 photocatalysts for simultaneous CO and lactic acid production - Weikang Ling; Jiliang Ma; Zhendong Liu; Rui Cui; Junqiang Zhang; Xinze Li; Min Hong; Runcang Sun (Chemical Engineering Journal, 2023)

Transient, printable and recyclable gelatin hydrogels with enhanced mechanical sensing and electromagnetic shielding performance by incorporation of reduced graphene oxide - Rui Yin; Chen Zhang; Youyou Chen; Yu Wang; Qiang Feng; Yaming Liu; Minghan Yu; Yunhuan Yuan; Cheng-Yan Xu; Feihua Liu; Weiwei Zhao (Chemical Engineering Journal, 2023)

A novel efficient wet process for preparing cross-linked starch: Impact of urea on cross-linking performance - Yan Min; Jie Yi; Rui Dai; Wentao Liu; Hui Chen (Carbohydrate Polymers, 2023)

Unexpected moderate contribution of intermediate volatility organic compounds from gasoline vehicle emission to secondary organic aerosol formation in summer of Beijing - Rongzhi Tang; Song Guo; Quanyang Lu; Kai Song; Yuanzheng Gong; Rui Tan; Kefan Liu; Hui Wang; Ying Yu; Ruizhe Shen; Shiyi Chen; Limin Zeng; et al. (Atmospheric Research, 2023)

Using Ribonucleoprotein-based CRISPR/Cas9 to Edit Single Nucleotide on Human Induced Pluripotent Stem Cells to Model Type 3 Long QT Syndrome (SCN5A±) - Ning Ge; Min Liu; Rui Li; Nicholas M. Allen; Joseph Galvin; Sanbing Shen; Timothy O’Brien; Terence W. Prendiville (Stem Cell Reviews and Reports, 2023)
Human induced pluripotent stem cells (hiPSCs) have been widely used in cardiac disease modelling, drug discovery, and regenerative medicine as they can be differentiated into patient-specific cardiomyocytes. Long QT syndrome type 3 (LQT3) is one of the more malignant congenital long QT syndrome (LQTS) variants with an SCN5A gain-of-function effect on the gated sodium channel. Moreover, the predominant pathogenic variants in LQTS genes are single nucleotide substitutions (missense) and small insertion/deletions (INDEL). CRISPR/Cas9 genome editing has been utilised to create isogenic hiPSCs to control for an identical genetic background and to isolate the pathogenicity of a single nucleotide change. In this study, we described an optimized and rapid protocol to introduce a heterozygous LQT3-specific variant into healthy control hiPSCs using ribonucleoprotein (RNP) and single-stranded oligonucleotide (ssODN). Based on this protocol, we successfully screened hiPSCs carrying a heterozygous LQT3 pathogenic variant ( SCN5A ± ) with high efficiency (6 out of 69) and confirmed no off-target effect, normal karyotype, high alkaline phosphatase activity, unaffected pluripotency, and in vitro embryonic body formation capacity within 2 weeks. In addition, we also provide protocols to robustly differentiate hiPSCs into cardiomyocytes and evaluate the electrophysiological characteristics using Multi-electrode Array. This protocol is also applicable to introduce and/or correct other disease-specific variants into hiPSCs for future pharmacological screening and gene therapeutic development. Graphical Abstract

Linear relationship between CH4 fluxes and atmospheric CO2 concentration levels controlled by rice biomass and soil methanogenic communities - Yuanyuan Wang; Zhenghua Hu; Shuqi He; Qiang Jing; Lidong Shen; Chao Liu; Zhurong Wu; Wei Huang; Guihua Lu; Rui Cao; Kezhi Zheng; Ning Dong; et al. (Nutrient Cycling in Agroecosystems, 2023)

Reduced attention on restricted organochlorine pesticides, whereas still noteworthy of the impact on the deep soil and groundwater: a historical site study in southern China - Changlin Xu; Yue Cai; Rui Wang; Jing Wu; Guoyi Yang; Yahui Lv; Dehong Liu; Yu Deng; Yaqi Zhu; Qing Zhang; Lijun Wang; Shengwei Zhang (Environmental Geochemistry and Health, 2023)

Glutathione Might Attenuate Arsenic-Induced Liver Injury by Modulating the Foxa2-XIAP Axis to Reduce Oxidative Stress and Mitochondrial Apoptosis - Hua Zhang; Baiming Jin; Lele Liu; Haonan Li; Xiujuan Zheng; Mingqi Li; Rui He; Kewei Wang (Biological Trace Element Research, 2023)

Human amnion-derived mesenchymal stem cells improve subclinical hypothyroidism by immunocompetence mediating apoptosis inhibition on thyroid cells in aged mice - Chuyu Li; Qiang Rui; Xiaohan Dong; Song Ning; Jing Zhou; Huimin Wu; Chunyan Jiang; Yugui Cui; Jiayin Liu; Jun Jiang; Lianju Qin (Cell and Tissue Research, 2023)
Subclinical hypothyroidism (SCH) affects 10% of the global population, which is most prevalent in women and the elderly. However, it remains debatable whether the elderly with subclinical hypothyroidism needs thyroxine supplement. Human amnion-derived mesenchymal stem cells (hAMSCs) could play important roles in autoimmune diseases, suggesting that hAMSC be a candidate to regulate the thyroid function of female age-related subclinical hypothyroidism. Herein, we established the model of SCH in the aged female mice. This study was designed to investigate whether human amnion-derived mesenchymal stem cells (hAMSC) could effect on immune regulation, apoptosis inhibition of thyroid cells, thyroid function, blood lipid levels, and heart function. In addition, qualified hAMSCs were intravenously injected into aged female SCH mice via the tail vein on day 0 and day 10. The levels of thyroid hormone and blood lipids as well as cardiac function, serum immunological indexes, and apoptosis of thyroid cells were then analyzed on day 5, 10, 15, and 20; meanwhile, the quantity of Th1, Th2, Th17, and Treg immune cells in peripheral blood was evaluated before and on day 20 post-injection. Our study demonstrated that after hAMSC transplantation, the thyroid functions, blood lipid levels, and heart function indexes of age-related SCH (AR-SCH) mice were significantly improved. Consistent with this, Th1 and Treg cells increased significantly, while Th2 and Th17 cells decreased in peripheral blood. Apoptosis was also suppressed in the thyroid cells. In summary, hAMSC delivery can potentially be a safe and effective therapy for treating SCH in the elderly, improving related complications by immunomodulatory and apoptosis inhibition.

Benchmarking FFTF LOFWOS Test# 13 using SAM code: Baseline model development and uncertainty quantification - Yang Liu; Travis Mui; Ziyu Xie; Rui Hu (Annals of Nuclear Energy, 2023)

Enzymatic DNA repairing amplification-powered construction of an Au nanoparticle-based nanosensor for single-molecule monitoring of cytosine deaminase activity in cancer cells - Wen-jing Liu; Rui Song; Xiao-ran Zou; Dong-ling Li; Qinfeng Xu; Chun-yang Zhang (Analytica Chimica Acta, 2023)

Portable multichannel detection instrument based on time-resolved fluorescence immunochromatographic test strip for on-site detecting pesticide residues in vegetables - Rui Xu; Yaodong Xiang; Zheng Shen; Gaozhen Li; Jiashuai Sun; Peiyu Lin; Xiaofeng Chen; Jingcheng Huang; Haowei Dong; Zhenying He; Wenzheng Liu; Lu Zhang; et al. (Analytica Chimica Acta, 2023)

Meta-analytic and experimental evidence that warmer climate leads to shift from advanced to delayed spring phenology - Jing Guo; Qimei Ma; Hanfeng Xu; Yue Luo; Dashan He; Fucheng Wang; Jiasheng Wu; Yongshuo H. Fu; Jianquan Liu; Rui Zhang; Lei Chen (Agricultural and Forest Meteorology, 2023)

Health benefits of traffic-related PM2.5 and CO reduction—a case study of Tianjin, China, from 2015 to 2019 - Yunqian Chen; Zheng Ran; Ya-nan Wang; Xiaoping Liu; Pu Yang; Kun Han; Xiaoge Yin; Chao Zou; Rui Wu; Hongjun Mao; Taosheng Jin (Air Quality, Atmosphere & Health, 2023)

Geological resources of scandium: a review from a Chinese perspective - Shang Liu; Hong-Rui Fan; M. Santosh; Xuan Liu; Qi-Wei Wang; Alan R. Butcher (International Geology Review, 2023)

The Effect of Water Spinach on the Water Quality, Antioxidant System, Non-Specific Immune Response, Growth Performance, and Carbon Balance in Red Tilapia Production - Yuan-Yuan Luo; Xian-Can Chen; Rui-Lin Xie; Zhuo-Hao Ruan; Zhi-Qiang Lu; Liang-Sen Jiang; Yi-Fu Li; Wen-Sheng Liu (Fishes, 2023)
In this study, the compound aquaculture model of red tilapia (O. mossambicus albina × O. urolepis hornorum) and water spinach (Ipomoea aquatica) was used to investigate the effect of water spinach rafts on the water quality, antioxidant system, non-specific immune response, and growth performance of red tilapia and the carbon balance of payments. Red tilapia is characterized by its high adaptability to different production environments and food sources, as one of the most productive fish in aquaculture, and is well accepted in the market due to its nutritional and organoleptic characteristics. The experiment lasted for nine weeks and included two systems: the red tilapia-water spinach raft aquaponics (AP) system with 10% cover ratio with water spinach floating beds, and the aquatic monoculture (AM) system with only red tilapia. The total phosphorus (TP), total nitrogen (TN), and nitrate nitrogen (NO−3-N) in the AM were higher than those in AP from the fifth to ninth week. On the second, third, fifth, and sixth weeks, the ammonia nitrogen (NH4+-N), in the AM was higher than those in the AP. From the seventh week, the pH of the AM was significantly lower than the AP, while the nitrite nitrogen (NO−2-N) was significantly higher than the AP. The water quality index of the AP was better than that of the AM, indicating that water spinach can remove the nutrients from aquaculture water bodies. The average daily gain and specific growth rate (SGR) of fish in AP were higher than those in the AM. The acid phosphatase (ACP), alkaline phosphatase (AKP), and catalase (CAT) activities in the hepatopancreas of red tilapia in the AP were also significantly higher than those in the AM, while the malondialdehyde (MDA) in the AP was lower than the AM. The serum ACP and CAT of red tilapia in the AP were also higher than those in the AM, while the MDA of fish in the AP was lower than the AM. The results showed that both the experimental group and the control group were carbon sources and released greenhouse gases into the atmosphere, but the total carbon emissions of the red tilapia and the water spinach symbiotic system in the experimental group was significantly lower than that of the control group (p

The regulative effect and repercussion of probiotics and prebiotics on osteoporosis: involvement of brain-gut-bone axis - Yuan-Wei Zhang; Mu-Min Cao; Ying-Juan Li; Guang-Chun Dai; Pan-Pan Lu; Ming Zhang; Li-Yong Bai; Xiang-Xu Chen; Cheng Zhang; Liu Shi; Yun-Feng Rui (Critical Reviews in Food Science and Nutrition, 2023)

Analysis of spatial and temporal variation of vegetation NPP in Daning River Basin and its driving forces - Wenqian Bai; Li He; Zhengwei He; Xueman Wang; Yang Zhao; Rui Qu; Fang Luo; Xin Chen; Zhifei Wang; Ming Liu (International Journal of Remote Sensing, 2023)

Rape straw biochar enhanced Cd immobilization in flooded paddy soil by promoting Fe and sulfur transformation - Rui Yuan; Tianren Si; Qingquan Lu; Rongjun Bian; Yan Wang; Xiaoyu Liu; Xuhui Zhang; Jufeng Zheng; Kun Cheng; Stephen Joseph; Lianqing Li; Genxing Pan (Chemosphere, 2023)

Rapid, stable, and highly-efficient development of salt-tolerant aerobic granular sludge by inoculating magnetite-assisted mycelial pellets - Xushen Han; Rui Tang; Changshen Liu; Jingxue Yue; Yan Jin; Jianguo Yu (Chemosphere, 2023)

Photocatalytic activity of TiO2-ZnO/g-C3N4 nanocomposites for methylene orange and Rhodamine B dyes removal from water and photocatalytic hydrogen generation - Jieying Liu; Yong Gao; Zhifang Zhang; Rui Dang; Rima Nour El Houda Tiri; MuhammedBekmezci; Ramazan Bayat; Rozhin Darabi; Fatih Sen (Chemosphere, 2023)

Illustration on phenotypic and genotypic characteristics of typical multi-antibiotic resistant bacteria in aquatic environments through complete genomes and comparative genomics - Chunli Wan; Rui Tang; Liyan Deng; Liya Fu; Panxin Wang; Xiang Liu; Changyong Wu (Chemosphere, 2023)

Nonthermal plasma coupled with liquid-phase UV/Fe–C for chlorobenzene removal - Caihong Qin; Chaochao Jiang; Rongrong Liu; Jiayu Huang; Rui Yu; Peng Zhang (Chemosphere, 2023)

YOLOv5s-CBAM-DMLHead: A lightweight identification algorithm for weedy rice (Oryza sativa f. spontanea) based on improved YOLOv5 - Chuangchuang Yuan; Tonghai Liu; Fangyu Gao; Rui Zhang; Xiaoyue Seng (Crop Protection, 2023)

The evolution of insecticide resistance in the white backed planthopper Sogatella furcifera (Horvath) of China in the period 2014–2022 - Ya-Ting Liu; Xin-Yu Song; Bin Zeng; Wen-Jing Zhang; Xing-Yu Chen; Ze-Rui Feng; Hua-Yang Yu; Cong-Fen Gao; Shun-Fan Wu (Crop Protection, 2023)

Legacy per- and polyfluoroalkyl substances (PFASs) especially alternative PFASs in shellfish from Shandong Province, China: Distribution, sources, and health risk - Jiacheng Zhang; Wei Li; Luping Yang; Zunhua Chu; Yanni Jiao; Lin Wang; Lijun Zhu; Chuan Qin; Rui Liu; Xibao Gao (Marine Pollution Bulletin, 2023)

Application of enzymatically treated Artemisia annua L. on adult grass carp (Ctenopharyngodon idella): Improved growth performance, intestinal antioxidant capacity and apical junctional complex - Qin-Qin Dai; Xiao-Qiu Zhou; Wei-Dan Jiang; Pei Wu; Yang Liu; He-Qun Shi; Lu Zhang; Hai-Feng Mi; Jia-Yong Tang; Rui-Nan Zhang; Lin Feng (Aquaculture, 2023)

Ammonia-oxidizing bacteria are the primary N2O producers in long-time tillage and fertilization of dryland calcareous soil - Ju Bai; Yang Li; Wei Zhang; Lixia Liu; Rui Wang; Zijian Qiu; Yuwang Liu; Qiuxia Meng; Qiang Zhang; Zhiping Yang; Shiqing Li; Yongliang Wang; et al. (Soil and Tillage Research, 2023)

Vertical distribution and transport of microplastics in the urban atmosphere: New insights from field observations - Zhen Yuan; Cheng-Lei Pei; Heng-Xiang Li; Lang Lin; Rui Hou; Shan Liu; Kai Zhang; Ming-Gang Cai; Xiang-Rong Xu (Science of The Total Environment, 2023)

Funneliformis mosseae influences leaf decomposition by altering microbial communities under saline-alkali conditions - Hui Liu; Jiazhen Zhang; Luying Zhang; Xi Zhang; Rui Yang (Science of The Total Environment, 2023)

Insight into the effect of a heavy metal mixture on neurological damage in rats through combined serum metabolomic and brain proteomic analyses - Jie Xie; Fankun Zhou; Lu Ouyang; Qi Li; Shaoqi Rao; Rui Su; Shuo Yang; Jiajun Li; Xin Wan; Lingyu Yan; Peishan Liu; Hui Cheng; et al. (Science of The Total Environment, 2023)

Hydrogeological controls on chromium enrichment along the groundwater flow path in the Baiyangdian Catchment, North China Plain - Chao Liu; Huaming Guo; Wendi Fan; Rui Xu; Shuangbao Han; Bingying Gao; Bo Zhao; Chunping Jiang (Science of The Total Environment, 2023)

Diversity and function of mountain and polar supraglacial DNA viruses - Yongqin Liu; Nianzhi Jiao; Kevin Xu Zhong; Lin Zang; Rui Zhang; Xiang Xiao; Yi Shi; Zhihao Zhang; Ye Tao; Liping Bai; Bianli Gao; Yunlan Yang; et al. (Science Bulletin, 2023)

Transmission to green economic development and the dependence on natural resources in China - Rui Ma; Xiao qin Xie; Bin Liu; Fengjiao Zhou; Mohamad Shaharudin bin Samsurijan (Resources Policy, 2023)

Dynamic simulation and control strategy exploration of the unsafe behavior of coal mine employees - Wanzhen Li; Lujie Zhou; Jian Hao; Kai Yu; Jing Chen; Pingping Liu; Rui Feng (Resources Policy, 2023)

Evaluation of sustainable development efficiency in Chinese provinces- based on closed-loop feedback three-stage dynamic network slack-based measure model - Yanyong Hu; Rui Zhang; Jiaxi Wu; Xiaotong Qie; Hong Liu (Process Safety and Environmental Protection, 2023)

Anti-inflammatory metabolites from the fruits of Pittosporum elevaticostatum - Jun-Rui Ren; Xin-Zheng Liu; Wei-Zhen Kong; Zhao-Xuan Wang; Jin-Ming Gao; Xiu-Yun Zhang (Phytochemistry Letters, 2023)

Energy optimal depth control for multimodal underwater vehicles with a high accuracy buoyancy actuated system - Junjun Cao; Rui Lin; Chunhu Liu; Hao Feng; Caoyang Yu; Baoheng Yao; Lian Lian (Ocean Engineering, 2023)

Dynamic modeling and switching analysis of all-attitude multimode underwater vehicle for multidimensional data acquisition - Rui Lin; Junjun Cao; Jialuan Xiao; Caoyang Yu; Chunhu Liu; Baoheng Yao; Lian Lian (Ocean Engineering, 2023)

Review on fault-tolerant control of unmanned underwater vehicles - Fuqiang Liu; Zuxing Ma; Bingxian Mu; Chaoqun Duan; Rui Chen; Yi Qin; Huayan Pu; Jun Luo (Ocean Engineering, 2023)

Experimental study on rock breaking by single chisel pick under deep-sea hydrostatic pressure - Zenghui Liu; Rui Lv; Chunyan Kong; Kai Liu; Changyun Wei (Ocean Engineering, 2023)

Synthesis and flotation performance of a novel low-foam viscous cationic collector based on hematite reverse flotation desilication system - Weichao Li; Wenbao Liu; Kelin Tong; Wengang Liu; Panxing Zhao; Rui Ding (Minerals Engineering, 2023)

Analysis of the contribution of land consolidation to sustainable poverty alleviation under various natural conditions - Hanbing Li; Xiaobin Jin; Barbara Prack McCormick; Pablo Tittonell; Jing Liu; Bo Han; Rui Sun; Yinkang Zhou (Land Use Policy, 2023)

Rare-metal Be–Nb–Ta mineralisation by pegmatite remelting: Insights from Dakalasu deposit in the Chinese Altai orogenic belt - Siyu Liu; Rui Wang; Shuang Yang; Liangliang Zhang; Zhongli Zhang (Lithos, 2023)

PANI grafted onto waste poros polyurethane for co-adsorption of multiple pollutants in industrial wastewater - Ning Wang; Yirui Guo; Yi Song; Wei Yan; Xuesong Gong; Yunfeng Li; Rui hua Mu; Yonghong Liu; Luohong Zhang (Journal of Water Process Engineering, 2023)

Contamination profile and risk assessment of per- and polyfluoroalkyl substances in Guanting Reservoir, a former drinking water source with degraded water quality - Tong Qi; Rui Guo; Shuai Ding; Chengyou Liu; Xue Li; Xiaocui Qiao; Yan Liu (Journal of Water Process Engineering, 2023)

Effects of multi-frequency ultrasound on inactivating Chironomus kiiensis eggs: Evidence from a case study in drinking water treatment plant - Hai-guang Yuan; Rui-jian Zhang; Ye-qin Xu; Zhi Dang; Yong Hu; Qian-Bin Wang; Hao-tao Dong; Jia-xin Liu; Shu-juan Pu; Zhi-li Du; Ying-shi Liu; Zong-jia Zhang (Journal of Water Process Engineering, 2023)

CuFe2O4/penicillin residue biochar heterogeneous Fenton-like catalyst used in the treatment of antibiotic wastewater: Synthesis, performance and working mechanism - Zaixing Li; Rui Liu; Wei Gao; Wenjing Zhang; Chao Li; Xiaoshuai Liu; Nannan Wang (Journal of Water Process Engineering, 2023)

Melt-blown fiber felt for efficient all-weather recovery of viscous oil spills by Joule heating and photothermal effect - Bohao Qi; Nuo Wang; Xin Hu; Suwan Cui; Hao Liu; Rui He; Junshuai Lian; Yiming Li; Jinren Lu; Yang Li; Mutai Bao (Journal of Hazardous Materials, 2023)

Catalytic degradation of benzene at room temperature over FeN4O2 sites embedded in porous carbon - Hui Ding; Lingxiao Xue; Jiahao Cui; Yongqiang Wang; Dan Zhao; Xing Zhi; Rui Liu; Jianfeng Fu; Shejiang Liu; Bingfeng Fu; Jiahui Shi; Ximeng Xu; et al. (Journal of Hazardous Materials, 2023)

Hydrophilic magnetic Ti3C2Tx-based nanocomposite as an efficient boron adsorbent: Synthesis, characterization, and application - Juan Bao; Tingting Zhang; Shiying Wu; Lujie Li; Xianhuai Huang; Weihua Li; Chang Liu; Jiansheng Li; Rui Lu (Journal of Hazardous Materials, 2023)

Triazole fungicides exert neural differentiation alteration through H3K27me3 modifications: In vitro and in silico study - Tingting Ku; Xin Tan; Yutong Liu; Rui Wang; Lifan Fan; Zhihua Ren; Xia Ning; Guangke Li; Nan Sang (Journal of Hazardous Materials, 2023)

Association between urinary neonicotinoid insecticide levels and dyslipidemia risk: A cross-sectional study in Chinese community-dwelling elderly - Jian Sun; Pei He; Rui Wang; Zhong-Yuan Zhang; Yu-Qing Dai; Xiao-Yu Li; Si-Yu Duan; Cai-Ping Liu; Hao Hu; Guang-Jun Wang; Yan-Ping Zhang; Fei Xu; et al. (Journal of Hazardous Materials, 2023)

Bimodal interferences of Pb(II) induced by parallel deposition in Pb(II)-Cu(II) electrochemical detections: Voltammetric signals analysis combined with numerical simulations on transient interfacial phenomena - Rui-Ze Xia; Xin Cai; Bo Liang; Hai-Hua Dai; Yang-Zhi Liu; Meng Yang; Shi-Hua Chen; Pei-Hua Li; Xing-Jiu Huang (Journal of Hazardous Materials, 2023)

Experimental and simulation study on heat transfer performance of a high-concentrating photovoltaic system coupled with gravitational heat pipe - Haifei Chen; Huihan Yang; Yanyan Liu; Yonghui Shao; Rui Zou; Yunjie Wang (Journal of Cleaner Production, 2023)

Intramolecular engineering of defective terminations within triazine-based conjugated polymers for augmented photocatalytic H2 production and Cr(VI) reduction - Zhiquan Jin; Sijia Jin; Shuqi li; Rui Zou; Da Wang; Feilong Dong; Min Liu; Shuang Song; Tao Zeng (Journal of Cleaner Production, 2023)

Oxygen-exfoliated cobalt-doped C3N4 for superior Fenton-like catalysis: The accessible metal exposure and synergistic pollutant adsorption from three-dimensional layered configuration - Qi-Xin Wei; Ai-Yong Zhang; Zedong Yang; Song Hu; De-Jin Wang; Chi Zhang; Chang Liu; Rui Liu (Journal of Environmental Chemical Engineering, 2023)

Chloride removal from sewage using bismuth trioxide: Characterization and optimization by response surface methodology (RSM) - Liangjing Zhang; Yu Wang; Yunlong Liu; Shucong Lv; Rui Wang; Xiaokun Hu; Yuchen Liu; Zhaojun Dong; Kuixuan Lin; Lusan Liu (Journal of Environmental Chemical Engineering, 2023)

Boosting PFOA photocatalytic removal from water using highly adsorptive and sunlight-responsive ZIF67/MIL-100(Fe) modified C3N4 - Peidong Su; Chunhui Zhang; Yu Liu; Junke Zhang; Ridha Djellabi; Rui Wang; Junqiang Guo; Rui Zhang; Hongwei Guo; Xiang Ding; Xinyue Liu (Journal of Environmental Chemical Engineering, 2023)

Enhanced removal of sulfamethoxazole in soil by ball-milled Fe0-FeS@BC activated persulfate process - Rui Liu; Jin-yan Yang (Journal of Environmental Chemical Engineering, 2023)

Transport model simulation prediction and environmental risk assessment of pyrethroid insecticides in urban artificial lakes caused by rainfall: A case study of Cloud Mountain Park in subhumid climate zone - Siyao Liu; Xuanying Li; Rui Ding; Yuwen Pan; Xiaoyu Ge; Weifang Ma (Journal of Environmental Management, 2023)

Surface modification of PVDF membranes with quaternized chitosan for selective separation of negatively charged polysaccharides – exemplified with heparin - Rui Zhang; Yahong Li; Jingjing Yan; Jianxian Zeng; Yuan Liu; Mingming Zhang; Pengfei Liu; Xiaoping Huang; Erdong Zhang; Kaipeng Cheng; Jingyu Chen; Jialin Sun (Journal of Environmental Chemical Engineering, 2023)

Microbial resistance stability of rice straw biochar with vermiculite modification: A novel insight into persistent free radicals and pore structure - Yuxue Liu; Rui Wang; Lili He; Cunjun Li; Yuying Wang; Haohao Lu; Shengmao Yang (Journal of Environmental Chemical Engineering, 2023)

The metal-organic frameworks as unique platform for photocatalytic CO2 conversion to liquid fuels - Xiahong Xu; Kangle Xie; Junjie Hu; Suijun Liu; Hong Zhong; He-Rui Wen (Journal of Environmental Chemical Engineering, 2023)

Multiple stages of Au mobilization in the Changshagou Au deposit, Eastern Tianshan, NW China: Insights from mineral chemistry and fluid inclusions - Yi-Hao Liu; Yun Zhao; Chun-Ji Xue; Rui Wang; Hai-Xia Chu; Xiao-Bo Zhao; Matthew J. Brzozowski; Reimar Seltmann; Jun Chen; Jun-Bao Gao (Journal of Asian Earth Sciences, 2023)

Triassic convergence and tectonic evolution of the West Qinling orogen: Constraints from reflection-seismology imaging - Huilin Li; Rui Gao; Xingfu Huang; Haiyan Wang; Xiaoyu Guo; Hongda Liang; Xiaomiao Tan; Xiaohui Liu; Zhen Yang (Gondwana Research, 2023)

Oat bran prevents high-fat-diet induced muscular dysfunction, systemic inflammation and oxidative stress through reconstructing gut microbiome and circulating metabolome - Rui Dong; Kejie Peng; Lin Shi; Qianwen Niu; Hamad Rafique; Yuan Liu; Li Yuan; Liang Zou; Lu Li; Maria Cristina Messia; Xinzhong Hu (Food Research International, 2023)

The mixed-order chlorine decay model with an analytical solution and corresponding trihalomethane generation model in drinking water - Weinan Feng; Wencheng Ma; Qijia Zhao; Feiyu Li; Dan Zhong; Liming Deng; Yisong Zhu; Zhaopeng Li; Ziyi Zhou; Rui Wu; Luming Liu; Jun Ma (Environmental Pollution, 2023)

Combining functional physiological phenotyping and simulation model to estimate dynamic water use efficiency and infer transpiration sensitivity traits - Ting Sun; Rui Cheng; Rujia Jiang; Yunxiu Liu; Yudong Sun; Zhuoyi Wang; Pingping Fang; Xinyang Wu; Kang Ning; Pei Xu (European Journal of Agronomy, 2023)

Seismic and hydrological triggers for a complex cascading geohazard of the Tianmo Gully in the southeastern Tibetan Plateau - Rui Guo; Liming Jiang; Zhida Xu; Chao Li; Ronggang Huang; Zhiwei Zhou; Tao Li; Yi Liu; Hansheng Wang; Xuanmei Fan (Engineering Geology, 2023)

A non-Darcy flow CFD–DEM method for simulating ground collapse induced by leakage through underground pipeline defect - Xiaojiao Li; Rui Chen; Leilei Liu; Chao Zhou; Bate Bate (Computers and Geotechnics, 2023)

Hybrid tribo/piezoelectric nanogenerator textile derived from 3D interlocked parallel-arranged yarns for bio-motion energy harvesting and tactile sensing - Lin Liu; Yuantao Li; Muchun Xu; Rui Tao; Qiao Zhong; Xi Yang; Shixia Lan; Jiyang Xie; Guo Chen; Yongyun Mao; Wanbiao Hu (Chemical Engineering Journal, 2023)

Calcium-looping coupling methane partial oxidation and dry reforming process for integrated CO2 capture and conversion: Regulable H2/CO molar ratio and excellent coke deposition-resistant - Lifei Wei; Rui Han; Shuang Xing; Yang Wang; Zhiyong Li; Qingling Liu (Chemical Engineering Journal, 2023)

Controllable solvent treatment of fluorinated graphite for high power density and low cathode swelling lithium primary batteries - Sen Ma; Wen Liu; Daoming Zhang; Cheng Yang; Ying Luo; Xiaobing Lou; Rui Guo; Yong Wang; Jingying Xie (Chemical Engineering Journal, 2023)

QSPR models for sublimation enthalpy of energetic compounds - Rui Liu; Yuechuan Tang; Jie Tian; Jing Huang; Chaoyang Zhang; Linyuan Wang; Jian Liu (Chemical Engineering Journal, 2023)

Renewable biocrude blends boost tribological properties and maintain fuel performance of diesel - Maojiong Cao; Yingxian Wang; Hugang Li; Jixiu Jia; Rui Li; Zhidan Liu (Chemical Engineering Journal, 2023)

Space charge region induced self-evolution dehydrogenation of polymorphic magnesium-based hydrides - Qinke Tang; Jiangchuan Liu; Mengran Li; Rui Shi; Yunfeng Zhu; Yao Zhang; Jiguang Zhang; Yana Liu; Yijin Wu; Ling Li; Xiaohui Hu; Liquan Li (Chemical Engineering Journal, 2023)

ZIF-8-derived hollow carbon polyhedra with highly accessible single Mn-N6 sites as peroxymonosulfate activators for efficient sulfamethoxazole degradation - Yue Zhao; Rui Gao; He Wang; Yanping Sun; Xiaohui Zhan; Lei Chen; Junyan Liu; Huixiang Shi (Chemical Engineering Journal, 2023)

Selective electrocatalytic reforming of PET-derived ethylene glycol to formate with a Faraday efficiency of 93.2% at industrial-level current densities - Kesheng Liu; Yuxiang Wang; Fulai Liu; Chuxuan Liu; Rui Shi; Yong Chen (Chemical Engineering Journal, 2023)

Intrinsic reaction selectivity between gaseous HCl and SO2 over ethanol-hydrated CaO adsorbent in coal-fired flue gas dechlorination - Xiaoshuo Liu; Rui Wang; Xinze Geng; Ao Shen; Cong Chen; Yifan Xu; Xunlei Ding; Yufeng Duan; Shilin Zhao (Chemical Engineering Journal, 2023)

Enhanced nitrate removal by alcohol-involved nitrate photolysis-induced advanced reduction process - Yawei Xie; Shiyi Ni; Shiming Wang; Chenda Wu; Keqi Huang; Dehua Ma; Lujun Chen; Rui Liu; Hongyuan Liu (Chemical Engineering Journal, 2023)

Bradykinin-pretreated Human cardiac-specific c-kit+ Cells Enhance Exosomal miR-3059-5p and Promote Angiogenesis Against Hindlimb Ischemia in mice - Jingzhou Li; Fei Song; Ruolan Chen; Jinjuan Yang; Jie Liu; Li Huang; Fuyu Duan; Meng Kou; Boon Xuan Lian; Xiaoxia Zhou; Weimin Han; Liang Mao; et al. (Stem Cell Reviews and Reports, 2023)

Experimental Study of the Rock Cutting Mechanism with PDC Cutter Under Confining Pressure Condition - Weiji Liu; Hongxing Deng; Xiaohua Zhu; Rui Li; Chao He (Rock Mechanics and Rock Engineering, 2023)

Lactiplantibacillus plantarum Regulated Intestinal Microbial Community and Cytokines to Inhibit Salmonella typhimurium Infection - Rui-Han Liu; An-Qi Sun; Ye Liao; Zheng-Xu Tang; Shi-Han Zhang; Xin Shan; Jing-Tao Hu (Probiotics and Antimicrobial Proteins, 2023)

Photobiomodulation: A Potential Non-invasive Method to Alleviate Neurological Events Following COVID-19 Infection - Chongyun Wu; Timon Cheng-Yi Liu; Rui Duan; Luodan Yang (Neuroscience Bulletin, 2023)

Astragaloside IV-mediated inhibition of oxidative stress by upregulation of ghrelin in type 2 diabetes–induced cognitive impairment - Rui-hua Zhang; Shan-shan Cao; Yong Shi; Xin Wang; Lei-lei Shi; Yu-han Zhang; Chao-jun Han; Bin Wang; Liang Feng; Ji-ping Liu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2023)

FOXO4-D-Retro-Inverso targets extracellular matrix production in fibroblasts and ameliorates bleomycin-induced pulmonary fibrosis in mice - Ying Liu; Qinhui Hou; Rui Wang; Yuan Liu; Zhenshun Cheng (Naunyn-Schmiedeberg's Archives of Pharmacology, 2023)

Realgar-Induced Neurotoxicity: Crosstalk Between the Autophagic Flux and the p62-NRF2 Feedback Loop Mediates p62 Accumulation to Promote Apoptosis - Rui Feng; Jieyu Liu; Zhao Yang; Tiantian Yao; Ping Ye; Xiuhan Li; Jiaxin Zhang; Hong Jiang (Molecular Neurobiology, 2023)

Urine 2-hydroxyphenanthrene is associated with current asthma: evidence from NHANES 2007–2012 - Lingyi Lu; Tingfeng Mao; Rui Xu; Lanxia Liu; Jiefeng Qian; Kai Yang; Anjie Yuan; Xinyue Wang; Rong Ni (International Archives of Occupational and Environmental Health, 2023)

Hong Kong–Zhuhai–Macao Bridge deformation monitoring using PPP-RTK with multipath correction method - Rui Gao; Zhizhao Liu; Robert Odolinski; Qiang Jing; Jiantong Zhang; Hua Zhang; Baocheng Zhang (GPS Solutions, 2023)

Development of a highly sensitive immunoassay based on pentameric nanobodies for carcinoembryonic antigen detection - Yi Gu; Yang Guo; Yang Deng; Haipeng Song; Rui Nian; Wenshuai Liu (Analytica Chimica Acta, 2023)

Development of a novel fluorescent aptasensor based on the interaction between hexagonal β-Co(OH)2 nanoplates and nitrogen-doped carbon dots for ultrasensitive detection of patulin - Qi Sun; Zhijuan Li; Ningxin Liu; Yuting Zhou; Fuyan Zhang; Shuang Li; Peng Jin; Rui Xiang; Tao Le (Analytica Chimica Acta, 2023)

An epoxide-based covalent sensor to detect cardiac proteome aggregation in a cardio-oncology model - Hao Jin; Di Shen; Biao Jing; Zhenduo Zhang; Zhiming Wang; Rui Sun; Huaiyue Zhang; Jialu Sun; Haochen Lyu; Yu Liu; Lili Wang (Analytica Chimica Acta, 2023)

Polarity-extended liquid chromatography-triple quadrupole mass spectrometry for simultaneous hydrophilic and hydrophobic metabolite analysis - Rui Guo; Qisheng Zhong; Jiaqi Liu; Peiming Bai; Zongpeng Wang; Jieling Kou; Peijie Chen; Jie Zhang; Bo Zhang (Analytica Chimica Acta, 2023)

Using Cu2+ to regulate the emission feature of near-infrared fluorescent sensor with AIE: To detect ascorbic acid in food samples and its application in bioimaging - Qian Meng; Junxiong Yao; Mengyu Chen; Yajie Dong; Xinyi Liu; Shuyang Zhao; Rui Qiao; Cuibing Bai; Changqing Qu; Hui Miao (Analytica Chimica Acta, 2023)

Halomonas flagellata sp. nov., a halophilic bacterium isolated from saline soil in Xinjiang - Yin Huang; Rashidin Abdugheni; Jinbiao Ma; Rui Wang; Lei Gao; Yonghong Liu; Wenjun Li; Man Cai; Li Li (Archives of Microbiology, 2023)

Characteristics and propagation of meteorological and hydrological droughts in eastern Gansu, a typical semi‐arid region, China - Rui Zou; Yixing Yin; Xiaojun Wang; Zengxin Zhang; Xieyao Ma; Mengyang Liu; Irfan Ullah (International Journal of Climatology, 2023)
The meteorological drought (MD) is the precursor of the hydrological drought (HD), and understanding the propagation process from MD to HD is of great significance for the early warning of HD. Based on the theory of run and Bayesian networks, this study uses the standardized precipitation index (SPI), standardized precipitation evapotranspiration index (SPEI) and standardized streamflow index (SSI) to explore the characteristics and propagation of MD and HD in the regions of eastern Gansu, China. The results indicate that: (1) The region was mainly wet (dry) and the wetness (dryness) was stronger before (after) 2000 when reflected by SSI. The frequency is higher based on SPI and SPEI than that based on SSI, while the duration and magnitude are lower than those based on SSI. (2) The propagation time from MD to HD is generally within 1–10 months. After the occurrence of a certain level of MD, it is most likely to propagate to HD events that are relatively weaker than the MD. Besides, the higher the intensity level of MD, the shorter the propagation time to HD, and the shorter for cumulative occurrence probability of HD to approach 1.0. (3) The increase in temperature and decrease in precipitation, runoff and runoff coefficient may contribute to the dryness after 2000. Moreover, the weakened propagation from MD to HD may be due to the rapid increase of water resource consumption caused by intensive anthropogenic activities in the study area. From the above results, this study found some propagation characteristics from MD to HD in a semi‐arid and semi‐humid watershed, which can provide a supplement for revealing the drought mechanism and can assist in the management and planning of water resources in China.

Relationship between Large-Scale Variability of North Pacific Waves and El Niño-Southern Oscillation - Xin Zhang; Kejian Wu; Rui Li; Shuai Zhang; Ruyan Zhang; Jin Liu; Alexander V. Babanin (Journal of Marine Science and Engineering, 2023)
Ocean waves are crucial for driving various oceanic processes. In this study, the spatial and temporal distribution of significant wave height (SWH) in the North Pacific (NP) is analyzed using the 42-year ERA5 reanalysis dataset from European Centre for Medium-Range Weather Forecasts (ECMWF). The presence of an ENSO signal is confirmed in wave fields of the North Pacific. Furthermore, the spatial distributions of swells and wind waves are analyzed using the Empirical Orthogonal Function (EOF) method, revealing that waves can transport large-scale signals from the NP to lower latitudes through swells. In addition, our research reveals a relationship between ENSO and Stokes drift in the NP. Stokes drift contributes positively to the maintenance of stable sea surface temperatures (SSTs) by transporting more (less) water towards the equatorial Pacific during El Niño (La Niña year) years. It is further noted that during strong ENSO events, the strength of the Stokes drift anomaly intensifies accordingly, which implies a strong link between wave-induced transport and ENSO.

Recent progress in oil-in-water-in-oil (O/W/O) double emulsions - Zijian Zhi; Rui Liu; Wenjun Wang; Koen Dewettinck; Filip Van Bockstaele (Critical Reviews in Food Science and Nutrition, 2023)

Emission accounting and drivers in Central Asian countries - Congyu Zhao; Binyuan Liu; Jieyu Wang; Rui Xue; Yuli Shan; Can Cui; Xiucheng Dong; Kangyin Dong (Environmental Science and Pollution Research, 2023)
Emerging countries are at the frontier of climate change actions, and carbon emissions accounting provides a quantifiable measure of the environmental impact of economic activities, which allows for comparisons of emissions across different entities. However, currently there is no study covering detailed emissions inventories for emerging countries in Central Asian. This paper compiles detailed and accurate carbon emissions inventories in several Central Asian countries (i.e., Kazakhstan, Kyrgyzstan, Pakistan, Palestine, Tajikistan, and Uzbekistan) during the period 2010–2020. Using the IPCC administrative territorial approach, we for the first time compile their emissions inventories in 47 economic sectors and five energy categories. Moreover, we also investigate decoupling status based on Tapio decoupling model and examine emissions driving factors based on the index decomposition analysis method. The primary results illustrate that carbon emissions in Central Asian countries are increasing with huge differences. Decoupling results highlight that most of the sample countries still need more effort to decouple the economy and emissions except that Pakistan achieves an ideal strong decoupling state. The results of the decomposition indicate that the economy and population both raise emissions, while energy intensity and carbon intensity are negative drivers in some countries. We propose practical policy implications for decarbonization and energy transition roadmap in Central Asian countries.

Energy technology innovation through the lens of the financial deepening: Financial institutions and markets perspective - Baodan Liu; Rui Hu; Sana Ullah (Environmental Science and Pollution Research, 2023)

Multi-omics-based approach reveals the effects of microplastics on microbial abundance and function of sediments in Shenzhen coastal waters - Rui Zhang; Yu Liu (Frontiers in Marine Science, 2023)
In recent years, microplastics (MPs) have received extensive attention due to their bioaccumulation and toxic effects on organisms. However, there are few studies on MPs in coastal waters ecosystem and the relationship between MPs and microorganisms. Thus, to understand the concentration and characteristics of MPs and explore the impact of MPs on microbial community, we collected sediment samples from the coastal waters of Shenzhen, a developed city in southern China, and then analyzed them. The results showed that the concentration of MPs in the sediments of eastern Shenzhen was 119 ± 18 items/kg, while the concentration of MPs in the sediments of western Shenzhen, in which coastal waters were heavily polluted, was as high as 664 ± 197 items/kg. micro-FTIR analysis showed that the copolymers of polystyrene (PS) (39.64%) and polyethylene (PE) (16.26%) were the main types of MPs in Shenzhen coastal waters. According to optical microscopy, MPs (51.52%) with a size range of 0.1-0.5 mm dominated sediments in Shenzhen coastal watershed. Fibrous black plastics and film white plastics were the main forms of MPs in sediment samples studied in eastern and western Shenzhen. Metagenome and metabonomics analysis showed that MPs had an impact on microbial diversity in sediments, the structure and composition of microbial community. What’s more, through a functional prediction analysis, MPs may have different effects on the functions of various microbial communities. The study on the effects of MPs on microorganisms in the sediments of coastal waters ecosystem can provides a basis for further study on the interaction between MPs and microorganisms in similar habitats.

Mn(VII) enhanced by CaSO3 to remove trace organic pollutants in high salt organic wastewater: Further enhancement of salinity - Linsong Cheng; Yuanxiang Mao; Lei Jiang; Rui Ma; Jiangsen Ma; Yiyuan Zhuo; Qiushi Shen; Caocong Liu; Liuwei Zhao; Xiaoyi Xu; Fangying Ji (Chemosphere, 2023)

Loss of amino acids 67-76 in the neuraminidase protein under antibody selection pressure alters the tropism, transmissibility and innate immune response of H9N2 avian influenza virus in chickens - Jianjun Zhang; Quan Li; Rui Zhu; Shunshun Xu; Shifeng Wang; Huoying Shi; Xiufan Liu (Veterinary Microbiology, 2023)

Seismic failure probability analysis of slopes via stochastic material point method - Dezhi Zai; Rui Pang; Bin Xu; Jun Liu (Soil Dynamics and Earthquake Engineering, 2023)

Uncertainty in China's food self-sufficiency: A dynamic system assessment - Xinyuan Liang; Xiaobin Jin; Xiaoxiao Xu; Hefeng Chen; Jing Liu; Xuhong Yang; Weiyi Xu; Rui Sun; Bo Han; Yinkang Zhou (Sustainable Production and Consumption, 2023)

Linking soil phosphorus fractions to associated microbial functional profiles under crop rotation on the Loess Plateau of China - Yang Liu; Rui Liu; Rajan Ghimire; Nannan Zhang; Sha Zhou; Fazhu Zhao; Jun Wang (Soil and Tillage Research, 2023)

VOC transport in an occupied residence: Measurements and predictions via deep learning - Rui Zhang; Xinglei He; Jialong Liu; Jianyin Xiong (Science of The Total Environment, 2023)

Mechanism analysis of synthetic musks-induced miscarriage risk in pregnant women: Molecular and adverse outcome pathways perspectives - Xixi Li; Rui Li; Meijin Du; Qing Li; Di Liu (Science of The Total Environment, 2023)

Methanotrophs dominate methanogens and act as a methane sink in a subterranean karst cave - Xiaoyu Cheng; Zhilin Zeng; Xiaoyan Liu; Lu Li; Hongmei Wang; Rui Zhao; Paul L.E. Bodelier; Weiqi Wang; Yiheng Wang; Olli H. Tuovinen (Science of The Total Environment, 2023)

Dependence analysis of social contact behaviors under the impacts of COVID-19 based on a copula approach - Hongxiang Ding; Junyi Zhang; Tao Feng; Rui Liu (Science of The Total Environment, 2023)

Variations in trihalomethane formation potential of Microcystis aeruginosa under different growth conditions: Phenomenon and mechanism - Rui Huang; Wenbo Guo; Zhiquan Liu; Shugeng Li; Zhiwei Zhao; Wenxin Shi; Fuyi Cui; Chun Hu (Science of The Total Environment, 2023)

Integrating data dependent and data independent non-target screening methods for monitoring emerging contaminants in the Pearl River of Guangdong Province, China - Rui Wang; Yanan Yan; He Liu; Yanxi Li; Meng Jin; Yuqing Li; RiZhu Tao; Qianghua Chen; Xuguang Wang; Bo Zhao; Danping Xie (Science of The Total Environment, 2023)

Association between PM2.5 exposure and the outcomes of ART treatment: A prospective birth cohort study - Yifan Wang; Yun Qiu; Bo Huang; Jiangbo Du; Liya Liu; Tao Jiang; Yangqian Jiang; Hong Lv; Qun Lu; Rui Qin; Shiyao Tao; Lei Huang; et al. (Science of The Total Environment, 2023)

Rare loss-of-function variants reveal threshold and multifactorial inheritance of dextrocardia - Zhongzhong Chen; Yunqian Gao; Lei Lu; Nan Li; Pei Liu; Rui Peng; Lingling Liu; Hefeng Huang; Qihua Fu; Haifa Hong; Jianguo Zhang; Hongyan Wang (Science Bulletin, 2023)

Collaborative removal of fine catalysts particles and insoluble organics from methanol-to-olefins reaction wastewater using horizontal swirl regeneration micro-channel separation (HSRMS) - Jianqi Chen; Rui Cai; Haitao Huang; Qi Wei; Bing Liu; Aosong Wei; Meng Zhang; Wenjie Lv; Hualin Wang (Process Safety and Environmental Protection, 2023)

Insecticide resistance: Status and potential mechanisms in Aedes aegypti - Yifan Wang; Xin Wang; Dylan J. Brown; Mengru An; Rui-De Xue; Nannan Liu (Pesticide Biochemistry and Physiology, 2023)

Exploring the repairing mechanisms of reduced graphene oxide (rGo) on the dysregulation of Xenopus Laevis larva hypothalamus-pituitary-thyroid (HPT) axis caused by chiral triazole fungicide metconazole - Yue Deng; Meiling Zheng; Rui Liu; Haixia Zeng; Jingling Diao; Ran Xiao; Xiaoxuan Su (Pesticide Biochemistry and Physiology, 2023)

Effects of the launch parameters on trans-phase stability performance and mechanism for submarine-launched missiles model - Qibin Zhuang; Huanbin Zhang; Chenhong Zhao; Xingyu He; Yu Liu; Zhirong Liu; Shuping Li; Rui Zhu; Dezhi Wu (Ocean Engineering, 2023)

Synthesis of a novel hydroxyl quaternary ammonium collector and its selective flotation separation of quartz from hematite - Wenbao Liu; Kelin Tong; Rui Ding; Wengang Liu; Panxing Zhao; Wenhan Sun; Qiang Zhao; Sikai Zhao (Minerals Engineering, 2023)

Integrated insight into the molecular mechanisms of selenium-modulated, MPP+-induced cytotoxicity in a Parkinson’s disease model - Wen Liu; Feiyang Zhang; Wu Liang; Kaixin Huang; Chenguang Jia; Jie Zhang; Xiang Li; Wei Wei; Rui Gong; Jincao Chen (Journal of Trace Elements in Medicine and Biology, 2023)

Nitrate attenuation with rising groundwater levels: An integrated assessment using isotope tracers and microbial signatures - Jie Li; Yulian Liu; Wei Dai; Jian Li; Pingheng Yang; Lijun Tian; Shihang Yu; Rui Zuo; Yuanzheng Zhai; Wei Song; Fan Yang; Ruijing Zhou; et al. (Journal of Hydrology, 2023)

A mega study of antibiotics contamination in Eastern aquatic ecosystems of China: occurrence, interphase transfer processes, ecotoxicological risks, and source modeling - Abdul Qadeer; Guo Rui; Liu Yaqing; Dai Ran; Chengyou Liu; Dong Jing; Muhammad Anis; Mengyang Liu; Shuhang Wang; Xia Jiang; Xingru Zhao (Journal of Hazardous Materials, 2023)

New insights into health risk assessment on soil trace metal(loid)s: Model improvement and parameter optimization - Jiaxun Sun; Xinmiao Huang; Xiaoyong Song; Rui Tang; Menglu Zhao; Boya Cai; Huijuan Wang; Zilin Han; Yafeng Liu; Zhengqiu Fan (Journal of Hazardous Materials, 2023)

Preparation of magnesium potassium phosphate cement from municipal solid waste incineration fly ash and lead slag co-blended: Ca-induced crystal reconstruction process and Pb-Cl synergistic solidification mechanism - Shiwei Liu; Xing Cao; Weichen Yang; Runjie Liu; Lin Fang; Rui Ma; Juan Peng; Shuaifei Zheng; Fei Ji (Journal of Hazardous Materials, 2023)

Characterizing VOCs emissions of five packaging and printing enterprises in China and the emission reduction potential of this industry - Guiying You; Hefan Liu; Rui Sun; Zengxin Jin; Jing Li; Xiaoling Zhou; Sihua Lu; Shaodong Xie (Journal of Cleaner Production, 2023)

Superhydrophobic MOF based materials and their applications for oil-water separation - Yijun Liu; Zhengda Lin; Yang Luo; Rui Wu; Rui Fang; Ahmad Umar; Zhongming Zhang; Zhiying Zhao; Jie Yao; Shuaifei Zhao (Journal of Cleaner Production, 2023)

Trade-off strategy for the usage of thiencarbazone-methyl·isoxaflutole on maize fields: Nitrogen-associated microbial response and environmental implications - Yonglu Wang; Fengsong Zhang; Lida Wang; Huajun Fang; Guixiang Zhang; Xiumei Zhao; Siyi Liu; Qingchao Li; Yue Liu; Rui Ren; Yu An; Lisha Fan (Journal of Cleaner Production, 2023)

Biotrophic interactions between plant and endophytic bacteria in removal of PAHs and Cd from contaminated soils enhanced by graphene oxide - Lingmei Li; Rui Liu; Jianjun Chen; Peidong Tai; Xiaoyi Bi; Ping Zou; Yajie Wang; Yao Xiao (Journal of Cleaner Production, 2023)

Molecular selection and environmental evaluation of eco-friendly surfactants to efficiently reduce pesticide pollution - Zhenping Bao; Yanling Wu; Rui Liu; Songhao Zhang; Yupu Chen; Tianyue Wu; Yuxia Gao; Chenhui Zhang; Fengpei Du (Journal of Cleaner Production, 2023)

Regeneration of high-performance materials for electrochemical energy storage from assorted solid waste: A review - Jia-feng Zhang; De-zhao Peng; Xiang-gang Gao; Jing-tian Zou; Long Ye; Guan-jun Ji; Bi Luo; Gui-hui Yu; Peng-fei Li; Xiao-wei Wang; Zao-wen Zhao; Bao Zhang; et al. (Journal of Cleaner Production, 2023)

Vegetation descriptors from Sentinel-1 SAR data for crop growth monitoring - Xin Bao; Rui Zhang; Jichao Lv; Renzhe Wu; Hongsheng Zhang; Jie Chen; Bo Zhang; Xiaoying Ouyang; Guoxiang Liu (ISPRS Journal of Photogrammetry and Remote Sensing, 2023)

CaO hydrated with ethanol solution for flue gas HCl immobilization. Part Ⅰ: Modification & dechlorination - Rui Wang; Xiaoshuo Liu; Cong Chen; Yuqing Wang; Zhen Shen; Lei Meng; Xiaobing Gu; Changdong Sheng; Yufeng Duan (Fuel, 2023)

Enhanced anode electrochemiluminescence in split aptamer sensor for kanamycin trace monitoring - Xiaoyue Zhang; Yu Du; Xuejing Liu; Rui Feng; Yue Jia; Xiang Ren; Nuo Zhang; Lei Liu; Qin Wei; Huangxian Ju (Food Chemistry, 2023)

Identification and application of species-specific peptide biomarkers from soft-shelled turtles (Pelodiscus sinensis) using post-translational modification detection-based peptidomics analysis - Haoran Xia; Xun Liu; Shuo Cai; Shengjun Chen; Song Li; Ming Zhao; Jin-ao Duan; Rui Liu; Shuying Han (Food Chemistry, 2023)

Immobilization of Bacillus Thuringiensis and applicability in removal of sulfamethazine from soil - Shengfang Wen; Hunan Liu; Rui Yang; Lanjun Wang; Lusheng Zhu; Jun Wang; Young Mo Kim; Jinhua Wang (Environmental Pollution, 2023)

Pd sub-nanolayer on Au core for enhanced catalytic hydrogenation reduction of oxyanions pollutants: Synergistic effect of Pd and Au - Minghui Li; Hang Liu; Chang Liu; Yan Ding; Caixia Fang; Rui Wan; Hongjie Zhu; Yaning Yang (Environmental Pollution, 2023)

An adaptive federated learning system for community building energy load forecasting and anomaly prediction - Rui Wang; Hongguang Yun; Rakiba Rayhana; Junchi Bin; Chengkai Zhang; Omar E. Herrera; Zheng Liu; Walter Mérida (Energy and Buildings, 2023)

A novel allocation method of regional carbon allowance in building sector: Perspective from coupling equity and efficiency - Qiqi Liu; Jingxin Gao; Weiguang Cai; Tengfei Huo; Rui Li (Environmental Impact Assessment Review, 2023)

Long-term periodicity of sedimentary basins in response to astronomical forcing: Review and perspective - Rui Zhang; Zhijun Jin; Mingsong Li; Michael Gillman; Shuping Chen; Quanyou Liu; Ren Wei; Juye Shi (Earth-Science Reviews, 2023)

Discrete element modelling of the effect of aspect ratio on compaction and shear behaviour of aggregates - Rui Lu; Qiang Luo; Tengfei Wang; David P. Connolly; Kaiwen Liu; Chunfa Zhao (Computers and Geotechnics, 2023)

The impact of different side chain ionomer on membrane electrode assembly performance and durability - Shengchu Liu; Rui Lin; Jiapeng Lu; Ying Wang; Xin Cai (Chemical Engineering Journal, 2023)

Controllable micro cross-linking towards multifunctional flame-retardant aliphatic polyamide - Qin Zhang; Guo-Rui Zhu; Xiang-Xin Xiao; Qing-Song Liu; Min Jiang; De-Ming Guo; Hai-Bo Zhao; Wen-Da Li; Li Chen; Bo-Wen Liu; Yu-Zhong Wang (Chemical Engineering Journal, 2023)

Exfoliation behavior and superior photothermal conversion performance of MXenes beyond Ti3C2T - Cuilian Wen; Qiugang Liao; Zhou Cui; Ziqiang Chen; Hao Liu; Rui Xiong; Baisheng Sa (Chemical Engineering Journal, 2023)

Antimicrobial hydrogel microneedle loading verteporfin promotes skin regeneration by blocking mechanotransduction signaling - Chengxiu Wei; Chuangang You; Liming Zhou; Huiling Liu; Shihao Zhou; Xingang Wang; Rui Guo (Chemical Engineering Journal, 2023)

Polyphenol synergistic cerium oxide surface engineering constructed core-shell nanostructures as antioxidants for durable and high-performance proton exchange membrane fuel cells - Shengqiu Zhao; Yucong Liao; Rui Wang; Guoliang Liu; Haining Zhang; Haolin Tang (Chemical Engineering Journal, 2023)

Insights on rational design and regulation strategies of Prussian blue analogues and their derivatives towards high-performance electrocatalysts - Yu-Rui Ji; Ya-Fei Guo; Xu Liu; Peng-Fei Wang; Ting-Feng Yi (Chemical Engineering Journal, 2023)

Remarkable bioactivity, bio-tribological, antibacterial, and anti-corrosion properties in a Ti-6Al-4V-xCu alloy by laser powder bed fusion for superior biomedical implant applications - Jiang Ju; Rui Zan; Zhao Shen; Chenchen Wang; Peng Peng; Jun Wang; Baode Sun; Bo Xiao; Qian Li; Shaofei Liu; Tao Yang (Chemical Engineering Journal, 2023)

A surface-induced coating strategy for constructing hydrophobic zeolite composite to enhance the toluene adsorption in humid environment - Shuangchun Lu; Wenjuan Xue; Hao Wang; Qingling Liu; Rui Han; Donghai Mei (Chemical Engineering Journal, 2023)

Investigating the electrochemical performance of MnO2 polymorphs as cathode materials for aqueous proton batteries - Yujie Dai; Jianze Zhang; Xiaorong Yan; Guoqing Zhao; Mingsheng Yang; Jiakui Xiong; Rui Li; Naihua Miao; Haiping Yu; Mingjun Hu; Jingru Liu; Jun Yang (Chemical Engineering Journal, 2023)

SIRT1 regulates osteoblast senescence through SOD2 acetylation and mitochondrial dysfunction in the progression of Osteoporosis caused by Cadmium exposure - Dehui Zhou; Yawei Ran; Rui Yu; Gang Liu; Di Ran; Zongping Liu (Chemico-Biological Interactions, 2023)

Functional characterization of novel NPRL3 mutations identified in three families with focal epilepsy - Shiyue Du; Sheng Zeng; Li Song; Hongying Ma; Rui Chen; Junyu Luo; Xu Wang; Tingbin Ma; Xuan Xu; Hao Sun; Ping Yi; Jifeng Guo; et al. (Science China Life Sciences, 2023)

Cutting Efficiency of a Newly Developed Incubator-Based Laser Cutting Method and Its Effects on Potato Tissue Culture Plantlet Growth - Tao Xu; Hongbing Duan; Xingkui Cai; Rui Yang; Feihu Yao; Benfang Tan; Fengshun Liu (Potato Research, 2023)

The biocontrol agent Bacillus velezensis T-5 changes the soil bacterial community composition by affecting the tomato root exudate profile - Yian Gu; Weina Liang; Zhidan Li; Sijie Liu; Sun Liang; Peng Lei; Rui Wang; Nan Gao; Sha Li; Zongqi Xu; Hong Xu (Plant and Soil, 2023)

Interaction of nitrogen availability in the soil with leaf physiological traits and nodule formation of Robinia pseudoacacia-rhizobia symbiosis depends on provenance - Hongguang Sun; Rui Liu; Hui Yuan; Mi Zhou; Zhenshan Liu; Bin Hu; Heinz Rennenberg (Plant and Soil, 2023)

The Dynamics of Dopamine D2 Receptor-Expressing Striatal Neurons and the Downstream Circuit Underlying L-Dopa-Induced Dyskinesia in Rats - Kuncheng Liu; Miaomiao Song; Shasha Gao; Lu Yao; Li Zhang; Jie Feng; Ling Wang; Rui Gao; Yong Wang (Neuroscience Bulletin, 2023)

Effects of EDTA and Organic Acids on Physiological Processes, Gene Expression Levels, and Cadmium Accumulation in Solanum nigrum Under Cadmium Stress - Wanhong Liu; Ting Yu; Hanping Cao; Xiang Peng; Ya Yang; Rui Li (Journal of Soil Science and Plant Nutrition, 2023)

An R2R3-MYB Transcription Factor CmMYB42 Improves Low-Nitrogen Stress Tolerance in Chrysanthemum - Rui Ma; Sen Yang; Yanhong Liu; Xia Sun; Wenli Wang; Chengshu Zheng (Journal of Plant Growth Regulation, 2023)

Nafamostat mesilate prevented caerulein-induced pancreatic injury by targeting HDAC6-mediated NLRP3 inflammasome activation - Peng Chen; Li-Jun Zhao; Ling Huang; Wen-Qi He; Ying-Rui Tang; Yi Liu; Jian-Dong Ren (Inflammation Research, 2023)

Featured immune characteristics of COVID-19 and systemic lupus erythematosus revealed by multidimensional integrated analyses - Xingwang Zhao; Mengjie Zhang; Yuying Jia; Wenying Liu; Shifei Li; Cuie Gao; Lian Zhang; Bing Ni; Zhihua Ruan; Rui Dong (Inflammation Research, 2023)

Resveratrol plays an anti-fibrotic and anti-autophagy role by stimulating miR-192-5p expression in urethral fibrosis - Jin Lv; Rui Zhang; DaoYuan Li; Yan Liu (Functional & Integrative Genomics, 2023)

Long-term effective remediation of black-odorous water via regulating calcium nitrate sustained-release - Rui Wan; Yunyi Zha; Mengqi Wu; Xiaoxiao Li; Haifeng Yang; Hongming Liu (Environmental Monitoring and Assessment, 2023)

Silicified Microorganisms and Microorganism-Like Particles in the Groundwater of an Abandoned Coal Mine - Guangyu Shao; Changsuo Li; Rui Liu; Peng Zhang; Lei Zuo; Yaqin Wang (Mine Water and the Environment, 2023)

Prediction of landslide block movement based on Kalman filtering data assimilation method - Yong Liu; Qing-jie Xu; Xing-rui Li; Ling-feng Yang; Hong Xu (Journal of Mountain Science, 2023)

Agricultural intensification weakens soil multifunctionality by reducing fungal diversity - Rui Xue; Chong Wang; Lei Zhao; Jia Cao; Mengli Liu; Dong Zhang (Applied Soil Ecology, 2023)

Quantifying the effects of urban development intensity on the surface urban heat island across building climate zones - Tianxing He; Rui Zhou; Qun Ma; Chunlin Li; Dan Liu; Xuening Fang; Yina Hu; Jun Gao (Applied Geography, 2023)

In situ 15 N‐N 2 O site preference and O 2 concentration dynamics disclose the complexity of N 2 O production processes in agricultural soil - Huanhuan Wei; Xiaotong Song; Yan Liu; Rui Wang; Xunhua Zheng; Klaus Butterbach‐Bahl; Rodney T. Venterea; Di Wu; Xiaotang Ju (Global Change Biology, 2023)
Arable soil continues to be the dominant anthropogenic source of nitrous oxide (N 2 O) emissions owing to application of nitrogen (N) fertilizers and manures across the world. Using laboratory and in situ studies to elucidate the key factors controlling soil N 2 O emissions remains challenging due to the potential importance of multiple complex processes. We examined soil surface N 2 O fluxes in an arable soil, combined with in situ high‐frequency measurements of soil matrix oxygen (O 2 ) and N 2 O concentrations, in situ 15 N labeling, and N 2 O 15 N site preference (SP). The in situ O 2 concentration and further microcosm visualized spatiotemporal distribution of O 2 both suggested that O 2 dynamics were the proximal determining factor to matrix N 2 O concentration and fluxes due to quick O 2 depletion after N fertilization. Further SP analysis and in situ 15 N labeling experiment revealed that the main source for N 2 O emissions was bacterial denitrification during the hot‐wet summer with lower soil O 2 concentration, while nitrification or fungal denitrification contributed about 50.0% to total emissions during the cold‐dry winter with higher soil O 2 concentration. The robust positive correlation between O 2 concentration and SP values underpinned that the O 2 dynamics were the key factor to differentiate the composite processes of N 2 O production in in situ structured soil. Our findings deciphered the complexity of N 2 O production processes in real field conditions, and suggest that O 2 dynamics rather than stimulation of functional gene abundances play a key role in controlling soil N 2 O production processes in undisturbed structure soils. Our results help to develop targeted N 2 O mitigation measures and to improve process models for constraining global N 2 O budget.

Insights into the quantitative structure–activity relationship for ionic liquids: a bibliometric mapping analysis - Rui Huang; Hui Liu; Ze Wei; Yi Jiang; Kai Pan; Xin Wang; Jie Kong (Environmental Science and Pollution Research, 2023)

Does physical activity moderate the association between shorter leukocyte telomere length and incident coronary heart disease? Data from 54,180 UK Biobank participants - Meiruo Xiang; Luke C. Pilling; David Melzer; Ben Kirk; Gustavo Duque; Rui Liu; George A. Kuchel; Andrew R. Wood; Brad Metcalf; Breno S. Diniz; Melvyn Hillsdon; Chia-Ling Kuo (GeroScience, 2023)
Telomere shortening is a biological aging hallmark. The effect of short telomere length may be targeted by increased physical activity to reduce the risk of multiple aging-related diseases, including coronary heart disease (CHD). The objective was to assess the moderation effect of accelerometer-based physical activity (aPA) on the association between shorter leukocyte telomere length (LTL) relatively in the population sample and incident CHD. Data were from the UK Biobank participants with well-calibrated accelerometer data for at least 6.5 days ( n = 54,180). Relative mean LTL at baseline (5–6 years prior to aPA assessment) was measured in T/S ratio, using a multiplex quantitative polymerase chain reaction (qPCR) technology, by comparing the amount of the telomere amplification product (T) to that of a single-copy gene (S). aPA measures included total number of events (at least 10-s continued physical activity > 32 milligravities [mg]), total volume, mean duration, mean intensity, and peak intensity of all events. LTL, aPA measures, and their interactions were associated with incident CHD (mean follow-up 6.8 years) using Cox proportional hazards models adjusting for covariates. Longer LTL (relative to the sample distribution) was associated with reduced incidence of CHD (adjusted hazard ratio [aHR] = 0.94 per standard deviation [SD] increase in LTL, [95% CI, 0.90 to 0.99], P = .010). Incidence of CHD was reduced by higher total volume of aPA (aHR = 0.82 per SD increase in LTL, [95% CI, 0.71 to 0.95], P = .010) but increased by higher total number of events (aHR = 1.11 per SD increase in LTL, [95% CI, 1.02 to 1.21], P = .020) after controlling for other aPA measures and covariates. However, none of the interactions between LTL and aPA measures was statistically significant ( P = .171).

Two new bibenzyls from Pleione grandiflora (Rolfe) Rolfe and their antioxidant activity - Wei Li; Jia-Rui Fu; Li-Jun Zheng; Lin Ni; Jun-Qing Liu; Jun-Wen Zhai; Zhuang Zhou; Sha-Sha Wu (Natural Product Research, 2023)

F-box and leucine-rich repeat protein 16 controls tamoxifen sensitivity via regulation of mitochondrial respiration in estrogen receptor-positive breast cancer cells - Feng Chen; Lu Wang; Yanrong Feng; Wenxin Ma; Junqin Liu; Qianyao Bi; Yao Song; Rui Gao; Yanhan Jia (Human Cell, 2023)

Association between prenatal exposure to trace elements mixture and visual acuity in infants: A prospective birth cohort study - Zijin Wang; Yuanyan Dou; Wenhui Guo; Yuan Lin; Yangqian Jiang; Tao Jiang; Rui Qin; Hong Lv; Qun Lu; Guangfu Jin; Hongxia Ma; Zhibin Hu; et al. (Chemosphere, 2023)

Quantifying uncertainty of marine water quality forecasts for environmental management using a dynamic multi-factor analysis and multi-resolution ensemble approach - Rui Yang; Hui Liu; Yanfei Li (Chemosphere, 2023)

Refined feature fusion for in-field high-density and multi-scale rice panicle counting in UAV images - Yao Chen; Rui Xin; Haiyan Jiang; Yonghuai Liu; Xiaoqi Zhang; Jialin Yu (Computers and Electronics in Agriculture, 2023)

Purification of conchocelis of Neoporphyra haitanensis by the method of dominant Bacteria enrichment comprehensive treatment - Mingjie Ma; Qiqin Liu; Lin Huang; Peng Zhang; Haimin Chen; Juanjuan Chen; Qijun Luo; Tiegan Wang; Rui Yang (Aquaculture, 2023)

Otolith microchemistry reveals various habitat uses and life histories of Chinese gizzard shad Clupanodon thrissa in the Min River and the estuary, Fujian Province, China - Qing Xu; Qing-qiang Ren; Tao Jiang; Chen-rui Jiang; Lü-ping Fang; Ming-zhe Zhang; Jian Yang; Min Liu (Fisheries Research, 2023)

Enhanced bacterial adhesion force by rifampicin resistance promotes microbial colonization on PE plastic compared to non-resistant biofilm formation - Jiayi Wu; Congcong Liu; Rui Wang; Saitao Yan; Baoliang Chen; Xiaoying Zhu (Water Research, 2023)

Acute inhalation of tungsten particles results in early signs of cardiac injury - Sage Templeton; Charlotte M. McVeigh; Colin Nguyen; Russell Hunter; David Scieszka; Guy W. Herbert; Edward B. Barr; Rui Liu; Haiwei Gu; Barry E. Bleske; Matthew J. Campen; Alicia M. Bolt (Toxicology Letters, 2023)

Residues, potential source and ecological risk assessment of polycyclic aromatic hydrocarbons (PAHs) in surface water of the East Liao River, Jilin Province, China - Mula Na; Yunmeng Zhao; Su Rina; Rui Wang; Xingpeng Liu; Zhijun Tong; Jiquan Zhang (Science of The Total Environment, 2023)

Evaluation of sludge anaerobic fermentation driving partial denitrification capability: In view of kinetics and metagenomic mechanisms - Qingtao Liu; Cong Li; Jiarui Fan; Yongzhen Peng; Rui Du (Science of The Total Environment, 2023)

Theory, framework, and methodology for physical lifespan prediction of hazardous waste landfills - Xu Ya; Yao Guangyuan; Liu Yuqiang; Liu Jingcai; Xiang Rui; Qian Can (Science of The Total Environment, 2023)

Ferulic acid enhanced resistance against blue mold of Malus domestica by regulating reactive oxygen species and phenylpropanoid metabolism - Mi Guo; Canying Li; Rui Huang; Linhong Qu; Jiaxin Liu; Chenyang Zhang; Yonghong Ge (Postharvest Biology and Technology, 2023)

Experimental study on low-frequency flow noise at the stern of a surface vessel induced by pulsating pressure - Rui Deng; Zhenpu Yan; Xiang Yu; Hao Li; Hailong Liu; Tiecheng Wu (Ocean Engineering, 2023)

Experimental study on the influence of a T-foil and bulbous bow on the resistance and motion in regular head waves of trimarans - Rui Deng; Sichong Huang; Shigang Wang; Hailong Liu; Xiang Yu; Tiecheng Wu (Ocean Engineering, 2023)

Direct numerical simulation of acoustic wave propagation in ocean waveguides using a parallel finite volume solver - Rui Xia; Xiao-Wei Guo; Chao Li; Jie Liu (Ocean Engineering, 2023)

First occurrence of caryocaridids (Crustacea, Phyllocarida) in the Ordovician of North China - Yi-long Liu; Ruo-ying Fan; Rui-wen Zong; Yi-ming Gong (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Enhanced selective nitrate-to-nitrogen electrocatalytic reduction by CNTs doped Ni foam/Cu electrode coupled with Cl− - Xinrui Liu; Rui Guo; Xia Qin; Cuicui Xu (Journal of Water Process Engineering, 2023)

Antibacterial, antiviral, and biodegradable collagen network mask for effective particulate removal and wireless breath monitoring - Peng Zhao; Rui Wang; Jun Xiang; Jinwei Zhang; Xiaodong Wu; Chaojian Chen; Gongyan Liu (Journal of Hazardous Materials, 2023)

Synergistic effect of double Schottky potential well and oxygen vacancy for enhanced plasmonic photocatalytic U(VI) reduction - Xin Liu; Rui-Xiang Bi; Zhi-Hai Peng; Lan Lei; Cheng-Rong Zhang; Qiu-Xia Luo; Ru-Ping Liang; Jian-Ding Qiu (Journal of Hazardous Materials, 2023)

Effects of gums on 3D printing performance of Pleurotus eryngii powder - Anqi He; Juan Xu; Qiuhui Hu; Liyan Zhao; Gaoxing Ma; Lei Zhong; Rui Liu (Journal of Food Engineering, 2023)

A “smart-sensing” bactericidal protein-based Pickering emulsion - Lishan Yao; Rui Wang; Shurui Peng; Zhenbin Liu; Hongbo Li; Dan Xu; Liangbin Hu; Haizhen Mo (Journal of Food Engineering, 2023)

Efficient lipid synthesis of Chlorella pyrenoidosa promoted under heavy metals from electric arc furnace slag - Qing Yu; Tian-Ji Liu; Ya-Nan Zeng; Yi-Tong Wang; Jun-Guo Li; Yu-Ran Wang; Le-Le Kang; Rui Ji; Fu-Ping Wang; Xiao-Man Wang; Bao Liu; Shuang Cai; et al. (Journal of Cleaner Production, 2023)

Spatiotemporal clustering analysis of shared electric vehicles based on trajectory data for sustainable urban governance - Lewen Bao; Zonglin Liu; Rui Miao; Zhihua Chen; Bo Zhang; Peng Guo; Yuze Ma (Journal of Cleaner Production, 2023)

Aggregation and stability of selenium nanoparticles: Complex roles of surface coating, electrolytes and natural organic matter - Sujuan Yu; Hao Liu; Rui Yang; Wenjing Zhou; Jingfu Liu (Journal of Environmental Sciences, 2023)

Evaluating the role of tectonic setting in new continental crust formation by Pb isotopic ratios - Xian Chen; Rui-Zhong Hu; Xuan-Ce Wang; Liang Liu (Journal of Asian Earth Sciences, 2023)

Structure-guided camera localization for indoor environments - Qing Li; Rui Cao; Kanglin Liu; Zongze Li; Jiasong Zhu; Zhenyu Bao; Xu Fang; Qingquan Li; Xianfeng Huang; Guoping Qiu (ISPRS Journal of Photogrammetry and Remote Sensing, 2023)

Enhanced recovery of germanium(IV) from zinc residue leachate by tartaric acid functionalized chitosan: Experiments and DFT calculation - Hongrui Xiang; Zhihui Yang; Xiaobo Min; Yanjie Liang; Cong Peng; Xiaoyun Liu; Rui Yuan; Qingwei Wang; Feiping Zhao (Hydrometallurgy, 2023)

Mapping submarine landslides susceptibility in continental slopes with rich gas hydrates - Lin Tan; Fang Liu; Yu Huang; Rui Wang; Jianhua Geng; Giovanni Crosta; Paolo Frattini (Gas Science and Engineering, 2023)

Estimation of rough fracture network permeability using fractal and topology theories - Di Shi; Liping Li; Yintong Guo; Jianjun Liu; Jupeng Tang; Xin Chang; Rui Song; Mingyang Wu (Gas Science and Engineering, 2023)

Influence factors of starch nanoparticles formation and their application in Pickering emulsion - Xiaoxia Yan; JinLin Bai; Rui Liu; Zeyi Liu; Shuyi Li; Tiehua Zhang (Food Bioscience, 2023)

Magnetic biochar with Mg/La modification for highly effective phosphate adsorption and its potential application as an algaecide and fertilizer - Jinqi Zhu; Tingwei Rui; Yiwen You; Dong Shen; Tao Liu (Environmental Research, 2023)

Analytical study on heavy metal output fluxes and source apportionment of a non-ferrous smelter in southwest China - Chenchen Li; Peng Dong; Jin Yan; Rui Gong; Qi Meng; Jun Yao; Hanjing Yu; Yaoqiang Ma; Bang Liu; Ruosong Xie (Environmental Pollution, 2023)

Effects of different water-cooled heat sinks on the cooling system performance in a data center - Wei He; Jifang Zhang; Hailong Li; Rui Guo; Shengchun Liu; Xiaohui Wu; Jie Wei; Yulin Wang (Energy and Buildings, 2023)

Enlocking the high Zn2+-storage of conversion-type Te cathode by regulating the surface binding-interaction with graphene - Cong Guo; Shangjun Yi; Rui Si; Yixiao Wang; He Liu; Feng Yu; Jingfa Li (Chemical Engineering Journal, 2023)

Self-shedding of multifunctional biomolecular nanocarriers for H-FABP monitoring in magnetic separation self-powered photoelectrochemical and colorimetric immunoassay platform - Dongquan Leng; Rui Xu; Xiang Ren; Hongmin Ma; Lei Liu; Qin Wei; Huangxian Ju (Chemical Engineering Journal, 2023)

Will the southward center of gravity migration of population, floor area, and building energy consumption facilitate building carbon emission reduction in China? - Rui Li; Kairui You; Weiguang Cai; Jiebing Wang; Yuan Liu; Yanhui Yu (Building and Environment, 2023)

Cell Therapy for Androgenetic Alopecia: Elixir or Trick? - Yongcui Mao; Pinyan Liu; Jiayun Wei; Ye Xie; Qiuxia Zheng; Rui Li; Jia Yao (Stem Cell Reviews and Reports, 2023)
Androgenetic alopecia is the most common cause of hair loss aggravated by increased life pressure, tension, and anxiety. Although androgenetic alopecia (AGA) does not significantly effect physical health, it can have serious negative impact on the mental health and quality of life of the patient. Currently, the effect of medical treatment for AGA is not idealistic, stem cell-based regenerative medicine has shown potential for hair regrowth and follicle repair, but the long-term effect and mechanism of stem cell therapy is not quite explicit. In this review, we summarize the methods, efficacy, mechanism, and clinical progress of stem cell therapies for AGA by now, hope it will present a more comprehensive view in this topic. Graphical Abstract

AIWW: a new nutrition-screening tool for the oncologic population - Yi-Zhong Ge; Zhen-Ming Fu; Qi Zhang; Meng-Meng Song; Guo-Tian Ruan; Xi Zhang; Xiao-Wei Zhang; Xiang-Rui Li; Kang-Ping Zhang; Meng Tang; Xiao-Yue Liu; Ming Yang; et al. (Science China Life Sciences, 2023)

Specific pupylation as IDEntity reporter (SPIDER) for the identification of protein-biomolecule interactions - He-Wei Jiang; Hong Chen; Yun-Xiao Zheng; Xue-Ning Wang; Qingfeng Meng; Jin Xie; Jiong Zhang; ChangSheng Zhang; Zhao-Wei Xu; Zi-Qing Chen; Lei Wang; Wei-Sha Kong; et al. (Science China Life Sciences, 2023)

Synthesis and pharmacological evaluation of new disulfides linked to 1,2,4-triazole bearing urea moiety - Rui Tang; Haichuan Zhao; Shuai Zhang; Xiaojia Liu; Jinbiao Liu; Wei Li; Hongying Wang; Caiwen Li; Baoquan Chen (Medicinal Chemistry Research, 2023)

Spatial distribution of landslide shape induced by Luding Ms6.8 earthquake, Sichuan, China: case study of the Moxi Town - Xuemei Liu; Pengcheng Su; Yong Li; Zhaoxu Xia; Siyuan Ma; Rui Xu; Yao Lu; Dahu Li; Heng Lu; Renmao Yuan (Landslides, 2023)

Centimeter-level clock synchronization and space-borne timescale generation for BDS-3 using inter-satellite link measurements - Jianhua Yang; Chengpan Tang; Xiaogong Hu; Shanshi Zhou; Li Liu; Yezhi Song; Yufei Yang; Rui Guo; Shuai Liu; Junyang Pan (Journal of Geodesy, 2023)

Study on electric agglomeration of bipolar-charged coal-fired fly ash particles and its effect on filtration performance of fibrous filter - Chao Lv; Guodong Li; Ruiqing Shen; Rui Shu; Mian Zhu; Zhenhui Yu; Jingxian Liu (Clean Technologies and Environmental Policy, 2023)

Effects of Dietary Vitamin D3 on Growth Performance, Immune Status, and Calcium and Phosphorus Metabolism in Litopenaeus vannamei Under Different Salinity Conditions - Miao Liu; Hui Zhang; Rui Shao; Xueqi Zhou; Qicun Zhou; Kangsen Mai; Qinghui Ai; Min Wan (Journal of Ocean University of China, 2023)

Fluorescence enhancement of surface plasmon coupled emission by Au nanobipyramids and its modulation effect on multi-wavelength radiation - Kai-Xin Xie; Rui-Ping Huo; Xiu-Li Song; Qiao-Ling Liu; Yue Jiang; Yu-Han Li; Lu-Lu Dong; Jia-Xin Cheng (Analytica Chimica Acta, 2023)

Correction of illumination effects on seasonal divergent NIRv photosynthetic phenology - Rui Chen; Gaofei Yin; Guoxiang Liu; Yajie Yang; Changjing Wang; Qiaoyun Xie; Wei Zhao; Aleixandre Verger (Agricultural and Forest Meteorology, 2023)

Analysis of cuproptosis-related lncRNA signature for predicting prognosis and tumor immune microenvironment in pancreatic cancer - Hong-Fei Yao; Da-Peng Xu; Jia-Hao Zheng; Yu Xu; Qin-Yuan Jia; Yu-Heng Zhu; Jian Yang; Rui-Zhe He; Ding Ma; Min-Wei Yang; Xue-Liang Fu; De-Jun Liu; et al. (Apoptosis, 2023)

Selective CDK9 knockdown sensitizes TRAIL response by suppression of antiapoptotic factors and NF-kappaB pathway - Qian Yuan; Kui Su; Shuyi Li; Xinyi Long; Lang Liu; Jianwu Sun; Xin Yuan; Minghui Yang; Rui Tian; Wanting Zhang; Zhujie Deng; Quanjiang Li; et al. (Apoptosis, 2023)

Spatiotemporal variation and multivariate controls of short‐cycle drought–flood abrupt alteration: A case in the Qinling‐Daba Mountains of China - Xiaoyan Song; Xiaoping Lei; Rui Ma; Jingzhi Hou; Wenbin Liu (International Journal of Climatology, 2023)
A comprehensive understanding of the patterns of drought and flood alternation in adjacent months is essential for enabling climate adaptation and mitigation strategies. However, there is a paucity of knowledge regarding short‐cycle drought–flood abrupt alteration (s‐DFAA) and its responses to multiple environmental factors at various timescales. This is because of the inadequate formula construction of the existing short‐cycle drought–flood abrupt alteration index (SDFAI), such as the inability to introduce drought standards. To accurately capture the s‐DFAA's characteristics in the Qinling‐Daba Mountains (Qinba Mountains), we proposed a revised SDFAI (R‐SDFAI), which incorporates the standardized precipitation index (SPI) and allows for the customization of drought standards. Next, we used wavelet transform coherence and multiple wavelet coherence to investigate the timescale relationships between s‐DFAA events and their influence factors such as relative humidity, sunshine duration, temperature, evaporation, Arctic Oscillation (AO), Niño3.4 SSTA Index (Niño3.4), Total Sunspot Number Index (TSNI) and Pacific Decadal Oscillation Index (PDO). Our results showed that the R‐SDFAI outperformed traditional SDFAI in capturing s‐DFAA events and characterizing their severity. Furthermore, s‐DFAA events identified by R‐SDFAI at different levels (i.e., mild, moderate, severe, extreme and total) displayed insignificant downward trends. Spatially, there were more s‐DFAA events in the east than the west. Wavelet analysis indicated that meteorological factors and teleconnections significantly impact s‐DFAA events at large timescales, though their driving mechanisms differed substantially. Among meteorological factors, single relative humidity and its related combinations exhibited relatively high percent area of significant coherence (PASC, ranging from 17.47 to 29.46). Each teleconnection and its combinations are irreplaceable, with PASC values always increasing with the number of variables. The PASC ranges from 8.3 to 10.29 for one factor, 12.38 to 18.65 for two factors, 24.02 to 30.58 for three factors and 40.88 for four factors, respectively.

A ZSG-DEA model with factor constraint cone-based decoupling analysis for household CO2 emissions: a case study on Sichuan province - Rui Zhao; Jie Liu; Hai Long; Xin Xiong; Dingye Wu (Environmental Science and Pollution Research, 2023)

Distribution, sources and influencing factors of organic carbon in the surface sediments of the coastal tidal flats in Jiangsu Province - Rui Zhao; Xinrui Dong; Qing Liu; Min Xu; Yifei Zhao (Frontiers in Marine Science, 2023)
Coastal tidal flats are situated in the interaction zone between the ocean and land and are vulnerable to natural changes, human activities, and global changes; these areas serve as an important mixing zone and burial area for carbon and nitrogen storage. Coastal tidal flats contribute significantly to the global carbon cycle due to their high biological productivity, high sedimentation rate, and low decomposition rate. However, there is a lack of research on the sources and influencing factors of organic carbon in surface sediments in the coastal tidal flat area of Jiangsu Province. In this study, fourteen surface sediment samples were collected from the Jiangsu coastal tidal flats, and the distribution of organic carbon was analyzed. The sources and influencing factors of sediment organic carbon were also investigated by analyzing the contents, ratios and stable isotopes of carbon and nitrogen in the sediments. The results indicated that the total organic carbon (TOC) and total nitrogen (TN) contents in the surface sediments of Jiangsu coastal tidal flats ranged from 0.09% to 0.82% and from 0.01% to 0.1%, with mean values of 0.36% and 0.04%, respectively, and that there was a significant positive correlation between TOC and TN. Moreover, the high-value areas were located mostly along the borders or in sections covered in vegetation, whereas the mudflat areas without vegetation had lower values. Considering the status of the Jiangsu coastal zone, the abandoned Yellow River estuary, Yangtze River inlet, marine benthic microalgae, C3 plants and C4 plants were selected as end members of organic carbon concentrations. The contributions of different sources were quantified using a Bayesian mixture model (MixSIAR). Among them, the abandoned Yellow River estuary and Yangtze River inlet contributed 28.1% and 19.3%, respectively, followed by marine benthic microalgae with a contribution of 26%, whereas C3 and C4 plants made limited contributions of 9% and 8.8%, respectively. Additionally, the sediment particle size, hydrodynamics, and tidal flat vegetation such as Spartina alterniflora were the key factors influencing the organic carbon distribution. In general, this study contributes to a better understanding of the biogeochemical processes and sources of organic carbon in coastal tidal flats. It also provides a solid foundation for the creation of carbon sink measures in nearshore tidal flats.

Evaluation of carbon emission efficiency and spatial relevance in the thermal power industry: evidence from China - Yu Liu; Rui-tang Guo; Wei-guo Pan (Environment, Development and Sustainability, 2023)

Research on the fire extinguishing performance of new gel foam for preventing and controlling the spontaneous combustion of coal gangue - Chuandong Liu; Rui Zhang; Zixian Wang; Xiaoqiang Zhang (Environmental Science and Pollution Research, 2023)

Transcriptional investigation of the toxic mechanisms of perfluorooctane sulfonate in rats based on an RNA-Seq approach - Tianrun Wang; Xuying Zhao; Tianze Liu; Jiguang Zhang; Jing Qiu; Mei Li; Rui Weng (Chemosphere, 2023)

Iron-rich red mud and iron oxide-modified biochars: A comparative study on the removal of Cd(II) and influence of natural aging processes - Huabin Wang; Dingxiang Chen; Yi Wen; Yong Zhang; Ying Liu; Rui Xu (Chemosphere, 2023)

Magnetic anaerobic granular sludge for sequestration and immobilization of Pb - Rui Zhou; Han Li; Chengshuai Liu; Yizhang Liu; Jyh-Fu Lee; Yu-Jung Lin; Zhang Yan; Zhangyi Xu; Xiaoyun Yi; Chunhua Feng (Water Research, 2023)

Atmospheric ammonia in China: Long-term spatiotemporal variation, urban-rural gradient, and influencing factors - Jinyan Dong; Baojie Li; Yan Li; Rui Zhou; Cong Gan; Yongqi Zhao; Rui Liu; Yating Yang; Teng Wang; Hong Liao (Science of The Total Environment, 2023)

In a quest for high-efficiency mainstream partial nitritation-anammox (PN/A) implementation: One-stage or two-stage? - Shenbin Cao; Konrad Koch; Haoran Duan; George F. Wells; Liu Ye; Yingfen Zhao; Rui Du (Science of The Total Environment, 2023)

Regional CO2 accounting and market layout of incinerator fly ash management in China - Yunqi Zhai; Fang Liu; Yifan Hu; Lei Wang; Xuebin Lu; Zhihao Yu; Hanqiao Liu; Rui Zhang (Science of The Total Environment, 2023)

Molecular insights into the dissolved organic matter of leather wastewater in leather industrial park wastewater treatment plant - Xiao-Xu Gao; Yun-Wen Wang; Ye-Chen An; Rui-Yun Ren; Yao-Hui Lin; Ning Wang; Yi-Fan Wang; Jing-Long Han; Zhi-Neng Hao; Jing-Fu Liu; Ai-Jie Wang; Nan-Qi Ren (Science of The Total Environment, 2023)

Determination of minimum infusion rate of propofol in combination with electroacupuncture in goats - Lingling Liu; Mahmoud M. Abouelfetouh; Rui Sun; Eman Salah; Sha Nan; Mingxing Ding; Yuzhen Song; Yi Ding (Small Ruminant Research, 2023)

Opportunities for the use of selenium nanoparticles in agriculture - Jiangyun Song; Sujuan Yu; Rui Yang; Junping Xiao; Jingfu Liu (NanoImpact, 2023)

Overexpression of CdtCIPK21 from triploid bermudagrass reduces salt and drought tolerance but increases chilling tolerance in transgenic rice - Rui Liu; Shilian Huang; Anyao Huang; Miao Chen; Yurong Luo; Zhenfei Guo; Shaoyun Lu (Journal of Plant Physiology, 2023)

Innovative screening for functional improved aromatic amine derivatives: Toxicokinetics, free radical oxidation pathway and carcinogenic adverse outcome pathway - Yajing Liu; Xinao Li; Qikun Pu; Rui Fu; Zhonghe Wang; Yu Li; Xixi Li (Journal of Hazardous Materials, 2023)

Removal of per- and polyfluoroalkyl substances by nanofiltration: Effect of molecular structure and coexisting natural organic matter - Caihong Liu; Ye Shen; Xiaoqing Zhao; Ziwei Chen; Rui Gao; Qingyang Zuo; Qiang He; Jun Ma; Yue Zhi (Journal of Hazardous Materials, 2023)

Mechanism for regulation of a forward osmosis membrane by the SA/UiO-66-NH2 composite interlayer and the resulting lithium ion concentration performance - Miaolu He; Yushuang Li; Leihao Feng; Jiaqi Wang; Ze Liu; Lei Wang; Jin Wang; Rui Miao; Xudong Wang (Journal of Cleaner Production, 2023)

Paleozoic remelting of carbonatite in Bayan Obo (China): Further insights into the formation of a giant REE deposit - Hai-Dong She; Hong-Rui Fan; M. Santosh; Xiao-Chun Li; Kui-Feng Yang; Qi-Wei Wang; Wei Wei; Yan-Jiang Liu; Shang Liu; Shuang-Liang Liu (Gondwana Research, 2023)

Comparative study of the combustion and kinetic characteristics of fresh and naturally aged pine wood - Jun Deng; Tong-shuang Liu; Min Yao; Xin Yi; Guang-Xing Bai; Qian-rui Huang; Zheng Li (Fuel, 2023)

Experimental and numerical study on the ignition delay times of methane/propane mixtures diluted in carbon dioxide - Wenxiang Xia; Chun Zou; Yi Yuan; Rui Fu; Jiacheng Liu; Chao Peng (Fuel, 2023)

Application of Clostridium butyricum, Rummeliibacillus suwonensis, and Issatchenkia orientalis for Nongxiangxing baijiu fermentation: Improves the microbial communities and flavor of upper fermented grain - Tongwei Guan; Xiaotian Wu; Rui Hou; Lei Tian; Qiao Huang; Fan Zhao; Ying Liu; Shirong Jiao; Shuangquan Xiang; Jiaxu Zhang; Dong Li; Jing Luo; et al. (Food Research International, 2023)

Biomineralization-inspired artificial clickase for portable click SERS immunoassay of Salmonella enterica serovar Paratyphi B in foods - Xianlong Zhang; Yiheng Shi; Panpan Wang; Di Wu; Jianghua Liu; Rui Huang; Yongning Wu; Guoliang Li (Food Chemistry, 2023)

Combined effects of NaOH, NaCl, and heat on the characteristics of ovalbumin gel and the exploration of the mechanism of transparent gel formation - Hui Xue; Tianfeng Han; Guowen Zhang; Xiaobo Hu; Ruiling Li; Huilan Liu; Rui Li; Yonggang Tu; Yan Zhao (Food Hydrocolloids, 2023)

Gelation mechanism of high soluble dietary fiber okara-egg tofu induced by combined treatment of steam explosion and enzymatic hydrolysis - Nuo Zhao; Jianfu Wu; Xiaoyuan Geng; Chenyang Wang; Tao Wu; Rui Liu; Wenjie Sui; Min Zhang (Food Hydrocolloids, 2023)

Intraspecific variations of adaptive strategies of native and invasive plant species along an elevational gradient - Hasigerili; Kun Guo; Miao-Miao Zheng; Rui-Ling Liu; Yan-Yan Wang; Yuan Gao; Li Shu; Xiao-Ran Wang; Jian Zhang; Wen-Yong Guo (Flora, 2023)

Insights into dissolved organics in non-urban areas - Optical properties and sources - Feng Yu; Xiaofei Li; Rui Zhang; Jingning Guo; Wen Yang; Lekhendra Tripathee; Lang Liu; Yuqin Wang; Shichang Kang; Junji Cao (Environmental Pollution, 2023)

Astrochronology and sedimentary noise modeling of Pliensbachian (Early Jurassic) sea-level changes, Paris Basin, France - Rui Zhang; David B. Kemp; Nicolas Thibault; Mads E. Jelby; Mingsong Li; Chunju Huang; Yu Sui; Zhixiang Wang; Dongyang Liu; Shizhen Jia (Earth and Planetary Science Letters, 2023)

Obliquity forcing of continental aquifers during the late Paleozoic ice age - Ren Wei; Mingsong Li; Rui Zhang; Yongyun Hu; James G. Ogg; Guoyong Liu; He Huang; Xiangwu He; Shuai Yuan; Qifan Lin; Zhijun Jin (Earth and Planetary Science Letters, 2023)

Stable β-form zinc phthalocyanine cathodes for flexible Zn-ion hybrid supercapacitors with ultra-long cycling life - Daotong Han; Wenyun Wang; Shangjing Yu; Wentao Qi; Rui Ling; Chao Yang; Guangqiang Liu (Chemical Engineering Journal, 2023)

In situ polymerization of polypyrrole in oil body for efficient solar-driven freshwater collection - Hongxiang Liu; Tianshu Zou; Xingyu Cui; Miao Ding; Biao Zhang; Xiaodong Yang; Yu Han; Shuwei Nie; Yuan Zhang; Enze Wang; Lili Wang; Yan Cheng; et al. (Chemical Engineering Journal, 2023)

Molecularly imprinted polymers embedded with double perovskite quantum dots: A ratiometric fluorescence sensor for visible and fluorescent determination of Rhein - Rongkun Zhu; Zengcheng Du; Mingfang Zhu; Huanru Liang; Shumei Wang; Qing Zhou; Rui Li; Yulan Li; Chaoying Zeng; Wenhao Liu; Qiqing Chen (Chemical Engineering Journal, 2023)

CRISPR-Cas12a powered multifunctional DNA nanodumbbell lock biosensor for multiple molecular detection - Yuqing Zhu; Xiaohe Zheng; Rui Zhu; Hongrui Zhao; Hongli Zhai; Feiyang Qian; Tenghua Zhang; Zihui Xie; Silan Liu; Bowen Jiang; Yan Sheng; Jiaming Hu (Chemical Engineering Journal, 2023)

Benzene abatement catalyzed by Ceria-Supported platinum nanoparticles and single atoms - Jing Liu; Xue Fang; Daoqing Liu; Xiaolei Hu; Tian Qin; Junxiao Chen; Rui Liu; Dongrun Xu; Weiye Qu; Yangyang Dong; Liwei Chen; Zhen Ma; et al. (Chemical Engineering Journal, 2023)

Dissipation and movement of soil water in artificial forest in arid oasis areas: Cognition based on stable isotopes - Dongdong Qiu; Guofeng Zhu; Xinrui Lin; Yinying Jiao; Siyu Lu; Jiatong Liu; Jiawei Liu; Wenhao Zhang; Linlin Ye; Rui Li; Qinqin Wang; Longhu Chen (CATENA, 2023)

Late Pleistocene zinc isotopic indices of paleoproductivity variations in the tropical West Pacific - Wenlong Pei; Jiayue Wang; Xinling Wang; Liang Du; Yipeng Wang; Yujin Fan; Rui Zhang; Tiegang Li; James Russell; Fan Zhang; Xiaoxiao Yu; Zhiyong Liu; et al. (CATENA, 2023)

Selenomethionine protects against Escherichia coli-induced endometritis by inhibiting inflammation and necroptosis via regulating the PPAR-γ/NF-κB pathway - Lu Cao; Shouyang Gao; Junbao Liu; Junrong Wang; Rui Qin (Chemico-Biological Interactions, 2023)

Potential thyroid hormone disorder risks of tire antioxidants to aquatic food chain organisms after absorbing free radicals in marine and freshwater environments - Yu Wang; Rui Fu; Xinao Li; Wenjin Zhao; Miao Liu; Yu Li (Aquatic Toxicology, 2023)

Duox mediated ROS production inhibited WSSV replication in Eriocheir sinensis under short-term nitrite stress - Rui Jia; Xiaoling Dai; Yanfang Li; Xintong Yang; Xiuwen Min; Derun Quan; Peng Liu; Xin Huang; Jiachun Ge; Qian Ren (Aquatic Toxicology, 2023)

Transcriptional analysis of the dimorphic fungus Umbilicaria muehlenbergii reveals the molecular mechanism of phenotypic transition - Dongjie Fan; Lushan Liu; Shunan Cao; Rui Liao; Chuanpeng Liu; Qiming Zhou (World Journal of Microbiology and Biotechnology, 2023)

The Regulation of the AMPK/mTOR Axis Mitigates Tendon Stem/Progenitor Cell Senescence and Delays Tendon Aging - Guangchun Dai; Yingjuan Li; Ming Zhang; Panpan Lu; Yuanwei Zhang; Hao Wang; Liu Shi; Mumin Cao; Renwang Shen; Yunfeng Rui (Stem Cell Reviews and Reports, 2023)

The PIWI-specific insertion module helps load longer piRNAs for translational activation essential for male fertility - Xin Wang; Di-Hang Lin; Yue Yan; An-Hui Wang; Jiaoyang Liao; Qian Meng; Wen-Qing Yang; Heng Zuo; Min-Min Hua; Fengjuan Zhang; Hongwen Zhu; Hu Zhou; et al. (Science China Life Sciences, 2023)

Genetic and Phenotypic Spectrum of Amyotrophic Lateral Sclerosis Patients with CCNF Variants from a Large Chinese Cohort - Bi Zhao; Qirui Jiang; Junyu Lin; Qianqian Wei; Chunyu Li; Yanbing Hou; Bei Cao; Lingyu Zhang; Ruwei Ou; Kuncheng Liu; Tianmi Yang; Yi Xiao; et al. (Molecular Neurobiology, 2023)
Cyclin F (CCNF) variants have been found to be associated with amyotrophic lateral sclerosis (ALS)/frontotemporal dementia (FTD). However, the genetic and clinical characteristics of ALS patients who carry CCNF variants are largely unknown. Genetic analysis was performed for 1587 Chinese ALS patients, and missense variants were predicted by software analyses. Additionally, we searched PubMed, Embase, and Web of Science for relevant literature and conducted a meta-analysis of the frequency of variants. In our ALS cohort, we identified 29 nonsynonymous variants in 41 ALS patients. Among these ALS patients, 18 (1.1%) were carriers of 15 rare missense variants that were considered probably pathogenic variants, and 11 of 15 variants were novel. Seven relevant studies were identified, and a total of 43 CCNF variants in 59 ALS patients with a frequency of 0.8% were reported. The ratio of males to females in our cohort (10/8) was similar to that in Caucasian populations (4/7) and significantly higher than that in Asian populations (10/1). The proportion of bulbar onset in Caucasian CCNF carriers was similar to our cohort (25.0 vs. 27.8%); however, bulbar onset had never been reported in previous Asian studies (0/11). FTD was not found in CCNF carriers in previous Asian studies and our cohort, but it has been reported in a FALS cohort (1/75) of Caucasian individuals. There were some differences in the clinical characteristics among different ethnic ALS populations. More basic scientific studies are needed to elucidate the pathogenic mechanisms and genotype-phenotype associations of CCNF variants.

Correction to: Mitochondrial Hydrogen Peroxide Activates PTEN and Inactivates Akt Leading to Autophagy Inhibition-Dependent Cell Death in Neuronal Models of Parkinson’s Disease - Qianyun Yu; Ruijie Zhang; Tianjing Li; Liu Yang; Zhihan Zhou; Long Hou; Wen Wu; Rui Zhao; Xiaoling Chen; Yajie Yao; Shile Huang; Long Chen (Molecular Neurobiology, 2023)

Effects of Enterobacter sp. Zm-123 and spent mushroom substrate on rape growth promotion and cadmium toxicity reduction in cadmium-contaminated soil - Yu Jin; Rui Yang; Yongduo Guan; Xiaochen Liu; JiaHui Fu; Xuesheng Liu; Juanjuan Qu (Journal of Soils and Sediments, 2023)

A Novel D-π-A Type Fluorescent Probe for Cu2+ Based on Styryl-Pyridinium Salts Conjugating Di-(2-picolyl)amine (DPA) Units - Rui Cao; Mengyu Zhang; Wen Tang; Jing Wu; Meixiang Wang; Xiaoxiao Niu; Zhaodi Liu; Fuying Hao; Huajie Xu (Journal of Fluorescence, 2023)

Preparation of Carbon Dots from PET Waste by One-step Hydrothermal Method and its Application in Light Blocking Films and LEDs - Rui Wang; Shumiao Li; Hanjiang Huang; Botong Liu; Lu Gao; Meiru Qu; Yanying Wei; Jianfei Wei (Journal of Fluorescence, 2023)

Effect of exogenous Ca on the physiology and growth indicators of pakchoi under foliar and root fluorine stress - Rui Liu; Si-fan Cui; Chun-dan Gan; Jin-yan Yang (Environmental Geochemistry and Health, 2023)

Government–business relations, environmental information transparency, and Hu-line-related factors in China - Rui Yang; Yingwen Chen; Yiqun Liu; Yuchen Feng; Jianwan Ji; Christina W. Y. Wong; Xin Miao; Yanhong Tang (Environment, Development and Sustainability, 2023)

Influences of paleoclimatic environment and hydrogeochemical evolution on groundwater salinity in an arid inland plain in northwestern China - Yujuan Lei; Yunde Liu; Ziyong Sun; Changjian Zou; Rui Ma; Lihe Yin; Huanying Pan (Applied Geochemistry, 2023)

Study on the Methods of Measurement, Optimization and Forecast of Propulsion Shaft Bearing Load of Ships - Rui Li; Ji Wang; Ziqi Chen; Feixiang Wang; Yujun Liu (Journal of Marine Science and Engineering, 2023)
The qualit12y of shafting alignment is related to the reliability and safety of a ship’s operation, and bearing displacement adjustment (BDA) plays a key role in shafting alignment. To solve the problems encountered in ship shafting alignment in the actual construction, this study focused on the investigation of the shafting load measurement system based on the strain gauge method (SGM), used the optimization method based on quadratic programming (QP) to calculate the BDA and adopted algorithms based on the bearing load influence coefficients (BICs) to forecast the load after the adjustment. The experimental work, as well as the measurement, calculation and analysis of several real ships, indicated that the measurement, optimization and forecasting methods of the bearing load of the propulsion shafting of large ships in this study would be significant for guiding the actual construction work of ship shafting alignment.

Removal of toilet paper fibers from residential wastewater: a life cycle assessment - Xiaoyu Wang; Guoqiang Liu; Weimin Sun; Zhiguo Cao; Huaqing Liu; Yiqun Xiong; Baoqin Li; Xiaoxu Sun; Yongbin Li; Rui Xu; Duanyi Huang; Pin Gao (Environmental Science and Pollution Research, 2023)

Short-term effects of individual exposure to PM2.5 on hospital admissions for myocardial infarction and stroke: a population-based case-crossover study in Guangzhou, China - Jie-Qi Jin; Guo-Zhen Lin; Shuang-Ying Wu; Mu-Rui Zheng; Hui Liu; Xiang-Yi Liu; Min-Qian Yan; Zhao-Yue Chen; Chun-Quan Ou (Environmental Science and Pollution Research, 2023)

Structural characterization of a pectic polysaccharide from laoshan green tea and its inhibitory effects on the production of NO, TNF- α and IL-6 - Fan Liu; Rongshen Wang; Ying Chen; Rui Geng; Hong Gao; Feng Wang; Xiaoxiao Liu; Wanzhong Li (Natural Product Research, 2023)

Novel insights into tumorigenesis and prognosis of endometrial cancer through systematic investigation and validation on mitophagy-related signature - Rui Sun; Xiaoyu Zhou; Tong Wang; Yao Liu; Lina Wei; Ziyi Qiu; Chunping Qiu; Jie Jiang (Human Cell, 2023)

BI-IEnKF coupling model for effective source term estimation of natural gas leakage in urban utility tunnels - Jiansong Wu; Jitao Cai; Zhe Liu; Shuaiqi Yuan; Yiping Bai; Rui Zhou (Tunnelling and Underground Space Technology, 2023)

Experimental study on low-damage performance of Sliding Hinge Joint - Junrong Liu; Rui Zhang; Zhenduo Yan; Jiang-Yue Xie; Kim Eng Chouery; Liang-Jiu Jia; Ping Xiang; Xianzhong Zhao; Shahab Ramhormozian; Rajesh P. Dhakal; G. Charles Clifton; Gregory A. MacRae (Soil Dynamics and Earthquake Engineering, 2023)

Eco-friendly phenol formaldehyde resin wood adhesive from bagasse lignin liquefaction - Jinming Liu; Enjun Xie; Yanrong Tang; Rui Feng; Weixing Gan (Sustainable Chemistry and Pharmacy, 2023)

The combined effects of atrazine and warming on environmental adaptability in lizards (Eremias argus) from the perspective of a life-history traits trade-off: Gender differences in trade-off strategies may reverse mortality risk - Yufan Nie; Zikang Wang; Simin Yu; Luyao Zhang; Rui Liu; Yuping Liu; Wentao Zhu; Zhiqiang Zhou; Jinling Diao (Science of The Total Environment, 2023)

Fe contents and isotopes in suspended particulate matter of Lancang River in Southwest China - Yang Tang; Guilin Han; Liu Man; Jie Zeng; Rui Qu (Science of The Total Environment, 2023)

Insight into micropollutant abatement during ultraviolet light-emitting diode combined electrochemical process: Reaction mechanism, contributions of reactive species and degradation routes - Rui Hu; Sui-Qin Yang; Jia-Ying Li; Fengyi Sun; Zheng-Qian Liu; Jingjing Yang; Yu-Hong Cui; Beiping Zhang (Science of The Total Environment, 2023)

The discovery of 3-fluoroalkyl indoles as potential antifungal agents to control tomato gray mold caused by Botrytis cinerea - Rui Feng; Fei Liu; Yan Wang; Shu Xu; Wuzhang Liu; Siwei Qiao; Songtao Liu; Yu Chen; Xu Feng; Qizhi Wang; Weidong Rao (Phytochemistry Letters, 2023)

Euphpepluone S, a new lathyrane diterpenoid with anti-inflammatory activity from Euphorbia peplus L. - Shi-Peng Guan; Ying Yang; Mao Sun; Min Cai; Xue-Xue Pu; Jian-Yi Huang; Ping Yi; Lin Liu; Ming-Rui Yuan; Yuan-Yuan Cheng; Ying-Tong Di (Phytochemistry Letters, 2023)

An approach for carbon content measurement in marine sediment: Application of organic and elemental carbon analyzer - Weifeng Wu; Haoshuai Li; Nan Wang; Xuan Huo; Guoqiang Zhong; Longhai Zhu; Jingyu Liu; Yang Zhou; Caiqing Yan; Rui Bao (Marine Environmental Research, 2023)

The tectono-magmatic formation and submarine geohazards of the Japan Sea: Constraints from in-situ trace elements and Sr isotopes of plagioclase and clinopyroxene - Shuang-Shuang Chen; Jing Chen; Qiuming Cheng; Rui Gao; Jia-Qi Liu (Marine and Petroleum Geology, 2023)

Mineralogy and geochemistry of the Zedong Late Cretaceous (∼94 Ma) biotite granodiorite in the Southern Lhasa Terrane: Implications for the tectonic setting and Cu-Au mineralization - Weice Zhang; Zhidan Zhao; Dong Liu; Kunfeng Qiu; Qing Wang; Di-Cheng Zhu; Tiannan Yang; Yingchao Liu; Rui Wang; Zengqian Hou; Xuanxue Mo (Lithos, 2023)

Lower limits of petrophysical parameters for effective reservoirs in ultradeep carbonate gas reservoirs: A case study from the Deng IV Member, Gaoshiti-Moxi Area, Sichuan Basin, SW China - Lu Wang; Yifan Zhang; Ruilan Luo; Rui Zou; Hui Deng; Run Zou; Liang Huang; Yisheng Liu (Journal of Hydrology, 2023)

Groundwater table fluctuation: A driving force affecting nitrogen transformation in nitrate-contaminated groundwater - Rui Zuo; Shida Zheng; Xin Liu; Guanlan Wu; Shufang Wang; Jinsheng Wang; Jiawei Liu; Chenxi Huang; Yuanzheng Zhai (Journal of Hydrology, 2023)

A Responsive Feeding Questionnaire Based on Self-Determination Theory for Caregivers of Chinese Toddlers - Yan Liu; Guiling Yu; Zhihui Li; Yan Kong; Rui Yang; Chunlan Yin; Xiaodi Sun (Journal of Nutrition Education and Behavior, 2023)

D-π-A array structure of Bi4Ti3O12-triazine-aldehyde group benzene skeleton for enhanced photocatalytic uranium (VI) reduction - Xin Liu; Rui-Xiang Bi; Feng-Tao Yu; Cheng-Rong Zhang; Qiu-Xia Luo; Ru-Ping Liang; Jian-Ding Qiu (Journal of Hazardous Materials, 2023)

Efficient emerging contaminants (EM) decomposition via peroxymonosulfate (PMS) activation by Co3O4/carbonized polyaniline (CPANI) composite: Characterization of tetracycline (TC) degradation property and application for the remediation of EM-polluted water body - Jin Qian; Xiaohui Mi; Zhijie Chen; Weihang Xu; Wen Liu; Rui Ma; Yichu Zhang; Yufei Du; Bing-Jie Ni (Journal of Cleaner Production, 2023)

Blending n-octanol with biodiesel for more efficient and cleaner combustion in diesel engines: A modeling study - Jing Li; Yifei Liang; Shuo Wang; Shaohua Wu; Wenming Yang; Rui Liu (Journal of Cleaner Production, 2023)

Deciphering riverine dissolved organic matter biodegradation: Evidence from three-dimensional fluorescence - Rong Xu; Jing Zhang; Jianwei Li; Rui Liu; Maofei Ni; Guangneng Zeng (Journal of Environmental Chemical Engineering, 2023)

Highly synergistic and polarized KNbO3/WO3 heterojunction for piezo-photocatalytic degradation of organic pollutant - Rui Huang; Wei Cai; Heng Zhang; Zhenhua Wang; Qin Zhang; Rongli Gao; Gang Chen; Xiaoling Deng; Xiang Lei; Jiling Dong; Xiaoyan Liu; Chunlin Fu (Journal of Environmental Chemical Engineering, 2023)

Competitive adsorption of heavy metals between Ca–P and Mg–P products from wastewater during struvite crystallization - Yazhou Wang; Jinrong Da; Yuxuan Deng; Rui Wang; Xiaoning Liu; Jianbo Chang (Journal of Environmental Management, 2023)

Study on dynamic fracture growth mechanism of continental shale under compression failure - Siwei Meng; Dongxu Li; Xin Liu; Zihan Zhang; Jiaping Tao; Liu Yang; Zhenhua Rui (Gas Science and Engineering, 2023)

Recent advances on the preparation and combustion performances of boron-based alloy fuels - Danfeng Yang; Rui Liu; Wei Li; Qi-Long Yan (Fuel, 2023)

Composition, metabolism and postharvest function and regulation of fruit cuticle: A review - Gang-Shuai Liu; Hong-Li Li; Zhen-Zhen Peng; Rui-Ling Liu; Yan-Chao Han; Yun-Xiang Wang; Xiao-Dan Zhao; Da-Qi Fu (Food Chemistry, 2023)

Bacterial microbiota and metabolic characteristics of traditional Zhangjiajie Jiuqu aromatic ester vinegar in China - Yue Sun; Xinyu Zuo; Rui Luo; Na Dang; Di Shi; Wenjun Liu (Food Bioscience, 2023)

Use of nano titanium hydroxide and nano zirconium hydroxide fixed filter paper for rapid detection of Staphylococcus aureus in dairy products by PCR without pre-enrichment - Chun Wang; Ruohong Zhang; Xiaofang Wang; Rui Xu; Hejing Yan; Xiaoran Li; Shaojun Liu; Shuren Yin; Hong Yao; Yang Yang; Shenghui Cui; Yunchang Guo (Food Control, 2023)

Metabolism of hydrogen peroxide by Lactobacillus plantarum NJAU-01: A proteomics study - Lei Chen; Rui Liu; Suyun Li; Mangang Wu; Hai Yu; Qingfeng Ge (Food Microbiology, 2023)

Regulating structure and properties of gelatine edible film through oxidized poly(2-hydroxyethyl acrylate) crosslinking - Baohua Liu; Songzhi Xie; Jian Wang; Chunman Zhu; Rui Qi; Yin Zhang; Dayu Liu (Food Packaging and Shelf Life, 2023)

Mechanistic insights into dissolved organic matter-driven protistan and bacterial community dynamics influenced by vegetation restoration - Zhang-mu Jing; Qing-qian Li; Yan-jie Wei; Bin Dong; Peng Yuan; Rui-xia Liu; Hong-jie Gao (Environmental Research, 2023)

An effective tool for tracking steroids and their metabolites at the watershed level: Combining fugacity modeling and a chemical indicator - Ru Xu; Shan Liu; Hui Chen; Qin-Wei Hao; Yong-Xia Hu; Heng-Xiang Li; Lang Lin; Rui Hou; Bing Hong; Shen Yu; Xiang-Rong Xu (Environmental Pollution, 2023)

Full-scale push-out testing of headed stud-steel block connectors in prefabricated steel-concrete composite beams - Jiepeng Liu; Jincheng Xie; Gang Xiong; Xuanding Wang; Yunhe Zou; Rui Shu; Y. Frank Chen (Engineering Structures, 2023)

Experimental and numerical study on interfacial thermal behaviour of CRTS II slab track under continuous high temperatures - Rui Zhou; Haohao Yue; Yanliang Du; Guowen Yao; Weibin Liu; Weixin Ren (Engineering Structures, 2023)

A multi-geophysical approach to assess potential sinkholes in an urban area - Rui Liu; Huaifeng Sun; Jianwen Qin; Ziqiang Zheng (Engineering Geology, 2023)

CO2 absorption in blended amine solvent: Speciation, equilibrium solubility and excessive property - Rui Zhang; Ruixi Liu; Francesco Barzagli; Meher Geetika Sanku; Chao'en Li; Min Xiao (Chemical Engineering Journal, 2023)

Immunoregulatory hydrogel decorated with Tannic acid/Ferric ion accelerates diabetic wound healing via regulating Macrophage polarization - Na Xu; Yuanping Gao; Zheng Li; Yu Chen; Menglong Liu; Jiezhi Jia; Rui Zeng; Gaoxing Luo; Jiangfeng Li; Yunlong Yu (Chemical Engineering Journal, 2023)

Heterogeneous doping via charge carrier transport improves Photoelectrochemical H2O oxidative H2O2 synthesis - Jinwei Bai; Rui-Ting Gao; Nhat Truong Nguyen; Xianhu Liu; Xueyuan Zhang; Lei Wang (Chemical Engineering Journal, 2023)

Fe/Ni layered double hydroxide biocatalysts inhibit tumor growth through ROS and ferroptosis signaling pathway - Qiwen Pan; Fei Lin; Ruiqi Liu; Yilin Li; Xinyue Zhang; Rui Luo; Lingling Cai; Yang Liu; Wuguo Deng; Liru He (Chemical Engineering Journal, 2023)

Local eutectic combined with surface functional treatment: An efficient strategy to lower desorption temperature of bulk magnesium-based hydride - Rui Shi; Haoxing Yan; Jiguang Zhang; Yunfeng Zhu; Yana Liu; Jun Wang; Xiaohui Hu; Liquan Li (Chemical Engineering Journal, 2023)

Revealing opposite behaviors of catalyst for VOCs Oxidation: Modulating electronic structure of Pt nanoparticles by Mn doping - Yanfei Zheng; Rui Han; Lizhe Yang; Jining Yang; Cangpeng Shan; Qingling Liu (Chemical Engineering Journal, 2023)

Performance of nitrification–denitrification and denitrifying phosphorus removal driven by in-situ generated biogenic manganese oxides in a moving bed biofilm reactor - Jinfeng Zhong; Jiamin Liu; Rui Hu; Dandan Pan; Sicheng Shao; Xiangwei Wu (Bioresource Technology, 2023)

A new model system for cotton indoor genetic and genomic research - Jun Zhang; Zhanfeng Si; Rui Chen; Wangshu Liu; Yue Shi; Zhuolin Shi; Huan Mei; Yan Hu; Lei Fang; Tianzhen Zhang (Science China Life Sciences, 2023)

Correction to: Inhibition of mGluR5 alters BDNF/TrkB and GLT‑1 expression in the prefrontal cortex and hippocampus and ameliorates PTSD‑like behavior in rats - Shuyue Cheng; Jingjing Xu; Wei Wang; Rui Wang; Haonan Li; Zhijun Jiang; Dexiang Liu; Fang Pan (Psychopharmacology, 2023)

PcCLCg is involved in the accumulation of Cl− in shoots for osmotic adjustment and salinity resistance in the Cl−-tolerant xerophyte Pugionium cornutum - Yan-Nong Cui; Zi-Ru Lin; Mei-Mei Cai; Rui-Wen Liu; Suo-Min Wang; Qing Ma (Plant and Soil, 2023)

Mitochondrial Hydrogen Peroxide Activates PTEN and Inactivates Akt Leading to Autophagy Inhibition-Dependent Cell Death in Neuronal Models of Parkinson’s Disease - Qianyun Yu; Ruijie Zhang; Tianjing Li; Liu Yang; Zhihan Zhou; Long Hou; Wen Wu; Rui Zhao; Xiaoling Chen; Yajie Yao; Shile Huang; Long Chen (Molecular Neurobiology, 2023)

Study on of structural style of fault zone and reservoir characteristics in the northern slope of Tazhong Uplift, Tarim Basin, China - Rui Zhao; Yuan Kang; Jun Han; Xiuxiang Zhu; Teng Zhao; Yuqing Liu; Chongyang Xiao; Shang Deng; Zhixing Ru; Yingtao Li (Carbonates and Evaporites, 2023)

A joint application of semi-airborne and in-tunnel geophysical survey in complex limestone geology - Rui Liu; Huaifeng Sun; Dong Liu; Xiaoming Wang; Xiaosheng Zhou; Yu Zhao; Xinyu Zhao; Yang Yang; Guang Yang; Hanwu Sun (Bulletin of Engineering Geology and the Environment, 2023)

Large-scale characteristics of thermokarst lakes across the source area of the Yellow River on the Qinghai-Tibetan Plateau - Wen-hui Liu; Guang-hao Zhou; Hai-rui Liu; Qing-peng Li; Chang-wei Xie; Qing Li; Jian-yun Zhao; Qi Zhang (Journal of Mountain Science, 2023)

Diffusion mechanism of deep shale gas and its carbon isotope fractionation: a combined simulated and mathematical analysis - Yu Zou; Guojian Wang; Cheng Tao; Rui Zhou; Shangqing Zhang; Dongna Liu; Xiaohui Lin; Xuying Zheng (Geosciences Journal, 2023)

Spatial Equity of Basic Education Resources and Coordinated Regional Development in Xinjiang, China - Tao Han; Jie Fan; Rui Guo; Yong Sun; Dong Chen; Baoying Liu; Yanan Lian (Chinese Geographical Science, 2023)

Spatial-temporal Coupling Analysis of Economic Development-Social Development-Government Governance in Xinjiang, China - Haifeng Hu; Yong Sun; Hao Zhao; Baoyin Liu; Rui Guo (Chinese Geographical Science, 2023)

Experimental study on flow and heat transfer of supercritical carbon dioxide in zigzag channels with bending angle 30° for advanced nuclear systems - Sheng-hui Liu; Rui-long Liu; Yan-ping Huang; Xiao-liang Zhu; Liu Yang; Jia Tang; Bin Han; Tian-yang Xing; Xue-bin Zhao (Annals of Nuclear Energy, 2023)

2,4-Dinitrotoluene (2,4-DNT) exposure induces liver developmental damage and perturbs lipid metabolism and oxygen transport gene expression in zebrafish (Danio rerio) - Liangxia Su; Hang Sha; Jun Liu; Le Yu; Huanhuan Li; Rui Wang (Environmental Science and Pollution Research, 2023)

Visualizing the intellectual structure and evolution of carbon neutrality research: a bibliometric analysis - Qi Zhang; Yiman Xiao; Yuting Liu; Tingqin Deng; Zhenghao Li; Rui Li (Environmental Science and Pollution Research, 2023)

ZNRF2 as an oncogene is transcriptionally regulated by CREB1 in breast cancer models - Jin-Tao Liu; Zhen-Xuan Sun; Rui Zhong; Yi-Dan Zhang; Teng Wang; Yu-Dong Hou; Jian-Heng Bao; Lei Zhang; Bo Chen (Human Cell, 2023)

Subassembly Partition of Hull Block Based on Two-Dimensional PSO Algorithm - Bo Liu; Rui Li; Ji Wang; Yujun Liu; Sheng Li (Journal of Marine Science and Engineering, 2023)
Subassembly partition is an important process in hull block building as it greatly affects the efficiency and quality of the assembly work. Recently, an experience-based method has been widely applied to the subassembly partition process, which consumes much design time and manpower, thus causing more challenges toward a more highly automated and efficient stage in this process. To shorten the gap, an automated subassembly partition method is presented in this study. First, the assembly information model is defined with essential attributes and topological relations of the parts. Second, an optimization model is established with consideration of a trade-off between the intra-cluster cohesion and cluster number on the premise of satisfying certain constraints. After that, considering the fuzziness and diversity of the subassembly partition problem, a two-dimensional coding discrete particle swarm optimization (PSO) algorithm is developed. Finally, two blocks are demonstrated as instances to verify the proposed method, and the results show that the proposed method is feasible and applicable to the block with a flat structure.

TEAD4 predicts poor prognosis and transcriptionally targets PLAGL2 in serous ovarian cancer - Xin Tong; Yi-Si Liu; Rui Tong; Wei-Wei Tang; Xue-Mei Li; Chun-Yan Wang; Yong-Peng Wang (Human Cell, 2023)

A testis-specific gene doublesex is involved in spermatogenesis and early sex differentiation of the Chinese mitten crab Eriocheir sinensis - Long Wang; Zhi-Qiang Liu; Ke-Yi Ma; Jing-Rui Tao; Xiang Fang; Gao-Feng Qiu (Aquaculture, 2023)

Free and conjugated forms of metabolites are indispensable components of steroids: The first evidence from an estuarine food web - Shan Liu; Ru Xu; Yun-Feng Pan; Qian-Yi Huang; Nian-Nian Wu; Heng-Xiang Li; Lang Lin; Rui Hou; Xiang-Rong Xu (Water Research, 2023)

Evaluating the impact of sky view factor and building shadow ratio on air temperature in different residential and commercial building scenarios: A case study of Beijing, China - Qiang Chen; Rui Liu; Qianhao Cheng; Yunhao Chen; Shisong Cao; Mingyi Du; Kangning Li (Urban Climate, 2023)

Different characteristics of soil CH4 emissions and methanogenic communities in paddy fields under gradually and abruptly elevated CO2 concentrations - Yuanyuan Wang; Zhenghua Hu; Lidong Shen; Guihua Lu; Rui Cao; Kezhi Zheng; Chao Liu; Zhurong Wu; Shuqi He (Soil Biology and Biochemistry, 2023)

Short-term effect of apparent temperature on daily hospitalizations for osteoporotic fractures in Beijing, China: A retrospective observational study - Shuai Lu; Xuejiao Liu; Yanlin Niu; Feng Li; Maoqi Gong; Yejun Zha; Qingchen Chao; Bo Lu; Baichao Zhang; Ning Li; Jia Chen; Qiyong Liu; et al. (Science of The Total Environment, 2023)

Underestimation of biomass burning contribution to PM2.5 due to its chemical degradation based on hourly measurements of organic tracers: A case study in the Yangtze River Delta (YRD) region, China - Qing Li; Kun Zhang; Rui Li; Liumei Yang; Yanan Yi; Zhiqiang Liu; Xiaojuan Zhang; Jialiang Feng; Qiongqiong Wang; Wu Wang; Ling Huang; Yangjun Wang; et al. (Science of The Total Environment, 2023)

The hybridization origin of the Chinese endemic herb genus Notopterygium (Apiaceae): Evidence from population genomics and ecological niche analysis - Yun Jia; Mi-Li Liu; Jordi López-Pujol; Rui-Wen Jia; Yi-Xuan Kou; Ming Yue; Tian-Xia Guan; Zhong-Hu Li (Molecular Phylogenetics and Evolution, 2023)

Growth, nutrient uptake and transcriptome profiling of rice seedlings in response to mixed provision of ammonium- and nitrate-nitrogen - Youqiang Fu; Xuhua Zhong; Chusheng Lu; Kaiming Liang; Junfeng Pan; Xiangyu Hu; Rui Hu; Meijuan Li; Qunhuan Ye; Yanzhuo Liu (Journal of Plant Physiology, 2023)

Examining moisture contribution for precipitation in response to climate change and anthropogenic factors in Hengduan Mountain Region, China - Xingxing Zhang; Zhaofei Liu; Yubo Liu; Liguang Jiang; Rui wang; Hou Jiang; Jing Li; Qiuhong Tang; Zhijun Yao (Journal of Hydrology, 2023)

Driving forces and variation in water footprint before and after the COVID-19 lockdown in Fujian Province of China - Fan Yu; Yuan Wang; Xin Liu; Jinru Yu; Dandan Zhao; Haijun Deng; Bin Guo; Rui Shi; Bowei Wu; Huayang Chen (Journal of Cleaner Production, 2023)

Diversity and distribution variation of urban spontaneous vegetation with distinct frequencies along river corridors in a fast-growing city - Xiaopeng Li; Sining Zhang; Rui Huang; Li Feng; Sihui Xu; Baichuan Liu (Journal of Environmental Management, 2023)

Particulate matter capturing over manganese dioxides with different crystal structures - Rui Liu; Huan-Huan Yang; Hao Zhou; Xianliang Yi; Yang Liu (Journal of Environmental Sciences, 2023)

Abiotic transformation of synthetic progestins in representative soil mineral suspensions - Xingjian Yang; Rui Wang; Zhili He; Xiong Dai; Xiuping Jiang; He Liu; Yongtao Li (Journal of Environmental Sciences, 2023)

Multiple evaluations of atmospheric behavior between Criegee intermediates and HCHO: Gas-phase and air-water interface reaction - Tianlei Zhang; Mingjie Wen; Chao Ding; Yongqi Zhang; Xiaohui Ma; Zhuqing Wang; Makroni Lily; Junhai Liu; Rui Wang (Journal of Environmental Sciences, 2023)

Improvement of soybean meal quality by one-step fermentation with mixed-culture based on protease activity - Chuan Wang; Xiaozhi Qiu; Rui Hou; Jun Liu; Li Li; Xiang Mao (Innovative Food Science & Emerging Technologies, 2023)

Cyclical water vapor sorption-induced structural alterations of mine roof shale - Ang Liu; Shimin Liu; Rui Zhang; Guijie Sang; Kaiwen Xia (International Journal of Coal Geology, 2023)

High-resolution records of sea surface temperature and salinity in the East China Sea over the past 14.2 kyr: Implication from alkenone and its hydrogen isotopes - Rui Zhang; Wenlong Pei; Yipeng Wang; Xinling Wang; Jiayue Wang; Tiegang Li; James Russell; Fan Zhang; Zhiyong Liu; Minglei Guan; Qi Han; Chenyang Tian; et al. (Global and Planetary Change, 2023)

Photo-assisted thermal catalysis for methanol synthesis from methane oxidation on Cu-MOR/g-C3N4 - Yan-Qun Chen; Rui-Xin Zhang; Miao Ren; Ya-Xin Jin; Wen-Jing Wang; Jia-Yao Feng; Zhi-Hua Gao; Zhi-Feng Yan; Yi-Ming Liu; Wei Huang; Lei Liu; Zhi-Jun Zuo (Fuel, 2023)

A practical application of front-face synchronous fluorescence spectroscopy to rapid, simultaneous and non-destructive determination of piperine and multiple adulterants in ground black and white pepper (Piper nigrum L.) - Zhao-Xi Liu; Shu-Rui Xiong; Shu-Hua Tang; Ying Wang; Jin Tan (Food Research International, 2023)

Antioxidant and anti-inflammatory activities of rape bee pollen after fermentation and their correlation with chemical components by ultra-performance liquid chromatography-quadrupole time of flight mass spectrometry-based untargeted metabolomics - Huifang Zhang; Xiaoling Zhu; Qian Huang; Li Zhang; Xiaohua Liu; Rui Liu; Qun Lu (Food Chemistry, 2023)

Wide-Scope Multi-residue analysis of pesticides in beef by gas chromatography coupled with quadrupole Orbitrap mass spectrometry - Xu Pang; Jing Qiu; Zhaoyang Zhang; Pi Li; Jiangtao Xing; Xin Su; Guiqiao Liu; Changyuan Yu; Rui Weng (Food Chemistry, 2023)

A dispersive solid-phase extraction method for the determination of Aristolochic acids in Houttuynia cordata based on MIL-101(Fe): An analytes-oriented adsorbent selection design - Rui Cheng; Xuejin Mao; Jiaying Yu; Fan Liu; Lan Guo; Dongmei Luo; Yiqun Wan (Food Chemistry, 2023)

Preparation and characterization of V-type starch nanoparticles by an oil-water interface method - Hao Lu; Xiaoyang He; Yang Qin; Na Ji; Lei Dai; Liu Xiong; Rui Shi; Tao Wang; Qingjie Sun (Food Hydrocolloids, 2023)

Acrylamide in food: Occurrence, metabolism, molecular toxicity mechanism and detoxification by phytochemicals - Fangfang Yan; Li Wang; Li Zhao; Chengming Wang; Qun Lu; Rui Liu (Food and Chemical Toxicology, 2023)

Improved soil surface nitrogen balance method for assessing nutrient use efficiency and potential environmental impacts within an alpine meadow dominated region - Ying Li; Baolin Li; Yecheng Yuan; Yan Liu; Rui Li; Wei Liu (Environmental Pollution, 2023)

Ciprofloxacin degradation performances and mechanisms by the heterogeneous electro-Fenton with flocculated fermentation biochar - Yanchao Jin; Peiwen Huang; Xiongjian Chen; Li-Ping Li; Chun-Yan Lin; Xiao Chen; Rui Ding; Jianxi Liu; Riyao Chen (Environmental Pollution, 2023)

Insights into the bacterial and archaeal population dynamics in the deep-sea hydrothermal sediments exposed to lights with different wavelengths - Ge Liu; Yeqi Shan; Rui Liu; Chaomin Sun (Deep Sea Research Part I: Oceanographic Research Papers, 2023)

Effect of SO2 on HCl removal over ethanol-hydrated CaO adsorbent: Mechanism of competitive adsorption and product layer shielding - Xiaoshuo Liu; Rui Wang; Yuqing Wang; Xunlei Ding; Ao Shen; Yufeng Duan; Shilin Zhao (Chemical Engineering Journal, 2023)

Hybrid plasma-thermal system for methane conversion to ethylene and hydrogen - Rui Liu; Yingzi Hao; Tong Wang; Li Wang; Annemie Bogaerts; Hongchen Guo; Yanhui Yi (Chemical Engineering Journal, 2023)

An injectable and rapidly degraded carboxymethyl chitosan/polyethylene glycol hydrogel for postoperative antiadhesion - Meiyue Wang; Sen Lin; Mengzhe Liu; Jing Jiao; Hongyan Mi; Jingjing Sun; Yiming Liu; Ruiying Guo; Sirui Liu; Haojie Fu; Yanyu Yang; Rui Li (Chemical Engineering Journal, 2023)

A novel reduced graphene oxide/polypyrrole conductive ceramic membrane enhanced electric field membrane bioreactor: Mariculture wastewater treatment performance and membrane fouling mitigation - Rui Wang; Hong You; Zhipeng Li; Binghan Xie; Shaojie Qi; Jing Zhu; Qiqing Qin; Han Wang; Jinxu Sun; Yi Ding; Yuhong Jia; Feng Liu (Bioresource Technology, 2023)

Biomarkers of aging - Hainan Bao; Jiani Cao; Mengting Chen; Min Chen; Wei Chen; Xiao Chen; Yanhao Chen; Yu Chen; Yutian Chen; Zhiyang Chen; Jagadish K. Chhetri; Yingjie Ding; et al. (Science China Life Sciences, 2023)

Exogenous methyl jasmonate and cytokinin antagonistically regulate lignin biosynthesis by mediating CsHCT expression in Camellia sinensis - Chun-Fang Liu; Ni Yang; Rui-Min Teng; Jing-Wen Li; Yi Chen; Zhi-Hang Hu; Tong Li; Jing Zhuang (Protoplasma, 2023)

Increased hypertension risk for the elderly with high blood levels of strontium and lead - Jiebao Zhang; Chunfang Xu; Yan Guo; Xingyi Jin; Zi Cheng; Qi Tao; Lin Liu; Rui Zhan; Xuemin Yu; Hongjuan Cao; Fangbiao Tao; Jie Sheng; et al. (Environmental Geochemistry and Health, 2023)

Distress mechanism and treatment measures in construction of large cross-section tunnel passing through Q2 soft-plastic loess layer - Qiuyang Hong; Hongpeng Lai; Yuyang Liu; Rui Chen (Bulletin of Engineering Geology and the Environment, 2023)

Impact of clayey sediment compaction on pore water evolution and the release of iron - Yanjun Liu; Teng Ma; Juan Chen; Ziqi Peng; Cong Xiao; Wenkai Qiu; Rui Liu; Yao Du (Applied Geochemistry, 2023)

Identifying the water quality variation characteristics and their main driving factors from 2008 to 2020 in the Yellow River Basin, China - Shasha Liu; Yue Qiu; Rui Fu; Yun Liu; Chengyu Suo (Environmental Science and Pollution Research, 2023)

Study on the combustion, entrainment, and plume flow behaviors of annular pool fires - Ping Huang; Rui Zhang; Longxing Yu; Chunxiang Liu (Environmental Science and Pollution Research, 2023)

Recent advances in CO2 fixation by microalgae and its potential contribution to carbon neutrality - Peilun Xu; Jun Li; Jun Qian; Bang Wang; Jin Liu; Rui Xu; Paul Chen; Wenguang Zhou (Chemosphere, 2023)

Evaluation method of rowing performance and its optimization for UAV-based shot seeding device on rice sowing - Wei Liu; Zhiyan Zhou; Xuelang Xu; Qingyu Gu; Shuaishuai Zou; Weizhuo He; Xiwen Luo; Junhao Huang; Jianqin Lin; Rui Jiang (Computers and Electronics in Agriculture, 2023)

Developing thermal infrared de-ghost and multi-level nested conglutinated segmentation algorithm for detection of rice seed setting rate - Jun Zhou; Xiangyu Lu; Rui Yang; Yaliang Wang; Huizhe Chen; Jianxun Shen; Mengyuan Chen; Zhenjiang Zhou; Fei Liu (Computers and Electronics in Agriculture, 2023)

Abundance and characteristics of microplastics in the Wanquan River estuary, Hainan Island - Tuan-Tuan Wang; Wang-Qing Tang; Dong-Hai Wu; Xin-Rui Yu; Guang-Yu Wang; Xing-Wei Cai; Shuai Shao; Sai Wang; Ling Mo; You-Sheng Liu; Guang-Guo Ying; Zhong-Bing Chen (Marine Pollution Bulletin, 2023)

The effect of repeated energy inputs on the release profiles of extracellular organic substances in sewage sludge - Rui Liu; Ying Xu; Liang Song; Shiyu Liu; Zixuan Liang; Danyang Zhu; Xiaohu Dai (Water Research, 2023)

Aggregation and construction mechanisms of microbial extracellular polymeric substances with the presence of different multivalent cations: Molecular dynamic simulation and experimental verification - Sainan Peng; Zhiyue Wang; Pingfeng Yu; Guiying Liao; Rui Liu; Dongsheng Wang; Weijun Zhang (Water Research, 2023)

Regulation of denitrification performance and microbial topology by lights: Insight into wavelength effects towards microbiota - Yang Liao; Jiyong Bian; Shiyu Miao; Siqi Xu; Rui Li; Ruiping Liu; Huijuan Liu; Jiuhui Qu (Water Research, 2023)

Emerging trends in pectin functional processing and its fortification for synbiotics: A review - Rui Sun; Yefan Niu; Menghui Li; Yuanye Liu; Kai Wang; Zhenpeng Gao; Zhouli Wang; Tianli Yue; Yahong Yuan (Trends in Food Science & Technology, 2023)

Post COVID-19 pandemic recovery of intracity human mobility in Wuhan: Spatiotemporal characteristic and driving mechanism - Rui An; Zhaomin Tong; Xiaoyan Liu; Bo Tan; Qiangqiang Xiong; Huixin Pang; Yaolin Liu; Gang Xu (Travel Behaviour and Society, 2023)

Association between exposure to ambient air pollution and semen quality: A systematic review and meta-analysis - Ruijun Xu; Yanling Zhong; Rui Li; Yingxin Li; Zihua Zhong; Tingting Liu; Qiling Wang; Ziquan Lv; Suli Huang; Yong-Gang Duan; Xinzong Zhang; Yuewei Liu (Science of The Total Environment, 2023)

Atmospheric microplastics at a southern China metropolis: Occurrence, deposition flux, exposure risk and washout effect of rainfall - Zhen Yuan; Chenglei Pei; Hengxiang Li; Lang Lin; Shan Liu; Rui Hou; Ran Liao; Xiangrong Xu (Science of The Total Environment, 2023)

How to achieve carbon neutrality while maintaining economic vitality: An exploration from the perspective of technological innovation and trade openness - Rui Jiang; Bangcheng Liu (Science of The Total Environment, 2023)

Bibenzyls and lignans from Dendrobium devonianum and their immunosuppressive activities - Jinyu Li; Xinyue Zhang; Yumeng Li; Bo Liu; Rui Zhan (Phytochemistry Letters, 2023)

A crack characterization model for subsea pipeline based on spatial magnetic signals features - Jiaxing Xin; Rui Li; Jinzhong Chen; Run-kun Lu; Chang Liu; Zhengda Su; Renyang He; Hongwu Zhu (Ocean Engineering, 2023)

Influencing mechanisms of gas bubbles on propagation characteristics of leakage acoustic waves in gas-liquid two-phase flow - Yuan Xue; Linjing Yue; Rui Ding; Shufang Zhu; Cuiwei Liu; Yuxing Li (Ocean Engineering, 2023)

Responses of agricultural drought to meteorological drought under different climatic zones and vegetation types - Peng Sun; Ruilin Liu; Rui Yao; Hao Shen; Yaojin Bian (Journal of Hydrology, 2023)

Multi-model analysis of historical runoff changes in the Lancang-Mekong River Basin – Characteristics and uncertainties - Yuxin Li; Aifang Chen; Ganquan Mao; Penghan Chen; Hao Huang; Hong Yang; Zifeng Wang; Kai Wang; He Chen; Ying Meng; Rui Zhong; Pengfei Wang; et al. (Journal of Hydrology, 2023)

Regulating the reaction pathway of nZVI to improve the decontamination performance through magnetic spatial confinement effect - Hai-Yuan Chi; Xiao-Xia Zhou; Min-Rong Wu; Wan-yu Shan; Jing-fu Liu; Jin-quan Wan; Bing Yan; Rui Liu (Journal of Hazardous Materials, 2023)

Interprovincial differences in the historical peak situation of building carbon emissions in China: Causes and enlightenments - Rui Li; Yanhui Yu; Weiguang Cai; Qiqi Liu; Yuan Liu; Haonan Zhou (Journal of Environmental Management, 2023)

Optimization and multi-uncertainty analysis of best management practices at the watershed scale: A reliability-level based bayesian network approach - Jincheng Li; Mengchen Hu; Wenjing Ma; Yong Liu; Feifei Dong; Rui Zou; Yihui Chen (Journal of Environmental Management, 2023)

Environmental risk of tailings pond leachate pollution: Traceable strategy for leakage channel and influence range of leachate - Bowen Shi; Xixi Li; Weiwu Hu; Beidou Xi; Shengrong Liu; Di Liu; Congchao Xu; Zihao Jia; Rui Li (Journal of Environmental Management, 2023)

An overview on constructed wetland-microbial fuel cell: Greenhouse gases emissions and extracellular electron transfer - Liangjing Zhang; Yunlong Liu; Shucong Lv; Rui Wang; Yu Wang; Kuixuan Lin; Xiaokun Hu; Yuchen Liu; Zhaojun Dong; Lusan Liu (Journal of Environmental Chemical Engineering, 2023)

Peroxymonosulfate activation by Cu2O@CuO nanowires array-based electroactive filter for efficient ofloxacin removal - Rongshuai Wang; Haoqi Wang; Chongying Zhong; Qing Liu; Rui Feng; Yanxia Zhao; Meng Sun; Liangguo Yan; Tao Yan (Journal of Environmental Chemical Engineering, 2023)

Catalytic performances of Cu-ZK-5 zeolites with different template agents in NH3-SCR - Yuchao Zang; Qing Li; Yalian Bi; Caixia Liu; Yan Zhang; Yanhua Wang; Min Zhang; Qingling Liu; Ziyin Zhang; Rui Han (Journal of Environmental Chemical Engineering, 2023)

Amorphous nanophosphates of dual-metal (Co and Ni) for the decomposition of ozone under humid conditions - Qian Zhang; Jifei Liao; Guangzhi Du; Yu Lin; Xiaoqiong Liu; Rui Wang; Lingyu Huang; Wenyan Xiao; Jiahao Chen; Yan Fu (Journal of Environmental Chemical Engineering, 2023)

A study on equivalent permeability models for tree-shaped fractures with different geometric parameters - Mingyang Wu; Rui Song; Zhengwen Zhu; Jianjun Liu (Gas Science and Engineering, 2023)

Thermodynamics and inhibition mechanism of imidazolium-based ionic liquids for inhibiting spontaneous combustion of iron sulfide - Hui Liu; Xiaoqing Gou; Kai Pan; Rui Huang; Zhihui Lang; Dong Ye; Xin Wang; Haining Wang (Fuel, 2023)

New insight into the role of the emulsified diesel droplet size in low rank coal flotation - Jincheng Liu; Rui Zhang; Xicheng Bao; Yesheng Hao; Xiahui Gui; Yaowen Xing (Fuel, 2023)

Insights into the HCl formation and volatilization mechanism from organochlorine in coal: A DFT study - Xiaoshuo Liu; Rui Wang; Tianfang Huang; Xinze Geng; Xunlei Ding; Yufeng Duan; Shilin Zhao (Fuel, 2023)

Advantageous Role of N-doping on K@Al in COS/CS2 Hydrolysis: Diminished Oxygen Mobility and Rich basic sites - Rui Cao; Xueqian Wang; Ping Ning; Yibing Xie; Langlang Wang; Yixing Ma; Xiang Li; Hui Zhang; Jingye Liu (Fuel, 2023)

Metal-carbonate interface promoted activity of Ag/MgCO3 catalyst for aqueous-phase formaldehyde reforming into hydrogen - Qiaojuan Wang; Jianyue Wang; Wenjuan Rui; Dan Yang; Xiaoyue Wan; Chunmei Zhou; Renhong Li; Wen Liu; Yihu Dai; Yanhui Yang (Fuel, 2023)

The effect of clay type and solid wettability on bitumen extraction from Canadian oil sands - An Li; Rui Li; Ci Yan; Han Wang; Qingxia Liu; Jacob H. Masliyah; Hongbo Zeng; Zhenghe Xu (Fuel, 2023)

A colorimetric smartphone-based sensor for on-site AA detection in tropical fruits using Fe-P/N C single-atom nanoenzyme - Ying Li; Rida Javed; Rui Li; Yuyang Zhang; Ziyue Lang; Hongbin Zhao; Xing Liu; Hongmei Cao; Daixin Ye (Food Chemistry, 2023)

Fabrication of starch-based emulsion gel beads by an inverse gelation technique for loading proanthocyanidin and curcumin - Xiaotong Bu; Minghang Guan; Lei Dai; Na Ji; Yang Qin; Xingfeng Xu; Liu Xiong; Rui Shi; Qingjie Sun (Food Hydrocolloids, 2023)

Evaluation of novel isolates of Lacticaseibacillus rhamnosus Probio-M9 derived through space mutagenesis - Jingfang Yang; Yue Sun; Xueyan Lei; Lixia Zhao; Rui Luo; Wenjun Liu (Food Bioscience, 2023)

Inhibition of human sulfotransferases (SULTs) by per- and polyfluoroalkyl substances (PFASs) and structure-activity relationship - Yong-Zhe Liu; Kai Yang; Wei Zhang; Qian zhang; Tong-Feng Liu; Tong Xu; Yang Li; Rui-Xue Ran; Kun Yang; Yun-Feng Cao; Zhong-Ze Fang (Food and Chemical Toxicology, 2023)

Long-term exposure to fine particulate matter and site-specific cancer mortality: A difference-in-differences analysis in Jiangsu province, China - Zhaoyu Fan; Yingxin Li; Jing Wei; Gongbo Chen; Rui Wang; Ruijun Xu; Tingting Liu; Ziquan Lv; Suli Huang; Hong Sun; Yuewei Liu (Environmental Research, 2023)

Environmental fate of microplastics in an urban river: Spatial distribution and seasonal variation - Ting Li; Kai Liu; Rui Tang; Jun-Rong Liang; Lei Mai; Eddy Y. Zeng (Environmental Pollution, 2023)

Behaviour of FRP spiral-confined concrete and contribution of FRP longitudinal bars in FRP-RC columns under axial compression - Jun-Jie Zeng; Yu-Yi Ye; Wei-Te Liu; Yan Zhuge; Yue Liu; Qing-Rui Yue (Engineering Structures, 2023)

Building form and outdoor thermal comfort: Inverse design the microclimate of outdoor space for a kindergarten - Rui Sun; Junjie Liu; Dayi Lai; Wei Liu (Energy and Buildings, 2023)

Managing iodine and tin based defects for efficient and stable mixed Sn-Pb perovskite solar cells - Yanjun Xing; Zhiqiang Deng; Tonghui Guo; Zequn Zhang; Qidong Tai; Rui Zhao; Jiaxing Xiong; Qiuxiang Wang; Like Huang; Xiaohui Liu; Ziyang Hu; Yuejin Zhu; et al. (Chemical Engineering Journal, 2023)

Modulation of the interfacial properties of TiN coatings to generate Rigid-Flexible SEI for better SiO anodes - Hebang Shi; He Zhang; Rui Wang; Ming Liu; Zihan Shen; Jingbo Chen; Binbin Wu; Maoqiao Xiang; Jun Li; Huigang Zhang; Pengpeng Lv; Qingshan Zhu (Chemical Engineering Journal, 2023)

In situ rapid and deep self-reconstruction of Fe-doped hydrate NiMoO4 for stable water oxidation at high current densities - Yijie Zhang; Rui Yao; Yun Wu; Qiang Zhao; Jinping Li; Guang Liu (Chemical Engineering Journal, 2023)

Highly stability Cu+ species in hollow Cu2O nanoreactors by modulating cavity size for CO2 electroreduction to C2+ products - Rui Zhang; Feifei Chen; Haokun Jin; Yong Zhang; Xiaoya Hao; Yingda Liu; Tianming Feng; Xinghua Zhang; Zunming Lu; Weihua Wang; Feng Lu; Hong Dong; et al. (Chemical Engineering Journal, 2023)

Boosting photocatalytic ammonia synthesis performance over OVs-Rich Ru/W18O49: Insights into the roles of oxygen vacancies in enhanced hydrogen spillover effect - Lulu Zhang; Rui Li; Luyao Cui; Zijun Sun; Lijun Guo; Xiaochao Zhang; Yunfang Wang; Yawen Wang; Zhuobin Yu; Tao Lei; Xuan Jian; Xiaoming Gao; et al. (Chemical Engineering Journal, 2023)

A novel solvent system of polyamides achieves new application in ZIBs by aggregation induced Lewis acid-base centers - Murong Xi; Zhenjie Liu; Rui Sheng; Jiafeng Zhu; Yong Guo; Juan Ding; Xingchao Wang; Yue Zhang; Lei Wang; Zhipeng Sun; Wenjun Zhang; Jiulin Wang; et al. (Chemical Engineering Journal, 2023)

An ultra-thin chemical vapor deposited polymer interlayer to achieve highly improved stability of perovskite solar cell - Jing Zhou; Xueying Tian; Rui Chen; Weitao Chen; Xin Meng; Xinyu Guan; Jianan Wang; Sanwan Liu; Fumeng Ren; Shasha Zhang; Yiqiang Zhang; Zonghao Liu; et al. (Chemical Engineering Journal, 2023)

Ultra-thin hierarchical porous carbon coated metal phosphide self-assembled efficient tri-functional electrodes for overall water splitting and rechargeable zinc-air batteries - Rui He; Tuo Lu; Nengneng Xu; Guicheng Liu; Yanxing Zhang; Jinli Qiao (Chemical Engineering Journal, 2023)

Magnetic hydrochar derived from waste lignin for thallium removal from wastewater: Performance and mechanisms - Huabin Wang; Ran Duan; Lin Ding; Lin Tian; Ying Liu; Yong Zhang; Rui Xu (Bioresource Technology, 2023)

Co-cultivation of microalgae-activated sludge for municipal wastewater treatment: Exploring the performance, microbial co-occurrence patterns, microbiota dynamics and function during the startup stage - Xin Li; Jian Liu; Jiansong Tian; Zhicheng Pan; Yangwu Chen; Fei Ming; Rui Wang; Lin Wang; Houzhen Zhou; Junjie Li; Zhouliang Tan (Bioresource Technology, 2023)

The impact patterns of classroom lighting parameters on visual fatigue and a mathematical model - Rui Dang; Yuxing Liu; Suo Chang (Building and Environment, 2023)

Determination of Rock Mass Parameters for the RHT Model Based on the Hoek–Brown Criterion - Shenglin Li; Tianlong Ling; Dianshu Liu; Shufeng Liang; Rui Zhang; Bo Huang; Kai Liu (Rock Mechanics and Rock Engineering, 2023)

Inhibition of mGluR5 alters BDNF/TrkB and GLT-1 expression in the prefrontal cortex and hippocampus and ameliorates PTSD-like behavior in rats - Shuyue Cheng; Jingjing Xu; Wei Wang; Rui Wang; Haonan Li; Zhijun Jiang; Dexiang Liu; Fang Pan (Psychopharmacology, 2023)

The role of tyrosine hydroxylase within dapoxetine-assisted therapy against premature ejaculation - Xi Liu; Tianle Zhu; Pan Gao; Jingjing Gao; Rui Gao; Hui Jiang; Xiansheng Zhang (Molecular Biology Reports, 2023)

Molecular Hydrogen: an Emerging Therapeutic Medical Gas for Brain Disorders - Chongyun Wu; Peibin Zou; Shu Feng; Ling Zhu; Fanghui Li; Timon Cheng-Yi Liu; Rui Duan; Luodan Yang (Molecular Neurobiology, 2023)

Parameter Study on How the Cervical Disc Degeneration Affects the Segmental Instantaneous Centre of Rotation - Hong Zhang; Dacheng Sang; Bin Zhang; Ya-Nan Ren; Xin Wang; Jing-Jing Feng; Cheng-Fei Du; Baoge Liu; Rui Zhu (Journal of Medical and Biological Engineering, 2023)

Activating α7nAChR helps post-myocardial infarction healing by regulating macrophage polarization via the STAT3 signaling pathway - Xiao-Hui Niu; Rong-Hua Liu; Xiao Lv; Rui-Lin He; Fang-Zhou Lv; Shu-Jie Wu; Xu-Qing Li; Lei Li; Jia-Feng Lin (Inflammation Research, 2023)

Cross-subject aesthetic preference recognition of Chinese dance posture using EEG - Jing Li; Shen-rui Wu; Xiang Zhang; Tian-jian Luo; Rui Li; Ying Zhao; Bo Liu; Hua Peng (Cognitive Neurodynamics, 2023)

Energy and environmental performance evaluation of China's non-ferrous metals industry from the perspective of network structure - Rui Yang; Yujin Xu; Kaiyuan Liu (Clean Technologies and Environmental Policy, 2023)

Full genome sequence of a novel iflavirus from the aster leafhopper Macrosteles fascifrons - Jiajing Xiao; Kai Zhu; Rui Ma; Chunmin Zhang; Keliang Lv; Danfeng Ge; Renyi Liu (Virus Genes, 2023)

Long-term performance analysis of BDS-3 precise point positioning (PPP-B2b) service - Shuang Sun; Min Wang; Changjian Liu; Xin Meng; Rui Ji (GPS Solutions, 2023)

Moderation device design for detecting hidden highly enriched uranium based on D-T neutron generator - Shang-Rui Jiang; Guang-Yu Shi; Si-Yuan Chen; Shi-Wei Jing; Chao Liu (Annals of Nuclear Energy, 2023)

Determination and prediction of digestible energy, metabolizable energy, and standardized ileal digestibility of amino acids in barley for growing pig - Rui Li; Mingzhou Tian; Ganyi Feng; Gaifeng Hou; Xianji Jiang; Gang Yang; Qiang Xiang; Xiaojie Liu; Cimi Long; Ruilin Huang; Yulong Yin (Animal Feed Science and Technology, 2023)

Determination of lead in Gentiana rigescens and evaluation of the effect of lead exposure on the liver protection of the natural medicine - Rui Zhang; Caixia Yan; Xiaofang Yang; Kan Hu; Fangfang Hao; Shengchun Yang; Qingwen Deng; Zhenjuan Duan; Yong Liu; Xiaodong Wen (Analytica Chimica Acta, 2023)

Quantify the effect of manure fertilizer addition and optimal nitrogen input on rainfed wheat yield and nitrogen requirement using nitrogen nutrition index - Pengzhao Liu; Xingyu Guo; Dong Zhou; Qi Zhang; Xiaolong Ren; Rui Wang; Xiaoli Wang; Xiaoli Chen; Jun Li (Agriculture, Ecosystems & Environment, 2023)

Circ_HIPK3 Inhibits H2O2-Induced Lens Epithelial Cell Injury in Age-Related Cataract Depending on the Regulation of miR-495-3p/HDAC4 Pathway - Sihui Chen; Minghong Wang; Rui Jian; Hui Li; Guoli Liu; Cuiyun Zhou; Yan Xiong; Wenqian Wang (Biochemical Genetics, 2023)

Immediate and long-term changes in the epidemiology, infection spectrum, and clinical characteristics of viral and bacterial respiratory infections in Western China after the COVID-19 outbreak: a modeling study - Tianshan Shi; Xin Zhao; Xiaoshu Zhang; Lei Meng; Donghua Li; Xinfeng Liu; Hongmiao Zheng; Deshan Yu; Tingrong Wang; Rui Li; Juansheng Li; Xiping Shen; et al. (Archives of Virology, 2023)

Modelling the spray range of rotating nozzles based on modified ballistic trajectory equation parameters - Rui Zhang; Yichuan Liu; Delan Zhu; Xiaomin Zhang; Fei Gao; Changjuan Zheng (Irrigation and Drainage, 2023)
The nozzle spray range is an important parameter in the design of sprinkler systems because it affects the wetted area and water application rate. In this study, the jet deformation parameter k jet , which can measure the mass and shape of the jet microelement, was investigated, and a spray range prediction model for a rotating nozzle was established based on the modified ballistic trajectory equation. A comparison verified the accuracy of the model, and the degree of influence of different factors on the spray range was analysed. The results showed the following: (1) The dimension of the jet deformation parameter k jet is the length L , which is a function of the nozzle diameter, working pressure and nozzle elevation angle. (2) The maximum mean absolute error and root mean square error of the current model at a nozzle elevation angle of 24° were 2.038 and 1.603, respectively, representing a maximum increase in prediction accuracy of 87% and 86.7%, respectively, over other models at the same angle. (3) A sensitivity analysis revealed that the factor with the greatest impact on the nozzle spray range was the nozzle diameter, and the smallest was the nozzle mounting height. (4) The maximum nozzle spray range was positively related to the nozzle diameter and working pressure, and the nozzle elevation angle varied at approximately 30° when the maximum range was reached. This study provides a reference for the design of sprinkler systems and the development of rotating nozzles.

Multifractal Analysis of the Structure of Organic and Inorganic Shale Pores Using Nuclear Magnetic Resonance (NMR) Measurement - Rui Yang; Weiqun Liu; Lingren Meng (Journal of Marine Science and Engineering, 2023)
The multifractal structure of shale pores significantly affects the occurrence of fluids and the permeability of shale reservoirs. However, there are few studies on the multifractal characteristics of shale pores that distinguish between organic and inorganic pores. In this study, we obtained the pore size distribution (PSD) of organic and inorganic shale pores separately by using a new NMR-based method and conducted a multifractal analysis of the structure of organic and inorganic shale pores based on PSD. We then investigated the geological significance of the multifractal characteristics of organic and inorganic shale pores using two multifractal characteristic parameters. The results showed that the structures of both organic and inorganic pores have multifractal characteristics. Inorganic pores have stronger heterogeneity and poorer connectivity compared to organic pores. The multifractal characteristics of inorganic pores significantly affect shale permeability and irreducible water saturation. Greater heterogeneity in the inorganic pore structure results in lower shale permeability and higher irreducible water saturation. Meanwhile, better connectivity leads to higher shale permeability and lower irreducible water saturation. The multifractal characteristics of organic pores significantly affect the shale adsorption capacity and have a weak impact on irreducible water saturation. Greater heterogeneity in the organic pore structure results in the shale having stronger adsorption capacity and higher irreducible water saturation The results also indicate that the multifractal characteristic parameters of inorganic pores can be regarded as an index for estimating the irreducible water saturation and flowback rate of fracturing fluid, and the multifractal characteristic parameters of organic pores can be regarded as an index for evaluating the quality of shale reservoirs.

Natural Frequency Analysis of Monopile Supported Offshore Wind Turbines Using Unified Beam-Column Element Model - Jian-Hong Wan; Rui Bai; Xue-You Li; Si-Wei Liu (Journal of Marine Science and Engineering, 2023)
Assessment of the natural frequency of the offshore wind turbine (OWT) system is a critical task in design to avoid resonance. The natural frequency of the monopile supported OWT may change during operation and needs to be calculated regularly. Conventional numerical methods separately model different components of the OWT system using various element types, which require tedious data manipulations and are inefficient to assess the changing natural frequency of the monopile supported OWTs. This paper develops a unified beam-column element by directly integrating the soil-pile interactions in element formulation. The proposed method is applicable for different components of the OWT system, including the rotor, the tower, the transition piece, and the monopile foundation, which enables an integrated and efficient OWT analysis by using only one type of element. The pile-soil interactions are directly considered in the element formulation. The tedious soil spring elements are avoided. Definitions and formulations of the proposed element are provided and the numerical solution procedure for the natural frequency analysis of OWTs is illustrated. The accuracy of the proposed element is validated against several closed-form solutions and the distributed spring model. The proposed method is also applied to analyze the natural frequencies of six OWTs in practice. The calculated results are consistent with the field measured data.

Diffusion simulation and risk assessment model establishment of chlorine gas leakage based on terrain conditions - Xiao-ting Ren; Xiao-ling Ma; Jiang-zheng Liu; Rui Liu; Chen-qian Zhao; Hao Wu; Zhao Wang; Chun-xu Hai; Xiao-di Zhang (Environmental Science and Pollution Research, 2023)

Study on the mechanical properties of coral sands with different particle gradations - Yuan-yi Chen; Yi Tang; Yun-fei Guan; Rui-ming Liu; Xun Han; Xian-qiang Zhao (Marine Georesources & Geotechnology, 2023)

The dissolution of polysaccharides and amino acids enhanced lactic acid production from household food waste during pretreatment process - Liang Song; Donghai Yang; Rui Liu; Shiyu Liu; Xiaohu Dai (Science of The Total Environment, 2023)

Pyrolysis temperature affects the physiochemical characteristics of lanthanum-modified biochar derived from orange peels: Insights into the mechanisms of tetracycline adsorption by spectroscopic analysis and theoretical calculations - Zhihao Chen; Bingfeng Lin; Yingping Huang; Yanbiao Liu; Yonghong Wu; Rui Qu; Cilai Tang (Science of The Total Environment, 2023)

Potential causes of partial-denitrification (PD) granular sludge breakdown under high nitrate loading rates - Rui Du; Qingtao Liu; Yongzhen Peng; Shenbin Cao (Science of The Total Environment, 2023)

Flow regime changes in the Lancang River, revealed by integrated modeling with multiple Earth observation datasets - Xingxing Zhang; Liguang Jiang; Zhaofei Liu; Cecile M.M. Kittel; Zhijun Yao; Daniel Druce; Rui Wang; Christian Tøttrup; Jun Liu; Hou Jiang; Peter Bauer-Gottwein (Science of The Total Environment, 2023)

Circ_0021573 acts as a competing endogenous RNA to promote the malignant phenotypes of human ovarian cancer cells - Lifang Liu; Bingkai Han; Lixia Liu; Hongying Cui; Hao Liu; Rui Jia; Xiaoyan Zhang; Xiaoxiao Lu (Reproductive Biology, 2023)

‘Yunnan’ quince rootstock promoted flower bud formation of ‘Abbé Fetel’ pear by altering hormone levels and PbAGL9 expression - Liu Cong; Hutian Ling; Shanshan Liu; Azheng Wang; Rui Zhai; Chengquan Yang; Zhigang Wang; Lingfei Xu (Journal of Plant Physiology, 2023)

Environment-friendly and efficient electrochemical degradation of sulfamethoxazole using reduced TiO2 nanotube arrays-based Ti membrane coated with Sb-SnO2 - Weichen Zeng; Han Zhang; Rui Wu; Luming Liu; Guibai Li; Heng Liang (Journal of Hazardous Materials, 2023)

Highly-efficient peroxydisulfate activation by polyaniline-polypyrrole copolymers derived pyrolytic carbon for 2,4-dichlorophenol removal in water: Coupling mechanism of singlet oxygen and electron transfer - Taigang Ma; Meijun Liu; Nnanake-Abasi O. Offiong; Jinhao Duan; Yuchun Liu; Hejun Ren; Rui Zhou (Journal of Hazardous Materials, 2023)

Screening of hazardous groundwater pollutants responsible for microbial ecological consequences by integrated nontargeted analysis and high-throughput sequencing technologies - Jian Li; Shihang Yu; Quanzhen Liu; Donghong Wang; Lei Yang; Jinsheng Wang; Rui Zuo (Journal of Hazardous Materials, 2023)

A critical review of adsorption isotherm models for aqueous contaminants: Curve characteristics, site energy distribution and common controversies - Qili Hu; Rui Lan; Liru He; Hengyuan Liu; Xiangjun Pei (Journal of Environmental Management, 2023)

Machine learning approaches to predict the apparent rate constants for aqueous organic compounds by ferrate - Shan-Shan Zheng; Wan-Qian Guo; Hao Lu; Qi-Shi Si; Bang-Hai Liu; Hua-Zhe Wang; Qi Zhao; Wen-Rui Jia; Tai-Ping Yu (Journal of Environmental Management, 2023)

Variability of fuel consumption and CO2 emissions of a gasoline passenger car under multiple in-laboratory and on-road testing conditions - Boya Zhou; Liqiang He; Shijian Zhang; Rui Wang; Luowei Zhang; Mengliang Li; Yu Liu; Shaojun Zhang; Ye Wu; Jiming Hao (Journal of Environmental Sciences, 2023)

Petrogenesis of Jurassic granites linked to crustal growth above the subduction zone in the Lesser Xing’an Range (LXR), NE China - Xian Chen; Rui-Zhong Hu; Liang Liu; De-Hui Zhang (Journal of Asian Earth Sciences, 2023)

Combine thermal processing with polyvalent phage LPEK22 to prevent the Escherichia coli and Salmonella enterica contamination in food - Yue Zhang; Geng Zou; Md. Sharifull Islam; Kun Liu; Suqiang Xue; Zhiyong Song; Yingwang Ye; Yang Zhou; Yuanguo Shi; Shaozhong Wei; Rui Zhou; Huanchun Chen; et al. (Food Research International, 2023)

2-hydroxy-3-phenylpropanoic acid suppressed the growth of Alternaria alternata through damaging cell membrane integrity and modulating reactive oxygen species metabolism - Jiaxin Liu; Canying Li; Chenyang Zhang; Rui Huang; Linhong Qu; Yonghong Ge (Fungal Biology, 2023)

Amino acid ionic liquid–based magnetic dispersive solid-phase extraction for benzimidazole residue analysis in fruit juice and human serum based on theoretical screening - Rui Chen; Xiaoqiang Qiao; Fengmao Liu; Xuehui Chen (Food Chemistry, 2023)

Influence of different thermal treatment methods on the processing qualities of sesame seeds and cold-pressed oil - Ying Huang; Changsheng Liu; Zhengfa Ge; Fenghong Huang; Hu Tang; Qi Zhou; Rui Liu; Jiazhang Huang; Chang Zheng (Food Chemistry, 2023)

Characterization of the key odorants of ripe Capparis spinosa L. fruit and changes in concentrations after storage by means of molecular sensory science - Zhimin Zhang; Miao Liang; Binshan Liu; Yajian Wu; Rui Wang; Yuping Liu (Food Chemistry, 2023)

Detoxification of patulin in apple juice by enzymes and evaluation of its degradation products - Xiaoshuang Liu; Leran Wang; Saiqun Wang; Rui Cai; Tianli Yue; Yahong Yuan; Zhenpeng Gao; Zhouli Wang (Food Control, 2023)

The protective role of vitamin C on intestinal damage induced by high-dose glycinin in juvenile Rhynchocypris lagowskii Dybowski - Rui Zhu; Zongyu Liu; Minghui Lu; Xueqin Wu; Xueyuan Zhao; Hong-He Wang; Ya-Nan Quan; Li-Fang Wu (Fish & Shellfish Immunology, 2023)

Microcystin-LR exposure interfered maintenance of colonic microenvironmental homeostasis in rat - Yang Liu; Chun-Li Qi; Da-Wei Li; Hong-Ye Li; Rui-Man Li; Wei-Dong Yang (Food and Chemical Toxicology, 2023)

Biotransformation of bisphenol A in vivo and in vitro by laccase-producing Trametes hirsuta La-7: Kinetics, products, and mechanisms - Jie Liu; Kai Sun; Rui Zhu; Xun Wang; Michael Gatheru Waigi; Shunyao Li (Environmental Pollution, 2023)

Exploring the heterogeneity in drivers of energy-saving behaviours among hotel guests: Insights from the theory of planned behaviour and personality profiles - Qian-Cheng Wang; Yi-Tian Ren; Xuan Liu; Rui-Dong Chang; Jian Zuo (Environmental Impact Assessment Review, 2023)

Superior tough, highly wear durable and self-lubricating epoxy composite co-enhanced by soft and hard nanomaterials - Yuanbo Zhang; Kaiming Yang; Rui Liu; Junyan Yao; Hongxia Yan (Chemical Engineering Journal, 2023)

SnS2-covalent organic framework Z-scheme van der Waals heterojunction for enhanced photocatalytic reduction of uranium (VI) in rare earth tailings wastewater - Xin Liu; Rui-Xiang Bi; Cheng-Rong Zhang; Qiu-Xia Luo; Ru-Ping Liang; Jian-Ding Qiu (Chemical Engineering Journal, 2023)

Spatially dual-confined metallic selenide double active centers for boosting potassium ion storage - Juan Gong; Rui Zhang; Xijun Wei; Yu Liu; Qing Luo; Qi Wan; Qiaoji Zheng; Lei Wang; Shude Liu; Dunmin Lin (Chemical Engineering Journal, 2023)

Superior nitrogen removal and efficient sludge reduction via partial nitrification-anammox driven by addition of sludge fermentation products for real sewage treatment - Jinjin Liu; Qiong Zhang; Shuying Wang; Xiyao Li; Rui Wang; Yongzhen Peng (Bioresource Technology, 2023)

Morphology and location of sensilla in the antennae and ovipositor of Sirex noctilio (Hymenoptera: Siricidae) - Enhua Hao; Rui Liu; Ruirui Xu; Pengfei Lu; Haili Qiao (Arthropod Structure & Development, 2023)

High density mapping of wheat stripe rust resistance gene QYrXN3517-1BL using QTL mapping, BSE-Seq and candidate gene analysis - Shuo Huang; Yibo Zhang; Hui Ren; Xin Zhang; Rui Yu; Shengjie Liu; Qingdong Zeng; Qilin Wang; Fengping Yuan; Ravi P. Singh; Sridhar Bhavani; Jianhui Wu; et al. (Theoretical and Applied Genetics, 2023)

Vitellogenin accumulation leads to reproductive senescence by impairing lysosomal function - Jie Tang; Yi-Cheng Ma; Yuan-Li Chen; Rui-Qiu Yang; Heng-Chen Liu; Xin Wang; Baosen Ni; Cheng-Gang Zou; Ke-Qin Zhang (Science China Life Sciences, 2023)

P2Y12 receptor gene polymorphisms are associated with epilepsy - Qi Wang; Nan-Rui Shi; Peng Lv; Juan Liu; Ji-Zhou Zhang; Bin-Lu Deng; Yan-Qin Zuo; Jie Yang; Xin Wang; Xiang Chen; Xiu-Min Hu; Ting-Ting Liu; et al. (Purinergic Signalling, 2023)
The basic research indicated that microglial P2Y12 receptors ( P2Y12Rs ) are involved in the pathophysiology of epilepsy through regulated microglial-neuronal interactions, aberrant neurogenesis, or immature neuronal projections. However, whether the clinic case of epilepsy would be associated with P2Y12 receptor gene polymorphisms is presented with few data. In our study, a total of 176 patients with epilepsy and 50 healthy controls were enrolled. Two single-nucleotide polymorphisms, namely rs1491974 and rs6798347, were selected for analysis. The results revealed that carriers of the G allele of rs1491974 G>A or rs6798347 G>A may be associated with an increased risk of epilepsy (OR = 0.576, 95% CI = 0.368–0.901, p = 0.015; OR = 0.603, 95% CI = 0.367–0.988, p = 0.043). Interestingly, we found that the rs1491974 G>A genotype and allele frequencies have only a significant difference in female instead of male case ( p = 0.004 for genotype; p = 0.001 for allele). The subgroup analysis demonstrated that individuals with the rs1491974 G>A genotype might have more frequent seizure (OR = 0.476, 95% CI = 0.255–0.890; p = 0.019). These data implied that both rs1491974 and rs6798347 polymorphisms of P2Y12R would be able to play import roles in epilepsy susceptibility, whereas the rs1491974 polymorphism may be specifically related to seizure frequency.

Silencing P25, HC-Pro and Brp1 of Potato Virus (Viroid) Using Artificial microRNA Confers Resistance to PVX, PVY and PSTVd in Transgenic Potato - Lili Jiang; Rui Mu; Ziquan Wang; Shangwu Liu; Dianqiu Lu (Potato Research, 2023)

Effects of Alpine Grassland Degradation on Soil Microbial Communities in Qilian Mountains of China - Chunming Li; Derong Zhang; Gengchun Xu; Rui Yan; Yang Huang; Liuqing Feng; Jin Yi; Xiangyu Xue; Huixia Liu (Journal of Soil Science and Plant Nutrition, 2023)

A chitin synthase mutation confers widespread resistance to buprofezin, a chitin synthesis inhibitor, in the brown planthopper, Nilaparvata lugens - Bin Zeng; Fu-Rong Chen; Ya-Ting Liu; Di Guo; Yi-Jie Zhang; Ze-Rui Feng; Li-Xiang Wang; John Vontas; Shun-Fan Wu; Kun Yan Zhu; Cong-Fen Gao (Journal of Pest Science, 2023)

Tectonic boundaries in the South China Sea from aeromagnetic signature - Yao Luo; Hang Yin; Qiang Liu; Jingmin Li; Shihua Liu; Wei Gao; Rui Li; Yi Yang (Journal of Oceanology and Limnology, 2023)

Tissue-resident immune cells in the pathogenesis of multiple sclerosis - Jie Tian; Lingli Jiang; Zixiang Chen; Qingfang Yuan; Chang Liu; Longfeng He; Feng Jiang; Ke Rui (Inflammation Research, 2023)

The Mechanical Model on Surface Subsidence Caused by Backfilling Mined-Out Area on Thick Loose Loess Layer: Taking a Sedimentary Bauxite Mine as an Example - Rui Liu (Geotechnical and Geological Engineering, 2023)

Phthalate Mixture Exposure is Associated with Elevated Blood Pressure in Chinese Children: A Panel Study - Miao Liu; Lei Zhao; Linlin Liu; Wenting Guo; Huihua Yang; Meng Li; Shuang Chen; Jie Yu; Qin Fang; Xuefeng Lai; Liangle Yang; Rui Zhu; et al. (Exposure and Health, 2023)

Knowledge mapping and trends in research on remote sensing change detection using CiteSpace analysis - Yuanhe Yu; Yuzhen Shen; Yaoyao Liu; Yuchun Wei; Xudong Rui; Bingbing Li (Earth Science Informatics, 2023)

rTFPI Protects Cardiomyocytes from Hypoxia/Reoxygenation Injury through Inhibiting Autophagy and the Class III PI3K/Beclin-1 Pathway - Runan Yan; Wei Gao; Wenjia Chen; Yue Liu; Li Shen; Yue Dai; Rui Xu; Qing Chang; Yu Fu; Yong Zhao (Cell Biochemistry and Biophysics, 2023)

Identification of three Streptomyces strains and their antifungal activity against the rubber anthracnose fungus Colletotrichum siamense - Jinhong Wang; Rui Wang; Jing Gao; Huanqing Liu; Wen Tang; Zhiqiang Liu; Xiaoyu Li (Journal of General Plant Pathology, 2023)

Nuclides selection method for nuclear reactor shielding based on non-dominated sorting - Rui Li; Shichang Liu; Xian Zhang; Chai Xiaoming; Yang Junyun; Huang Qianming; Yixue Chen (Annals of Nuclear Energy, 2023)

Combined effects of fluoroquinolone antibiotics and organophosphate flame retardants on Microcystis aeruginosa - Yang Zhao; Yingping Huang; Shuang Hu; Tao Xu; Yanfen Fang; Huigang Liu; Ying Xi; Rui Qu (Environmental Science and Pollution Research, 2023)

Effects of Vertical Water Column Temperature on Distribution of Juvenile Tuna Species in the South China Sea - Shigang Liu; Yuan Li; Rui Wang; Xing Miao; Ran Zhang; Siyuan Chen; Puqing Song; Longshan Lin (Fishes, 2023)
In this study, we conducted two surveys in the central and southern parts of the South China Sea, in autumn 2012 and spring 2013. Six juvenile tuna species were caught in each survey. Gradient forest analysis (GFA) and a generalized additive model (GAM) were used to analyze the relationship between the catch per unit effort (CPUE) for the juvenile tuna species and six sea temperature indices for the South China Sea. In the GFA, the temperature difference between the sea surface and 50 m depth (D50) showed the highest importance to CPUE than other indices, which indicates that D50 was the best predictor of the abundance of juvenile tuna species. The GAM analysis showed that lower deep-water temperature, a shallow mixed layer depth, and a higher difference in temperature between the surface and deeper water were associated with increased CPUE. The results indicate that a relatively rapid decrease in vertical water temperature is favorable for the aggregation of juvenile tuna. These results contribute to understanding of the distribution mechanism of juvenile tuna species in the South China Sea and provide a scientific basis for the rational development and utilization of tuna resources.

Landslide susceptibility prediction improvements based on a semi-integrated supervised machine learning model - Ning Yang; Rui Wang; Zhaofei Liu; Zhijun Yao (Environmental Science and Pollution Research, 2023)

Identification of marine natural product Pretrichodermamide B as a STAT3 inhibitor for efficient anticancer therapy - Rui Li; Yue Zhou; Xinxin Zhang; Lujia Yang; Jieyu Liu; Samantha M. Wightman; Ling Lv; Zhiqing Liu; Chang-Yun Wang; Chenyang Zhao (Marine Life Science & Technology, 2023)
The Janus kinase (JAK)/signal transducer and activator of transcription 3 (STAT3) regulates the expression of various critical mediators of cancer and is considered as one of the central communication nodes in cell growth and survival. Marine natural products (MNP) represent great resources for discovery of bioactive lead compounds, especially anti-cancer agents. Through the medium-throughput screening of our in-house MNP library, Pretrichodermamide B, an epidithiodiketopiperazine, was identified as a JAK/STAT3 signaling inhibitor. Further studies identified that Pretrichodermamide B directly binds to STAT3, preventing phosphorylation and thus inhibiting JAK/STAT3 signaling. Moreover, it suppressed cancer cell growth, in vitro, at low micromolar concentrations and demonstrated efficacy in vivo by decreasing tumor growth in a xenograft mouse model. In addition, it was shown that Pretrichodermamide B was able to induce cell cycle arrest and promote cell apoptosis. This study demonstrated that Pretrichodermamide B is a novel STAT3 inhibitor, which should be considered for further exploration as a promising anti-cancer therapy.

Phytoplankton biomass dynamics with diffuse terrestrial nutrients pollution discharge into bay - Wei Ouyang; Rui Wang; Kaiyue Ji; Xitao Liu; Fang Geng; Xin Hao; Chunye Lin (Chemosphere, 2023)

Alleviating effects of zinc and 24-epibrassionlide on cadmium accumulation in rice plants under nitrogen application - Zunxin Wang; Yang Li; Mingsong Liu; Ying Yang; Rui Wang; Siyuan Chen; Zongmei Liu; Feiyu Yan; Xinhong Chen; Junguo Bi; Zhiyao Dong; Feibing Wang (Chemosphere, 2023)

Effects of different photoperiod conditions on survival, growth, and gonadal development of Takifugu rubripes adults - Weiyuan Li; Yuyu Xiong; Ziwei Wang; Qi Zhang; Xufang Shen; Qi Liu; Hongwei Yan; Rui Gao; Ying Liu; Hongshuai Pang; Xiuli Wang (Aquaculture, 2023)

Spatiotemporal difference of leachate production and its impact on the development and dynamics of LCS clogging - Ya Xu; Guangyuan Yao; Rui Xiang; Yuqiang Liu; Qifei Huang (Waste Management, 2023)

SLP-2 regulates the generation of reactive oxygen species and the ERK pathway to promote papillary thyroid carcinoma motility and angiogenesis - Jianping Chen; Duting Wang; Rui Xu; Ting Yao; Yu Guo; Qi Liu; Erlong Yang; Zhengqing Wu; Zhenyu Xu (Tissue and Cell, 2023)

Abnormal fatty acid metabolism and ceramide expression may discriminate myocardial infarction from strangulation death: A pilot study - Song-Jun Wang; Bing-Rui Liu; Fu Zhang; Ya-Ping Li; Xiao-Rui Su; Chen-Teng Yang; Bin Cong; Zhi-Hua Zhang (Tissue and Cell, 2023)

Changes in PM2.5-related health burden in China's poverty and non-poverty areas during 2000–2020: A health inequality perspective - Yan Li; Baojie Li; Hong Liao; Bing-Bing Zhou; Jing Wei; Yuxia Wang; Yuzhu Zang; Yang Yang; Rui Liu; Xiaorui Wang (Science of The Total Environment, 2023)

Microbial-induced calcium carbonate precipitation: Influencing factors, nucleation pathways, and application in waste water remediation - Yu Liu; Amjad Ali; Jun-Feng Su; Kai Li; Rui-Zhu Hu; Zhao Wang (Science of The Total Environment, 2023)

Predictive and estimation model of Cd, Ni, and Zn bioaccumulations in maize based on diffusive gradients in thin films - Rui Chen; Xiulin Mu; Jiaxing Liu; Nuo Cheng; Rongguang Shi; Miaomiao Hu; Zhuoran Chen; Hao Wang (Science of The Total Environment, 2023)

Climate change has increased the global threats posed by three ragweeds (Ambrosia L.) in the Anthropocene - Xiaoqing Xian; Haoxiang Zhao; Rui Wang; Hongkun Huang; Baoxiong Chen; Guifen Zhang; Wanxue Liu; Fanghao Wan (Science of The Total Environment, 2023)

Utility of a non-target screening method to explore the chlorination of similar sulfonamide antibiotics: Pathways and NCl intermediates - Di Xia; He Liu; Yang Lu; Yanchen Liu; Jiahao Liang; Danping Xie; Guining Lu; Jinrong Qiu; Rui Wang (Science of The Total Environment, 2023)

Manganese-induced α-synuclein overexpression promotes the accumulation of dysfunctional synaptic vesicles and hippocampal synaptotoxicity by suppressing Rab26-dependent autophagy in presynaptic neurons - Zhuo Ma; Kuan Liu; Rui-feng Zhang; Zi-xin Xie; Wei Liu; Yu Deng; Xin Li; Bin Xu (Science of The Total Environment, 2023)

Gonad development and recruitment pattern of the oysters Crassostrea ariakensis and Crassostrea sikamea in a subtropical bay in China - Wei Jiang; Wen-Jing Shi; Nan-Nan Li; Wen-Kao Zhang; Li-Zhi Chen; Qi Liu; Chun-Yu Ye; Rui-Liang Fan; Wei-Min Quan (Regional Studies in Marine Science, 2023)

Experimental study on the effects of salt solution pH on the performance of reverse electrodialysis stack - Lu Wang; Yanan Zhao; Xi Chen; Rui long; Zhichun Liu; Wei Liu (Process Safety and Environmental Protection, 2023)

The F-box protein OsEBF2 confers the resistance to the brown planthopper (Nilparvata lugens Stål) - Feilong Ma; Zixin Li; Sayi Wang; Kejia Li; Fei Tang; Jingxuan Jia; Qiujin Zhao; Peihua Jing; Wenqing Yang; Congmin Hua; Haifu Han; Jiayin Xu; et al. (Plant Science, 2023)

Antimicrobial peptide CB-M exhibits direct antifungal activity against Botrytis cinerea and induces disease resistance to gray mold in cherry tomato fruit - Xiaomin Yang; Yating Wang; Hanyue Jiang; Rui Song; Yongguo Liu; Honglian Guo; Demei Meng (Postharvest Biology and Technology, 2023)

Dynamic stiffness formulation for free vibration analysis of rotating cross-ply laminated combined elliptical-cylindrical-conical shell - Qing Peng; Qingshan Wang; Zhengxiong Chen; Rui Zhong; Tao Liu; Bin Qin (Ocean Engineering, 2023)

Marine osmium‑uranium‑sulfur isotope evidence for the interaction of volcanism and ocean anoxia during the Middle Pleistocene in the tropical Western Pacific - Wenlong Pei; Jiayue Wang; Xinling Wang; Rui Zhang; Tiegang Li; Fan Zhang; Xiaoxiao Yu; Zhiyong Liu; Minglei Guan; Qi Han (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

A stomatal optimization model adopting a conservative strategy in response to soil moisture stress - Rui Zhu; Tiesong Hu; Quan Zhang; Xiang Zeng; Shan Zhou; Fengyan Wu; Yong Liu; Yanxuan Wang (Journal of Hydrology, 2023)

Ultrasensitive hydrogel grating detector for real-time continuous-flow detection of trace threat Pb2+ - Xiao-Yu Tian; Meng-Wei Sun; Guo-Yu Wen; Min Cao; Da-Wei Pan; Rui Xie; Xiao-Jie Ju; Zhuang Liu; Wei Wang; Liang-Yin Chu (Journal of Hazardous Materials, 2023)

MiR-130/SNAP-25 axis regulate presynaptic alteration in anterior cingulate cortex involved in lead induced attention deficits - Tao Wang; Rui-Li Guan; Yun-Feng Zou; Gang Zheng; Xue-Feng Shen; Zi-Peng Cao; Rui-Hua Yang; Ming-Chao Liu; Ke-Jun Du; Xue-Hang Li; Michael Aschner; Ming-Gao Zhao; et al. (Journal of Hazardous Materials, 2023)

Self-assembly of Au nanocrystals into large-area 3-D ordered flexible superlattice nanostructures arrays for ultrasensitive trace multi-hazard detection - Wei Liu; Qian Li; Jiabin Wu; Weizhe Wang; Rui Jiang; Chunli Zhou; Shuangbao Wang; Xueming Zhang; Tangyou Sun; Zhimou Xu; Dingsheng Wang (Journal of Hazardous Materials, 2023)

Case-driven assessment of power grid emergency response capability considering typhoon disaster scenario diversity - Zhao-ge Liu; Xiang-yang Li; Dilawar Khan Durrani; Rui-jin Zhang (Journal of Cleaner Production, 2023)

Too ill to cure? – An uncertainty-based probabilistic model assessment on one of China’s most eutrophic lakes - Xuan Yi; Rui Zou; Xiawei Liao; Huaicheng Guo; Yong Liu (Journal of Environmental Management, 2023)

A comprehensive meta-analysis of the impacts of intensified drought and elevated CO2 on forage growth - Wanlu Liu; Lulu Liu; Rui Yan; Jiangbo Gao; Shaohong Wu; Yanhua Liu (Journal of Environmental Management, 2023)

Variations of the urban PM2.5 chemical components and corresponding light extinction for three heating seasons in the Guanzhong Plain, China - Julian Shi; Suixin Liu; Yao Qu; Ting Zhang; Wenting Dai; Peiyun Zhang; Rui Li; Chongshu Zhu; Junji Cao (Journal of Environmental Management, 2023)

Antifouling modification of PVDF membranes via incorporating positive-charge tuned quaternized chitosan magnetic particles - Ziming Zhu; Xuan Zhou; Rui Zhang; Yahong Li; Yuan Liu; Jianxian Zeng; Xiaoping Huang; Pengfei Liu; Jianrong Xue; Kaipeng Cheng; Hongfei Xu (Journal of Environmental Chemical Engineering, 2023)

Rapid nitrification using nitrifying biomass acclimated to sulfamethoxazole (SMX) - Xinyue Zhang; Jiayu Huang; Song Chen; Ning Yan; Rui Liu; Yongming Zhang; Bruce E. Rittmann (Journal of Environmental Chemical Engineering, 2023)

Estimating the magnitude of early Permian relative sea-level changes in southern North China - Rui Ma; Jianghai Yang; Yuan Wang; Jiaxin Yan; Jia Liu (Global and Planetary Change, 2023)

Consolidating the gelling performance of myofibrillar protein using a novel OSA-modified-starch-stabilized Pickering emulsion filler: Effect of starches with distinct crystalline types - Qingling Wang; Yi Luan; Ziwei Tang; Zhikun Li; Chen Gu; Rui Liu; Qingfeng Ge; Hai Yu; Mangang Wu (Food Research International, 2023)

Metagenomic insights into bacterial communities and functional genes associated with texture characteristics of Kazakh artisanal fermented milk Ayran in Xinjiang, China - Malina Kuerman; Rui Wang; Yu Zhou; Xiaoying Tian; Qingyu Cui; Huaxi Yi; Pimin Gong; Zhe Zhang; Kai Lin; Tongjie Liu; Lanwei Zhang (Food Research International, 2023)

Distribution pattern, removal effect, transfer behavior of ten pesticides and one metabolite during the processing of grapes - Chengcheng Liu; Rui Chen; Fengmao Liu; Zhiqiang Gao; Xiaohan Li; Yue Wang; Shiyu Wang; Yuyan Li (Food Research International, 2023)

The physicochemical properties of a starch–sodium stearoyl lactylate complex formed via annealing treatment in ethanol solutions - Xiaoyu Chen; Chaofan Wang; Xiaoyang He; Yang Qin; Lei Dai; Liu Xiong; Tao Wang; Rui Shi; Na Ji; Qingjie Sun (Food Hydrocolloids, 2023)

Novel polysaccharide from Panax notoginseng with immunoregulation and prebiotic effects - Hui-Rong Yang; Xue Li; Hao Liu; Dong-Rui Zhao; Ying-Jie Zeng (Food Bioscience, 2023)

Expanded polystyrene buoys as an important source of hexabromocyclododecanes for aquatic ecosystem: Evidence from field exposure with different substrates - Yun-Feng Pan; Shan Liu; Heng-Xiang Li; Lang Lin; Rui Hou; Yuan-Yue Cheng; Xiang-Rong Xu (Environmental Pollution, 2023)

Associations of co-exposure to polycyclic aromatic hydrocarbons and metals with hyperuricemia risk in Chinese coke oven workers: Mediating roles of oxidative damage - Chaofan Guo; Xin Liu; Xiaojing Liao; Haimei Wu; Zhaorui Zhang; Dehua Wu; Rui Ma; Yongshun Huang; Na Zhao; Yongmei Xiao; Qifei Deng (Environmental Pollution, 2023)

Long-term effects of optimized fertilization, tillage and crop rotation on soil fertility, crop yield and economic profit on the Loess Plateau - Haoyu Li; Yuanhong Zhang; Yuanguang Sun; Pengzhao Liu; Qi Zhang; Xiaoli Wang; Rui Wang; Jun Li (European Journal of Agronomy, 2023)

Longitudinal shear behavior and design method of UHPC connection for prefabricated slabs in composite beams - Hao Wang; Xiao-gang Liu; Qing-rui Yue; Ning Wang; Ming-zhao Zheng (Engineering Structures, 2023)

The source of wind power producers’ market power - Yang Yu; Lin Chen; Rui Liu (Energy Policy, 2023)

Methyl 4-hydroxybenzoate nanospheres anchored on poly(amidoxime)/polyvinyl alcohol hydrogel network with excellent antibacterial activity for efficient uranium extraction from seawater - Junqiang Zhang; Jiliang Ma; Gaojie Jiao; Kangning Liu; Rui Cui; Shangru Zhai; Runcang Sun (Desalination, 2023)

Novel supported low-temperature solid molten salt (SMS) anode materials for Li-ion batteries - Lei Jiang; Ning Han; Tingting Luo; Zhe Zhang; Fenghao Liang; Daoning Wu; Xiaochun Li; Fengjiao Liu; Yichuan Rui; Wei Zhang; Yi Qu; Bohejin Tang (Chemical Engineering Journal, 2023)

Efficient removal of nitrogen from tidal flow constructed wetlands based on the in-situ zeolite regeneration: Measures and mechanisms - Rui Ma; Jiangsen Ma; Yuzhe Chen; Yiyuan Zhuo; Linsong Cheng; Lei Jiang; Yuanxiang Mao; Qiushi Shen; Caocun Liu; Fangying Ji (Chemical Engineering Journal, 2023)

Facile fabrication of flexible and ultrathin self-assembled Ti3C2T /bacterial cellulose composite films with multifunctional electromagnetic shielding and photothermal conversion performances - Hao Liu; Zhou Cui; Lijin Luo; Qiugang Liao; Rui Xiong; Chao Xu; Cuilian Wen; Baisheng Sa (Chemical Engineering Journal, 2023)

Effect of the acid site in the catalytic degradation of volatile organic compounds: A review - Caihong Pang; Rui Han; Yun Su; Yanfei Zheng; Mingke Peng; Qingling Liu (Chemical Engineering Journal, 2023)

Metagenomics-based interpretation of selective bioaugmentation promoting partial-denitrification coupling with anammox process reactivation in suspended sludge system - Cong Li; Qingtao Liu; Jiarui Fan; Yongzhen Peng; Rui Du (Chemical Engineering Journal, 2023)

Friction induced mechanochemistry: self-adaptive lubrication through in-situ tribo-click system - Rui Dong; Yunlei Zhang; Hao-Zhe Xu; Luyao Bao; Shuanhong Ma; Xin-Gang Wang; Qiangliang Yu; Meirong Cai; Feng Zhou; Weimin Liu (Chemical Engineering Journal, 2023)

Redox of anionic and cationic radical intermediates in a bipolar polyimide COF for high-performance dual-ion organic batteries - Shuai Gu; Jingjing Chen; Rui Hao; Xi Chen; Zhiqiang Wang; Iftikhar Hussain; Guiyu Liu; Kun Liu; Qingmeng Gan; Zhiqiang Li; Hao Guo; Yingzhi Li; et al. (Chemical Engineering Journal, 2023)

Long-lifespan benzoquinone-intercalated vanadium oxide with vacancies and disorders on the (00l) facets for efficient sodium-ion battery: A facile approach to Na+ capture and pre-sodiation - Rui Tang; Kai Li; Changlin Liu; Yang Liu; Yun Gong; Jianhua Lin (Chemical Engineering Journal, 2023)

Waterproof conductive fiber with microcracked synergistic conductive layer for high-performance tunable wearable strain sensor - Shiyin Yang; Wenke Yang; Rui Yin; Hu Liu; Hongling Sun; Caofeng Pan; Chuntai Liu; Changyu Shen (Chemical Engineering Journal, 2023)

Target acquisition of anti-aging manno-oligosaccharide that triggers ECM process via TGF-β/Smads-SIRT1 signalling pathway - Liu Yang; Chengting Zi; Dingkang Chen; Jinyu Li; Rui He; Jiang-Miao Hu (Carbohydrate Polymers, 2023)

Insight of key parameters in freeze-thaw damage on the performance of cement-based materials: A comparative study with rapid-freeze method - Siyuan Chen; Rui Liu; Huigang Xiao; Wei Wang (Cold Regions Science and Technology, 2023)

The off-axis plume–ridge interaction model: Confirmation from the mineral chemistry of Cretaceous basalts of the Ontong Java Plateau - Jing Chen; Shuang-Shuang Chen; Donald B. Dingwell; Rui Gao; Jia-Qi Liu (Chemical Geology, 2023)

Rapid and massive fractionation of hemicelluloses for purifying cellulose at room temperature by tetramethylammonium hydroxide - Rui Tian; Bolang Zhu; Qiaoling Liu; Yajie Hu; Ziying Yang; Jun Rao; Yuying Wu; Baozhong Lü; Jing Bian; Feng Peng (Bioresource Technology, 2023)

An achieved strategy for magnetic biochar for removal of tetracyclines and fluoroquinolones: Adsorption and mechanism studies - Xianzhao Zhang; Dawei Zhen; Fengmao Liu; Rui Chen; Qingrong Peng; Zongyi Wang (Bioresource Technology, 2023)

Long-term exposure to ambient particulate matter and kidney function in older adults - Yingxin Li; Xueli Yuan; Jing Wei; Yuanying Sun; Wenqing Ni; Hongmin Zhang; Yan Zhang; Rui Wang; Ruijun Xu; Gongbo Chen; Yuewei Liu; Jian Xu (Atmospheric Environment, 2023)

Different roles of primary and secondary sources in reducing PM2.5: Insights from molecular markers in Pearl River Delta, South China - Kong Yang; Duo-Hong Chen; Xiang Ding; Jun Li; Yu-Qing Zhang; Tao Zhang; Qiao-Yun Wang; Jun-Qi Wang; Qian Cheng; Hao Jiang; Ping Liu; Zi-Rui Wang; et al. (Atmospheric Environment, 2023)

Territorial function differentiation and its comprehensive regionalization in China - Jie Fan; Kan Zhou; Kerong Sheng; Rui Guo; Dong Chen; Yafei Wang; Hanchu Liu; Zheng Wang; Yong Sun; Jie Zhang; Jianxiong Wu; Hao Zhao (Science China Earth Sciences, 2023)

Long-term cycles of the Solar System concealed in the Mesozoic sedimentary basin record - Rui Zhang; Zhijun Jin; Michael Gillman; Quanyou Liu; Ren Wei; Peng Li; Zhihui Zhang (Science China Earth Sciences, 2023)

A Medicago truncatula lncRNA MtCIR1 negatively regulates response to salt stress - Rui Tian; Xiaohan Sun; Cuimei Liu; Jinfang Chu; Mingui Zhao; Wen-Hao Zhang (Planta, 2023)

An in silico and in vitro integrated analysis method to reveal the curative mechanisms and pharmacodynamic substances of Bufei granule on chronic obstructive pulmonary disease - Yuan-yuan Ma; Rong Li; Zhi-xian Shang; Wei Liu; Xin-yi Jiao; Liu-yi Liang; Rui Liu; Zheng Li (Molecular Diversity, 2023)

Simultaneous measurement of multiple labile heavy metals in soils by diffusive gradients in thin film technique - Rui Chen; Jiaxing Liu; Guoyu Ding; Fumin Ren; Rongguang Shi; Jungang Lv; Jing Cheng (Journal of Soils and Sediments, 2023)

Orbital and Millennial-Scale Climate Variability over the Past 76 ka in the Western Tarim Basin, Northwest China - Rui Zhang; Qiuzhen Yin; Weihua Nai; Zhixiang Wang; Hao Lu; Chunju Huang; Yansheng Gu; Lin Li; Yusong Wang; Linjing Liu (Journal of Earth Science, 2023)

Effects of earthworm (Eisenia fetida) and arbuscular mycorrhizal fungi improving plant hormones and antioxidant enzymes under simulated acid rain stress - Wang Binglei; Wang Chong; Liu Xuelian; Xue Rui; Liu Mengli; Xu Guangxia; Li Zhiyi (Applied Soil Ecology, 2023)

Ameliorating C and N balance without loss of productivity by applying mulching measures in rainfed areas - Zihan Liu; Bingfan Wang; Zhaoyang Li; Chenxu Zhao; Rui Qian; Fangyuan Huang; Peng Zhang; Hui Li; ZhiKuan Jia (Agriculture, Ecosystems & Environment, 2023)

Aerobic degradation of bisphenol A by Pseudomonas sp. LM-1: characteristic and pathway - Chen Gu; Jinxuan Liang; Ming Liu; Jianliang Rui; Jiyan Shi; Yanming Yu; Xuwang Zhang (Biodegradation, 2023)

Effects of single or conjoint administration of lactic acid bacteria as potential probiotics on the growth, immune responses, and disease resistance of Carassius auratus - Ruoming Li; Teng Chi; Qing Xu; Juntong Liu; Xiaofeng Shan; Rui Zhou; Jiayun Yao; Wuwen Sun; Guiqin Wang (Aquaculture International, 2023)

Kingella pumchi sp. nov., an organism isolated from human vertebral puncture tissue - Meng Xiao; Ruina Liu; Juan Du; Rui Liu; Lei Zhai; He Wang; Su Yao; Ying-Chun Xu (Antonie van Leeuwenhoek, 2023)

Correction: Celecoxib and octreotide synergistically ameliorate portal hypertension via inhibition of angiogenesis in cirrhotic rats - Jin-Hang Gao; Shi-Lei Wen; Shi Feng; Wen-Juan Yang; Yao-Yao Lu; Huan Tong; Rui Liu; Shi-Hang Tang; Zhi-Yin Huang; Ying-Mei Tang; Jin-Hui Yang; Hui-Qi Xie; et al. (Angiogenesis, 2023)

Snow depth variability across the Qinghai Plateau and its influencing factors during 1980–2018 - Heng Ma; Gangfeng Zhang; Rui Mao; Bo Su; Weihang Liu; Peijun Shi (International Journal of Climatology, 2023)
As a crucial component of the climate system, snow cover plays an important role on surface energy budgets, hydrological cycles and socioeconomic development. This paper investigated the spatiotemporal patterns of snow depth across the Qinghai Plateau (QP) during 1980–2018 based on passive microwave (PMW) satellite observation and reanalysis products. The study identified the relationships between the changes in PMW snow depth and topographic features and revealed the impact of climatic variables (air temperature, precipitation and wind speed) and large‐scale atmospheric circulations on observed snow depth variability. The results show that the spatial pattern of snow depth climatology is similar in all datasets, except in terms of magnitude, with high values in the southern and southeastern parts of the QP and low values in the eastern and northwestern parts. Average snow depth correlates positively with precipitation, elevation and slope, and negatively with air temperature and wind speed. The long‐term trends in snow depth vary with the season and the datasets. The PMW snow depth across the QP shows a significant annual (−0.125 cm·decades −1 , p −1 , p

Unique bacterial communities and lifestyles in deep ocean blue holes: Insights from the Yongle Blue Hole (South China Sea) - Shun Zhou; Jiwen Liu; Peng Yao; Liang Fu; Zuosheng Yang; Yulin Zhang; Rui Du; Chao Jia; Lin Chen; Jinchang Liang; Xiaolei Wang; Xiaochong Shi; et al. (Frontiers in Marine Science, 2023)
Deep ocean blue holes possess steep physicochemical gradients, especially low dissolved oxygen concentration, which shape the extraordinary microbial communities. However, the environmental responses of microorganisms with different lifestyles and knowledge of culturable microorganisms in the blue holes are still unknown. Here, we investigated the bacterial community structure with different lifestyles of the world’s deepest blue hole - the Yongle Blue Hole (YBH) in the South China Sea using both culture-dependent and -independent methods. YBH can be divided by oxygen content into an oxic zone, a suboxic zone and two anoxic zones. The abundance of bacteria, archaea, genes dsrB and soxB were all higher in the free-living (FL) lifestyle than in the particle-associated (PA) lifestyle, yet the diversity and richness of PA bacteria were higher than that of FL bacteria. More Gammaproteobacteria and less Alphaproteobacteria , Chloroflexi and Nitrospinae were observed within the FL fraction than within the PA fraction. The relative abundance of sulfur-oxidizing bacteria (SOB) was dominant between 100-140 m (anoxic zone I) in YBH, with a maximum of 90.0% (140 m FL fraction). The SOB in YBH were mainly colorless sulfur bacteria and purple non-sulfur bacteria, of which Thiomicrorhabdus and Sulfurimonas were the main representatives. In addition, a total of 294 bacterial strains were isolated on a variety of media and culture conditions, and 22.2% (18/81) of anaerobic strains were identified as potential novel species. Our study reveals a distinction between FL and PA bacteria in YBH. It contributes to further understanding of the bacterial community in deep ocean blue holes, and provides bacterial resources for subsequent studies on their adaptation to extreme marine environments.

A new acylated iridoid and other chemical constituents from Valeriana jatamansi and their biological activities - Yun Wang; Dao-Qun Shi; Na Jiang; Kai-Rui Rao; Shi-Xian Zhang; Dan Liu; Rong-Tao Li; Hong-Mei Li (Natural Product Research, 2023)

Time-frequency analysis framework for understanding non-stationary and multi-scale characteristics of sea-level dynamics - Xindan Liang; Yinyi Lin; Renguang Wu; Gang Li; Nicole Khan; Rui Liu; Hua Su; Shan Wei; Hongsheng Zhang (Frontiers in Marine Science, 2023)
Rising sea level caused by global climate change may increase extreme sea level events, flood low-lying coastal areas, change the ecological and hydrological environment of coastal areas, and bring severe challenges to the survival and development of coastal cities. Hong Kong is a typical economically and socially developed coastal area. However, in such an important coastal city, the mechanisms of local sea-level dynamics and their relationship with climate teleconnections are not well explained. In this paper, Hong Kong tide gauge data spanning 68 years was documented to study the historical sea-level dynamics. Through the analysis framework based on Wavelet Transform and Hilbert Huang Transform, non-stationary and multi-scale features in sea-level dynamics in Hong Kong are revealed. The results show that the relative sea level (RSL) in Hong Kong has experienced roughly 2.5 cycles of high-to-low sea-level transition in the past half-century. The periodic amplitude variation of tides is related to Pacific Decadal Oscillation (PDO) and El Niño-Southern Oscillation (ENSO). RSL rise and fall in eastern Hong Kong often occur in La Niña and El Niño years, respectively. The response of RSL to the PDO and ENSO displays a time lag and spatial heterogeneity in Hong Kong. Hong Kong's eastern coastal waters are more strongly affected by the Pacific climate and current systems than the west. This study dissects the non-stationary and multi-scale characteristics of relative sea-level change and helps to better understand the response of RSL to the global climate system.

Sedimentation of cohesive sediments at the subtidal flat affected by wind wave in high turbidity estuary - Qi Shen; Qin Zhu; Shuguang Liu; Sha Lou; Hualin Wu; Zhenchang Zhu; Bin Xu; Rui Yuan (Frontiers in Marine Science, 2023)
Sedimentation is an important mechanism to mitigate the shrinking of tidal flat and to restore its ecological function by means of sand or mud nourishment. To explore the sedimentation of cohesive sediments, a seabed tripod observation system was deployed at the subtidal region of the Hengsha Shoal adjacent to the turbidity maximum zone of the Yangtze Estuary for 11 days. The results showed that the fine sediment with the median grain size around 8 mm occupied the whole water column. The seabed was in relative equilibrium state with the fluctuation of bed level smaller than 16 mm during the moderate wind condition while the seabed experienced a rapid erosion of 38mm and a successive intensive accretion of 68mm during the process of wind wave and swell. The bottom hydrodynamic at 0.3mab during the bed accretion was stronger than that during the bed erosion. The deposition process of cohesive sediments can be better described by the simultaneous deposition paradigm than that by the exclusive deposition paradigm according to the direct data-model comparison of the bed level changes, especially during the impact of fluid mud. Three possible reasons for the better performance of the simultaneous deposition paradigm were proposed. The first possibility is that the fine suspended sediments do maintain a continuous contact with the sediment bed since the direct bed level changes during our observation period has been well reproduced by the simultaneous deposition paradigm. The second possibility is the SSC-induced turbulence damping which facilitates the fine sediment settling in the form of cohesive sediment flocs, indicating the settling of sediments can’t be judged by the critical shear stress for deposition just based on the single particle grain size. The last possibility is the fluid mud-induced overestimated bed shear stress by using turbulent velocity fluctuation above the fluid mud-water interface, which produces excess sediment erosion waiting to be compensated by the simultaneous deposition paradigm. For practical modeling purposes, modeling under the simultaneous deposition paradigm can give satisfactory results for the sedimentation of cohesive sediment especially during the impact of wave or swell.

Protective effect of Sargassum fusiforme polysaccharides on H2O2-induced injury in LO2 cells - Jiarui Li; Zhuo Wang; Jianping Chen; Baozhen Luo; Xuehua Chen; Rui Li; Jialong Gao; Xiaofei Liu; Bingbing Song; Saiyi Zhong (Frontiers in Marine Science, 2023)
Introduction Sargassum fusiform is considered a traditional Chinese medicinal herb to treat many diseases, Sargassum fusiform polysaccharides (SFPS) were found to display many important biological activities. The purpose of this study was to investigate the in vitro antioxidant activity of crude polysaccharide from Sargassum fusiforme and its protective effect against H 2 O 2 -induced injury in LO2 cells. Methods SFPS was extracted from Sargassum fusiforme using water extraction and alcohol precipitation. High-performance liquid chromatography (HPLC) was used to measure its monosaccharide composition. The in vitro antioxidant activity of SFPS was evaluated using scavenging 1,1-diphenyl-2-picrylhydrazyl (DPPH) and hydroxyl radical assays. Moreover, its hepatoprotective activity was examined by establishing H 2 O 2 -induced LO2 cells injury model. Results and discussion The results showed that the SFPS was composed of Glc, Ara, Fuc, Gal, Man, Rha and Xyl. Meanwhile, SFPS exhibited strong antioxidant activity and potential hepatoprotective effect. Further studies found that SFPS could alleviate LO2 cells injury induced by H 2 O 2 via decreasing malondialdehyde (MDA) and lactate dehydrogenase (LDH) levels, increasing superoxide dismutase (SOD) and catalase (CAT) activities and inhibiting intracellular reactive oxygen species (ROS) production. These results revealed that SFPS had the ability to protect the liver cells from H 2 O 2 -induced liver injury through its antioxidant activity.

Effects of chemical additives and mature compost on reducing nitrogen loss during food waste composting - Shangao Xiong; Yongdi Liu; Hao Zhang; Shaoqi Xu; Songrong Li; Xinqi Fan; Rui Chen; Guochun Ding; Ji Li; Yuquan Wei (Environmental Science and Pollution Research, 2023)

Calculation method and mechanism of ultimate side resistance of screw pile - Hong-wei Ma; Li Liu; Peng Wang; Song Yuan; Qing-rui He; Xiao-li Yang (Marine Georesources & Geotechnology, 2023)

Bicarbonate enhanced heterogeneous activation of peroxymonosulfate by copper ferrite nanoparticles for the efficient degradation of refractory organic contaminants in water - Chun Cai; Yangfan Liu; Rui Xu; Jiaheng Zhou; Jin Zhang; Yu Chen; Lingyu Liu; Lexiang Zhang; Shuping Kang; Xianjun Xie (Chemosphere, 2023)

Recovery of nickel in the form of Ni(OH)2 from plating wastewater containing Ni-EDTA using bipolar membrane electrodialysis - Yaoxing Liu; Xiaoyu Wu; Liping Dai; Xiaoyun Wu; Jianguo Ding; Riyao Chen; Rui Ding; Jianxi Liu; Bart Van der Bruggen (Chemosphere, 2023)

Insight into the formation and biological effects of natural organic matter corona on silver nanoparticles in water environment using biased cyclical electrical field-flow fractionation - Zhiqiang Tan; Weichen Zhao; Yongguang Yin; Ming Xu; Wenxiao Pan; Yanwanjing Liu; Qinghua Zhang; Bruce K. Gale; Yukui Rui; Jingfu Liu (Water Research, 2023)

Increasing role of phenolic oxidative branch in daytime oxidation process of aromatics in Chinese haze period - Fanglin Wang; Xiaodi Liu; Shaojun Lv; Si Zhang; Can Wu; Shijie Liu; Yali Lei; Yubao Chen; Rui Li; Gehui Wang (Science of The Total Environment, 2023)

Mapping Chinese annual gross primary productivity with eddy covariance measurements and machine learning - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Shi-Ping Chen; Shao-Min Liu; Hui-Min Wang; Jun-Hua Yan; Jun-Lei Tan; Fa-Wei Zhang; et al. (Science of The Total Environment, 2023)

Hotspots of riverine greenhouse gas (CH4, CO2, N2O) emissions from Qinghai Lake Basin on the northeast Tibetan Plateau - Penglin Lin; Zhiheng Du; Lei Wang; Jingfeng Liu; Qian Xu; Jia Du; Rui Jiang (Science of The Total Environment, 2023)

Hydrodynamically–driven distribution and remobilization of heavy metals in surface sediments around the coastal area of Shandong Peninsula, China - Tao Liu; Longhai Zhu; Rui Bao; Rijun Hu; Shenghui Jiang; Yingtao Zhu; Yulong Song (Science of The Total Environment, 2023)

Mineral weathering of iron ore tailings primed by Acidithiobacillus ferrooxidans and elemental sulfur under contrasting pH conditions - Qing Yi; Songlin Wu; Yunjia Liu; Ting-Shan Chan; Ying-Rui Lu; Narottam Saha; Gordon Southam; Longbin Huang (Science of The Total Environment, 2023)

Revealing the driving synergistic degradation mechanism of Rhodococcus sp. B2 on the bioremediation of pretilachlor-contaminated soil - Hongming Liu; Shiyan Liu; Huijun Liu; Mengna Liu; Xiaye Yin; Peng Lu; Qing Hong; Aimin Liu; Rui Wan; Shangping Fang (Science of The Total Environment, 2023)

Synergistic activation of anionic redox via cosubstitution to construct high-capacity layered oxide cathode materials for sodium-ion batteries - Haocheng Ji; Wenhai Ji; Haoyu Xue; Guojie Chen; Rui Qi; Zhongyuan Huang; Hui Fang; Mihai Chu; Lele Liu; Zhewen Ma; Shenyang Xu; Jingjun Zhai; et al. (Science Bulletin, 2023)

Fungal polyketides from a rhizospheric soil-derived Penicillium sp. YUD17004 associated with Gastrodia elata - Hong-Tao Li; Rui-Ning Yang; Tao Liu; Fei Xie; Hao-Jie Duan; Dan-Dan Xia; Hao Zhou; Zhong-Tao Ding (Phytochemistry, 2023)

Flow-drag reduction performance of a resident electrolytic microbubble array and its mechanisms - Rui Zhu; Huanbin Zhang; Weiqi Wen; Xingyu He; Chenhong Zhao; Yu Liu; Qibin Zhuang; Zhirrong Liu (Ocean Engineering, 2023)

Study on the trajectory of tip leakage vortex and energy characteristics of mixed-flow pump under cavitation conditions - Wei Li; Mingjiang Liu; Leilei Ji; Shuo Li; Rui Song; Cheng Wang; Weidong Cao; Ramesh K. Agarwal (Ocean Engineering, 2023)

Analytical solutions on non-Darcy seepage of grouted and lined subsea tunnels under dynamic water levels - Xiang Liu; Dongchi Wang; Yu Zhang; Annan Jiang; Qian Fang; Rui Zhang (Ocean Engineering, 2023)

Lead-chlorine synergistic immobilization mechanism in municipal solid waste incineration fly ash (MSWIFA)-based magnesium potassium phosphate cement - Xing Cao; Qiushi Zhang; Weichen Yang; Lin Fang; Shiwei Liu; Rui Ma; Kai Guo; Ning Ma (Journal of Hazardous Materials, 2023)

Impact of international trade on water scarcity: An assessment by improving the Falkenmark indicator - Rui Zhong; Aifang Chen; Dandan Zhao; Ganquan Mao; Xu Zhao; Hao Huang; Junguo Liu (Journal of Cleaner Production, 2023)

Innovation incentives and urban carbon dioxide emissions: A quasi-natural experiment based on fast-tracking green patent applications in China - Rui Liu; Xuezhong Zhu; Meiyang Zhang; Cheng Hu (Journal of Cleaner Production, 2023)

Recovery of nickel, phosphorus and nitrogen from electroless nickel-plating wastewater using bipolar membrane electrodialysis - Yaoxing Liu; Xiaoyu Wu; Xiaoyun Wu; Liping Dai; Jianguo Ding; Xin Ye; Riyao Chen; Rui Ding; Jianxi Liu; Yanchao Jin; Bart Van der Bruggen (Journal of Cleaner Production, 2023)

Occurrence, sources, and risk assessment of pyrethroid insecticides in surface water and tap water from Taihu Lake, China - Rui Wang; Shengwei Zhang; Kaiyan Xiao; Minghong Cai; Hongling Liu (Journal of Environmental Management, 2023)

Habitat quality dynamics in China's first group of national parks in recent four decades: Evidence from land use and land cover changes - Xin Chen; Le Yu; Yue Cao; Yidi Xu; Zhicong Zhao; Youbo Zhuang; Xuehua Liu; Zhenrong Du; Tao Liu; Bo Yang; Lu He; Hui Wu; et al. (Journal of Environmental Management, 2023)

Learn then match: A fast coarse-to-fine depth image-based indoor localization framework for dark environments via deep learning and keypoint-based geometry alignment - Qing Li; Rui Cao; Jiasong Zhu; Hao Fu; Baoding Zhou; Xu Fang; Sen Jia; Shenman Zhang; Kanglin Liu; Qingquan Li (ISPRS Journal of Photogrammetry and Remote Sensing, 2023)

Detrital zircon U-Pb geochronology of the Lunpola basin strata constrains the Cenozoic tectonic evolution of central Tibet - Xiaohui Liu; Rui Gao; Xiaoyu Guo; Lin Ding (Gondwana Research, 2023)

Significance of silicate liquid immiscibility for the origin of young highly evolved lithic clasts in Chang’E-5 regolith - Jing Yang; Dongyang Ju; Runlian Pang; Rui Li; Jianzhong Liu; Wei Du (Geochimica et Cosmochimica Acta, 2023)

Experimental study on non-isothermal oxidative characteristics and kinetics of methane in accelerating rate calorimetry tests - Xiaodong Tang; Wanfen Pu; Dan Wang; Shanshan Qu; Yiming Rui; Xuepei Zhao; Renbao Liu (Fuel, 2023)

Influence of collaborative disposal of sewage sludge in the fly ash partitioning and PM10 emission from a subcritical coal-fired boiler - Tianyu Liu; Chang Wen; Ke Zhou; Changkang Li; Youjian Zhu; Dapeng Wang; Rui Li; Zhenqi Jing (Fuel, 2023)

Branch development in monoculture and mixed-species plantations of Betula alnoides, Erythrophleum fordii and Pinus kesiya var. langbianensis in southwestern China - Kai-Li Liu; Chun-Sheng Wang; Bo-Yao Chen; Rui-Hui Wang; Jie Zeng (Forest Ecology and Management, 2023)

The gluten structure, starch digestibility and quality properties of pasta supplemented with native or germinated quinoa flour - Bao Xing; Zhuo Zhang; Manli Zhu; Cong Teng; Liang Zou; Rui Liu; Lizhen Zhang; Xiushi Yang; Guixing Ren; Peiyou Qin (Food Chemistry, 2023)

Identification of high iron–chelating peptides with unusual antioxidant effect from sea cucumbers and the possible binding mode - Chaozhong Fan; Xiaofan Ge; Junyu Hao; Tao Wu; Rui Liu; Wenjie Sui; Jieting Geng; Min Zhang (Food Chemistry, 2023)

Exploring the role of protein DJ-1 in quality of pale, soft and exudative (PSE) and red, firm and non-exudative (RFN) pork during post-mortem aging - Rui Liu; Keyue Li; Tianyi Yang; Lun Yang; Man Qin; Hai Yu; Mangang Wu; Qingfeng Ge; Wenbin Bao; Shenglong Wu (Food Chemistry, 2023)

Improving the viability of Lactobacillus plantarum LP90 by carboxymethylated dextran-whey protein conjugates: The relationship with glass transition temperature - Wen Li; Yunjiao Zhao; Yuan Zhao; Shunqin Li; Liyuan Yun; Zijian Zhi; Rui Liu; Tao Wu; Wenjie Sui; Min Zhang (Food Hydrocolloids, 2023)

Effects of pH and incubation temperature on properties of konjac glucomannan and zein composites with or without freeze-thaw treatment - Rui Lai; Jie Liu; Yawei Liu (Food Hydrocolloids, 2023)

Vitamin D3 enhances the antibacterial ability in head-kidney macrophages of turbot (Scophthalmus maximus L.) through C-type lectin receptors - Yawen Lan; Rui Shao; Jinjin Zhang; Jiayu Liu; Xinmeng Liao; Shufei Liang; Kangsen Mai; Qinghui Ai; Min Wan (Fish & Shellfish Immunology, 2023)

Composite organic amendment boosts soil remediation and Cd detoxification to rape under different nitrogen level - Xu Zhang; Qingkai Guan; Linghui Kong; Rui Yang; Xuesheng Liu; Juanjuan Qu; Yu Jin (European Journal of Soil Biology, 2023)

Controlled design of Na–P1 zeolite/ porous carbon composites from coal gasification fine slag for high-performance adsorbent - Rui Shu; Qixia Qiao; Feiqiang Guo; Kaiming Dong; Sha Liu; Liya Xu; Yonghui Bai; Nan Zhou (Environmental Research, 2023)

Microplastics perturb colonic epithelial homeostasis associated with intestinal overproliferation, exacerbating the severity of colitis - Shuang Xie; Rui Zhang; Zhaoyan Li; Chunru Liu; Yanyu Chen; Qinghua Yu (Environmental Research, 2023)

Overlooked mechanism of Pb immobilization on montmorillonite mediated by dissolved organic matter in manure compost - Yuanchen Zhu; Qingkai Guan; Linghui Kong; Rui Yang; Wei Wang; Yu Jin; Xuesheng Liu; Juanjuan Qu (Environmental Pollution, 2023)

Breast adipose metabolites mediates the association of tetrabromobisphenol a with breast cancer: A case-control study in Chinese population - Ai Zhang; Rui Wang; Qianfeng Liu; Zhengjun Yang; Xiaohui Lin; Jing Pang; Xiaoyu Li; Dan Wang; Jiayu He; Jianping Li; Mingyue Zhang; Yue Yu; et al. (Environmental Pollution, 2023)

Analysis of steel baffle installed on footing with dowels for resisting boulder impact - Charles W.W. Ng; Dingchen Zhang; Clarence E. Choi; Haiming Liu; Raymond C.H. Koo; Rui Chen (Engineering Geology, 2023)

Correlation analysis and modeling of human thermal sensation with multiple physiological markers: An experimental study - Kangji Li; Rui Yu; Yufei Liu; Junqiang Wang; Wenping Xue (Energy and Buildings, 2023)

Characteristics of non-point source pollution based on monitoring experiment in the Yingwugou small watershed, China - Kai Peng; Jia-ke Li; Gai-rui Hao; Yi-wen Liu; Xiang Zhou; Wei-feng Xie (Ecohydrology & Hydrobiology, 2023)

Four-armed host-defense peptidomimetics-augmented vanadium carbide MXene-based microneedle array for efficient photo-excited bacteria-killing - Xiaoqian Feng; Dongyi Xian; Jintao Fu; Rui Luo; Wenhao Wang; Yuwei Zheng; Qing He; Zhan Ouyang; Shaobin Fang; Wancong Zhang; Daojun Liu; Shijie Tang; et al. (Chemical Engineering Journal, 2023)

A systematic review of electrocoagulation technology applied for microplastics removal in aquatic environment - Fangyuan Liu; Chunpeng Zhang; Huilin Li; Nnanake-Abasi O. Offiong; Yuhang Bi; Rui Zhou; Hejun Ren (Chemical Engineering Journal, 2023)

Fluoroalkane modified cationic polymers for personalized mRNA cancer vaccines - Junyan Li; Yuanyuan Wu; Jian Xiang; Hairong Wang; Qi Zhuang; Ting Wei; Zhiqin Cao; Qingyang Gu; Zhuang Liu; Rui Peng (Chemical Engineering Journal, 2023)

Facile fabrication of hierarchically porous melamine foam@COF composite for sample treatment of non-targeted food safety analysis and oil/water separation - Wei Li; Wei-Liang Jin; Hong-Xin Jiang; Rui Wang; Hao Jia; Jing-Qi Liu; An-Na Tang; Li-Na Zhu; De-Ming Kong (Chemical Engineering Journal, 2023)

Balance the rapid release of insecticide microcapsules using double-layer shielding effect when the foliar application - Rui Wang; Song Liu; Feng-shou Sun; Xin Yu; Xiao Liu; Bei-xing Li; Wei Mu; Da-xia Zhang; Feng Liu (Chemical Engineering Journal, 2023)

Combining a novel biofilm reactor with a constructed wetland for rural, decentralized wastewater treatment - Rui Zhang; Xianchang Liu; Lutian Wang; Pan Xu; Kai Li; Xiaoxiao Chen; Rong Meng; Yuewu Pu; Xuetong Yang; Diederik P.L. Rousseau; Stijn W.H. Van Hulle (Chemical Engineering Journal, 2023)

Insights into the practicability of electrochemical enhanced heterogeneous activation of peroxymonosulfate for the treatment of liquid waste during penicillin g production - Lili Liu; Jun Wang; Jianan Li; Meng Zhang; Yunxiao Zhang; Rui Zhan; Jiaxin Li; Zhiping Wang (Chemical Engineering Journal, 2023)

Scaled-up microwave pyrolysis of sludge for hydrogen-rich biogas and life cycle assessment: Parameters synergistic optimization, carbon footprint analysis and technology upgrade - Junhao Lin; Shiwei Liu; Zijian Han; Rui Ma; Chongwei Cui; Shichang Sun (Chemical Engineering Journal, 2023)

Robust emission in near-infrared II of lanthanide nanoprobes conjugated with Au (LNPs-Au) for temperature sensing and controlled photothermal therapy - Guofeng Liu; Zhenxing Wang; Wan Sun; Xiaohui Lin; Rui Wang; Chonghui Li; Li Zong; Zuoling Fu; Hanping Liu; Shicai Xu (Chemical Engineering Journal, 2023)

A High-efficiency blue-LED-excitable NIR-II-emitting MgO:Cr3+,Ni2+ phosphor for future broadband light source toward multifunctional NIR spectroscopy applications - Bo-Mei Liu; Xiao-Xuan Guo; Lu-Yu Cao; Lin Huang; Rui Zou; Zhi Zhou; Jing Wang (Chemical Engineering Journal, 2023)

Formation mechanism and metabolic pathways of photogranule in batch and continuous-flow mode under high salinity stress - Jing Zhu; Hong You; Zhipeng Li; Binghan Xie; Weirun Li; Shaojie Qi; Rui Wang; Hongying Chen; Binyu Ma; Yi Ding; Haili Tan; Feng Liu; et al. (Chemical Engineering Journal, 2023)

Microfluidic emulsification techniques for controllable emulsion production and functional microparticle synthesis - Wei Wang; Bing-Yu Li; Mao-Jie Zhang; Yao-Yao Su; Da-Wei Pan; Zhuang Liu; Xiao-Jie Ju; Rui Xie; Yousef Faraj; Liang-Yin Chu (Chemical Engineering Journal, 2023)

Near-infrared I/II emission and absorption carbon dots via constructing localized excited/charge transfer state for multiphoton imaging and photothermal therapy - Wen-Bo Zhao; Dan-Dan Chen; Kai-Kai Liu; Yong Wang; Rui Zhou; Shi-Yu Song; Fu-Kui Li; Lai-Zhi Sui; Qing Lou; Lin Hou; Chong-Xin Shan (Chemical Engineering Journal, 2023)

Rationally tailoring anion traps into electrospun nanofibers for highly efficient perrhenate/pertechnetate capture - Dingyang Chen; Zhaoli Liu; Shuying Li; Xiaofei Jing; Yuyang Tian; Wei Hu; Fengchao Cui; Rui Zhao; Guangshan Zhu (Chemical Engineering Journal, 2023)

Constructing a fine dispersion and chemical interface based on an electrostatic self-assembly and aqueous phase compound in GO/SiO2/SBR composites to achieve high-wear resistance in eco-friendly green tires - Rui Zhang; Jiaye Li; Stephen Jerrams; Shui Hu; Li Liu; Shipeng Wen; Liqun Zhang (Chemical Engineering Journal, 2023)

Lanthanoid hydrogen-bonded organic frameworks: Enhancement of luminescence by the coordination-promoted antenna effect and applications in heavy-metal ion sensing and sterilization - Yun-Lan Li; Hai-Ling Wang; Zhi-Chuan Chen; Zhong-Hong Zhu; Yan-Cheng Liu; Rui-Yun Yang; Fu-Pei Liang; Hua-Hong Zou (Chemical Engineering Journal, 2023)

In-situ growth of bimetallic FeCo-MOF on magnetic biochar for enhanced clearance of tetracycline and fruit preservation - Yi-Cai Jiang; Meng-Fan Luo; Zi-Nuo Niu; Si-Yuan Xu; Yue Gao; Yuan Gao; Wen-Juan Gao; Jing-Jing Luo; Rui-Lin Liu (Chemical Engineering Journal, 2023)

Interfacial modulation of organic-inorganic two-dimensional superlattices for efficient electromagnetic wave absorption - Wenjian Wang; Ke Ran; Xingwang Hou; Yilin Huang; Zidong Zhang; Dongxu He; Yuan Fang; Shuai Wang; Yu Liu; Rui Zhao; Xiao-Yu Yang; Weidong Xue (Chemical Engineering Journal, 2023)

Lattice doping of Zn boosts oxygen vacancies in Co3O4 Nanocages: Improving persulfate activation via forming Surface-Activated complex - Mei-Mei Wang; Li-Juan Liu; Jia-Rui Xi; Ying Ding; Peng-Xi Liu; Liang Mao; Bing-Jie Ni; Wei-Kang Wang; Juan Xu (Chemical Engineering Journal, 2023)

Rapid, selective, and room temperature dissolution of crystalline xylan by a hydrotrope - Qiaoling Liu; Rui Tian; Ziwen Lv; Yuying Wu; Baozhong Lv; Xiang Hao; Zhimin Xue; Feng Peng (Carbohydrate Polymers, 2023)

Investigating the concentration distribution characteristics of methane in large storage facility using desorption-concentration gradient method and CFD simulation - Yaohua Hou; Chao Chen; Hongyong Liu; Sicheng Li; Chang Liu; Rui Zhao (Building and Environment, 2023)

More intelligent and efficient thermal environment management: A hybrid model for occupant-centric thermal comfort monitoring in vehicle cabins - Xinglei He; Xiaohan Zhang; Rui Zhang; Jiaxin Liu; Xiaoyu Huang; Jinchen Pei; Jingyang Cai; Fen Guo; Yichun Wang (Building and Environment, 2023)

Water-soluble brown carbon in PM2.5 at two typical sites in Guanzhong Basin: Optical properties, sources, and implications - Xiaofei Li; Feng Yu; Yiying Song; Chao Zhang; Fangping Yan; Zhaofu Hu; Yali Lei; Lekhendra Tripathee; Rui Zhang; Jingning Guo; Yuqin Wang; Qingcai Chen; et al. (Atmospheric Research, 2023)

Positional cloning identified HvTUBULIN8 as the candidate gene for round lateral spikelet (RLS) in barley (Hordeum vulgare L.) - Dandan Qin; Gang Liu; Rui Liu; Chunchao Wang; Fuchao Xu; Qing Xu; Yu Ling; Guoqing Dong; Yanchun Peng; Shuangtao Ge; Ganggang Guo; Jing Dong; et al. (Theoretical and Applied Genetics, 2023)
Key message Map-based cloning, subcellular localization, virus-induced-gene-silencing and transcriptomic analysis reveal HvTUB8 as a candidate gene with pleiotropic effects on barley spike and leaf development via ethylene and chlorophyll metabolism. Abstract Barley lateral spikelet morphology and grain shape play key roles in grain physical quality and yield. Several genes and QTLs for these traits have been cloned or fine mapped previously. Here, we report the phenotypic and genotypic analysis of a barley mutant with round lateral spikelet (rls) from cv. Edamai 934. rls had round lateral spikelet, short but round grain, shortened awn, thick glume and dark green leaves. Histocytologic and ultrastructural analysis revealed that the difference of grain shape of rls was caused by change of cell arrangement in glume, and the dark leaf color resulted from enlarged chloroplast. HvTUBULIN8 ( HvTUB8 ) was identified as the candidate gene for rls by combination of RNA-Seq, map-based-cloning, virus-induced-gene-silencing (VIGS) and protein subcellular location. A single G-A substitution at the third exon of HvTUB8 resulted in change of Cysteine 354 to tyrosine. Furthermore, the mutant isoform Hvtub8 could be detected in both nucleus and cytoplasm, whereas the wild-type protein was only in cytoplasm and granular organelles of wheat protoplasts. Being consistent with the rare phenotype, the “A” allele of HvTUB8 was only detected in rls , but not in a worldwide barley germplasm panel with 400 accessions. VIGS confirmed that HvTUB8 was essential to maintain spike integrity. RNA-Seq results suggested that HvTUB8 may control spike morphogenesis via ethylene homeostasis and signaling, and control leaf color through chlorophyll metabolism. Collectively, our results support HvTUB8 as a candidate gene for barley spike and leaf morphology and provide insight of a novel mechanism of it in barley development.

LncRNA as potential biomarker and therapeutic target in glioma - Xun Xu; Yuan Liang; Ilgiz Gareev; Yanchao Liang; Rui Liu; Ning Wang; Guang Yang (Molecular Biology Reports, 2023)

Biological Function and Stress Response Mechanism of MYB Transcription Factor Family Genes - Rui Ma; Bowen Liu; Xi Geng; Xiao Ding; Na Yan; Xia Sun; Wenli Wang; Xianzhi Sun; Chengshu Zheng (Journal of Plant Growth Regulation, 2023)

Biofilm formation under high temperature causes the commensal bacteria Bacillus cereus WPySW2 to shift from friend to foe in Neoporphyra haitanensis in vitro model - Qiqin Liu; Rui Yang; Xiaoxiao Sun; Xinqian Zhou; Haimin Chen (Journal of Oceanology and Limnology, 2023)

Boron accumulation in soil, sediment, and plant of wastewater-irrigated areas in Tianjin, China - Qian Zhao; Rui Zhang; Lei Wang; Hongwen Sun; Chunguang Liu (Environmental Monitoring and Assessment, 2023)

Azospirillum Endophyticum sp. nov., an Endophyte of Paris Polyphylla Smith var. Yunnanensis - Peng-Chao Zhan; Rui-Feng Mao; Cong-Jian Li; Zhen Zhang; Jing-Ran Liu; Mei Tang; Xiao-Yang Zhi; Ling-Ling Yang (Current Microbiology, 2023)

NLOS signal detection and correction for smartphone using convolutional neural network and variational mode decomposition in urban environment - Qi Liu; Chengfa Gao; Rui Shang; Zihan Peng; Ruicheng Zhang; Lu Gan; Wang Gao (GPS Solutions, 2023)

Precise orbit determination for BDS-3 GEO satellites enhanced by intersatellite links - Xiaojie Li; Xiaogong Hu; Rui Guo; Chengpan Tang; Shuai Liu; Jie Xin; Jinglei Guo; Yijun Tian; Yufei Yang; Jianhua Yang; Xinglong Zhao (GPS Solutions, 2023)

Effects of combined application of nitrogen, phosphorus, and potassium fertilizers on tea (Camellia sinensis) growth and fungal community - Sheng Tang; Jingjie Zhou; Wankun Pan; Tao Sun; Mengjiao Liu; Rui Tang; Zijing Li; Qingxu Ma; Lianghuan Wu (Applied Soil Ecology, 2023)

The influence of hapten spacer arm length on antibody response and immunoassay development - Yuchen Bai; Rui Liu; Leina Dou; Weilin Wu; Wenbo Yu; Kai Wen; Xuezhi Yu; Jianzhong Shen; Zhanhui Wang (Analytica Chimica Acta, 2023)

Solar ring mission: Building a panorama of the Sun and inner-heliosphere - Yuming Wang; Xianyong Bai; Changyong Chen; Linjie Chen; Xin Cheng; Lei Deng; Linhua Deng; Yuanyong Deng; Li Feng; Tingyu Gou; Jingnan Guo; Yang Guo; et al. (Advances in Space Research, 2023)

Molecular characterization of a novel victorivirus isolated from the phytopathogenic fungus Phaeobotryon rhois - Ying Zhao; Hongyan Du; Yuanyuan Liu; Rongrong Zhong; Zhengzhe Guan; Ganlin Wang; Yuanyuan Zhang; Chenxing Wei; Mengjiao Wang; Xinru Wan; Rui Zang; Caiyi Wen; et al. (Archives of Virology, 2023)